Refractory materials and methods of forming them
Zircon refractories with controlled particle size and optimized sintering processes address high-temperature processing challenges, enhancing creep resistance and reducing blistering for alkali-free aluminosilicate glasses in TFT substrates.
Patent Information
- Application Number
- JP2023538882
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-29
- Filing Date
- 2021-12-23
- Publication Date
- 2024-12-18
- Estimated Expiration
- 2041-12-23
AI Technical Summary
Current zircon materials used in forming high-strain-point alkali-free aluminosilicate glasses for ultra-high resolution TFT substrates face issues with increased bubble formation and creep deformation at high temperatures, which are unsuitable for high-temperature processing.
Development of zircon refractories with improved properties, including controlled particle size distribution and specific composition, through processes such as isostatic pressing, sintering at optimized temperatures and cooling rates, to enhance creep resistance and reduce blistering.
The improved zircon refractories exhibit reduced blistering and creep deformation, enabling stable high-temperature processing of alkali-free aluminosilicate glasses for TFT substrates without deformation.
Smart Images

Figure 0007602650000009 
Figure 0007602650000010 
Figure 0007602650000011
Abstract
Description
[Technical field]
[0001] FIELD OF THE DISCLOSURE This disclosure relates generally to zircon refractories and methods of making and using zircon refractories, and more particularly to sintered zircon refractories and methods of making and using same. Summary of the Invention [Problem to be solved by the invention]
[0002] High strain point alkali-free aluminosilicate glasses, such as glasses for ultra-high resolution Liquid Crystal Display (LCD) substrates using amorphous silicon or oxide thin film transistors (TFTs) or organic light emitting diode (OLED) substrates using low temperature polysilicon (LTPS) TFT deposition, are designed to allow high temperature processing of TFTs (up to 700°C) without deformation. These glasses can be formed using a fusion draw process, in which liquid glass flows over the edge of a glass overflow forming block made of zircon (ZrSiO4) material and fuses at the bottom of the glass overflow forming block to form a sheet. The zircon forming block in contact with the alkali-free aluminoborosilicate glass provides good corrosion resistance and mechanical properties at the forming temperature of the glass. However, the formation of these high strain point alkali-free aluminosilicate glasses places more stringent demands on the forming block due to the high forming temperatures (+30 to 120°C). Higher forming temperatures increase the reaction rate between the glass and the zircon material, leading to higher bubble formation in the glasses with current zircon materials, which cannot be tolerated in ultra-high resolution TFT substrate applications. Secondly, higher forming temperatures promote the creep deformation rate of the zircon material, leading to greater sagging of the forming blocks (up to 10 times more deformation), which cannot be tolerated in the formation of these glasses. Thus, a new range of zircon materials with improved properties at high temperatures is needed. [Brief description of the drawings]
[0003] The present disclosure may be better understood, and its numerous features and advantages made apparent to those skilled in the art, by reference to the accompanying drawings, in which: FIG.
[0004] [Figure 1]FIG. 1 includes a flow chart illustrating a formation process according to embodiments described herein. [Diagram 2] FIG. 2 includes a diagram illustrating a particular embodiment of a glass overflow forming block. [Diagram 3] FIG. 3 includes diagrams illustrating a particular set of various cross-sectional perspective views of a glass overflow forming block. [Figure 4] FIG. 4 includes an image of the microstructure of a zircon body of a refractory material formed according to embodiments described herein. [Diagram 5] FIG. 5 includes an image of the microstructure of a zircon body of a refractory material formed according to embodiments described herein. [Figure 6] FIG. 6 contains plots of creep deformation rate versus temperature for different samples. [Figure 7] FIG. 7 includes images of the microstructure of different sample bodies formed according to embodiments herein. [Figure 8] FIG. 8 contains plots of creep deformation rate versus temperature for different samples. [Figure 9] FIG. 9 contains plots of creep deformation rate versus temperature for additional samples. [Figure 10] FIG. 10 includes a cross-sectional image of the interface between the surface of the zircon material and the glass layer after performing the blister test. [Figure 11] FIG. 11 contains plots of normalized creep deformation rate versus dopant concentration for different samples.
[0005] Those skilled in the art will appreciate that elements in the figures are illustrated for simplicity and clarity and have not necessarily been drawn to scale. For example, the dimensions of some of the elements in the figures may be exaggerated relative to other elements to help improve understanding of embodiments of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0006] The following is generally directed to refractories having a zircon body and methods of forming refractories having a zircon body. Notably, the refractories may have improved properties and / or performance. For example, the refractories may have improved creep resistance, such as improved creep deformation rate, reduced blistering, or both, at high operating temperatures. A zircon body may be defined as a refractory body formed according to embodiments described herein such that the composition of the zircon body is predominantly zircon material (i.e., the zircon body may include at least 50 wt. % zircon content, based on the total weight of the zircon body), and the zircon material is intentionally doped with one or more alkaline earth oxides and Al2O3.
[0007] According to certain embodiments, methods of forming a refractory having a zircon body according to embodiments described herein may include specific heating and / or cooling characteristics that facilitate the formation of a zircon body of a refractory having improved properties and / or performance.
[0008] Referring to FIG. 1, a process 100 for forming a refractory including a zircon body is illustrated. The process 100 may begin with block 102 forming a green body of the refractory. The green body is an unfinished body and may undergo further processing before the final formed zircon body is formed. Forming the green body may include providing a zircon batch, which may include a mixture of raw powders used in forming the zircon body. The raw powders may initially include raw raw materials, such as raw zircon material (i.e., sand), alkaline earth metal-containing materials, Al2O3-containing materials, and SiO2-containing materials. The raw raw materials may be initially processed by separating undesirable components (e.g., impurities) from the raw raw materials. The raw raw materials may be processed using classification techniques, such as particle size separation, vibration or gravity table separation, electrostatic separation, electromagnetic separation, or any combination thereof. Particle size separation may separate particles in the powder based on their size, thereby reducing the impurity content. Vibration or gravity table separation can separate particles in the powder based on density, which can reduce the amount of alumina-rich silicates and silica grains from the raw powder. Electrostatic separation can separate particles in the powder based on electrical conductivity, which can allow for the separation of titaniferous mineral particles, ilmenite and rutile. Electromagnetic separation can separate particles in the powder based on their magnetic properties. It will be appreciated that the initial processing of the raw feedstock can include any combination of the above separation methods and can include multiple applications of any of the above separation methods. It will further be appreciated that the initial processing of the raw feedstock can include incremental or parallel application of the above separation methods.
[0009] Providing the zircon batch may include combining or mixing the raw material powders and any additional materials (i.e., sintering aids, binders, other additives, etc.) by any suitable method. Mixing or batch preparation may be done dry or wet. Mixing may include an additional step of granulation. A granulation step may be added to improve the flowability of the batch and thus increase the apparent density of the green body. In one exemplary embodiment, granulation may be done using spray drying. The raw material powders may be mixed in a mixing tank and then spray dried.
[0010] Forming the green body may further include molding the spray dried powder or batch to form a green body having a particular shape using isostatic pressing. The spray dried powder forms a high flow powder that can be used to fill large isostatic pressing cans with minimal filling defects such as uneven compaction of green density, voids, or cracks. The feed powder is filled into a rubber mold that is maintained within a solid metal can. The bag is then sealed and a vacuum is applied to the feed powder. The can is then immersed in a pressure vessel filled with fluid and pressurized. After pressing, the mold is removed from the pressure vessel and the green body is removed.
[0011] The molding can be carried out at a specific pressure, for example by isostatic pressing, at a pressure of at least 50 MPa, for example at least 60 MPa, at least 70 MPa, at least 80 MPa, at least 90 MPa, at least 100 MPa, at least 110 MPa, at least 120 MPa, at least 130 MPa, at least 140 MPa, or even at least 150 MPa. The pressure can be applied to the green body in stages using isostatic pressing cycles lasting from about 10 minutes to about 120 minutes. These pressing cycles can limit defect formation during the pressing stage. The molding can also be carried out using alternative techniques such as slip casting or unidirectional pressing.
[0012] The shape of the green body can be linear, cylindrical, spherical, elliptical, or almost any other shape. In certain embodiments, the green body can be in the shape of a linear block, referred to as a blank, which can then be machined to form a glass overflow trough, a spout lip, or a bushing block. In other specific embodiments, the green body can have at least one dimension greater than 100 mm, such as greater than 200 mm, greater than 300 mm, greater than 400 mm, greater than 500 mm, greater than 600 mm, greater than 700 mm, or even greater than 800 mm. In other embodiments, the green body can be structured to more closely fit the final part, such as a forming block, to limit post-forming processes.
[0013] 2 illustrates a forming block 200. The forming block 200 may include an overflow trough portion 202 and a tapered portion 204. The overflow trough portion 202 may include a trough having a depth that decreases along the length of the forming block 200. FIG. 3 includes a cross-sectional view of an example shape of the tapered portion 204. More specifically, the tapered portion may include a wedge shape 2042, a concave shape 2044, or a convex shape 2046. Other shapes may be used to meet the needs or requirements for a particular application.
[0014] After the green body is formed, the process 100 may continue at block 104 with forming the green body into a refractory material comprising a zircon body. The green body may be heated in an oven, heater, furnace, or the like to form a body comprising the zircon material. The heating process may include an initial heating, where moisture, solvent, or another volatile component is evaporated, organic material is evaporated, or any combination thereof. The initial heating may be performed at a temperature in the range of 100° C. to 300° C. for a period in the range of 10 hours to 200 hours.
[0015] Following the initial heating, the green body may be heated to form a sintered zircon body. In one embodiment, heating the green body may include controlling a heating temperature, a soaking period, a heating rate, or any combination thereof to facilitate the formation of a refractory having improved properties and / or performance. In one embodiment, heating the green body may include heating at one or more specific heating temperatures for a heating period. In a particular embodiment, sintering the green body may include heating the green body at a first temperature for a first period and heating the green body at a second temperature lower than the first temperature for a second period to form a refractory including the zircon body. In one aspect, the first temperature may include a maximum heating temperature that may facilitate the formation of a refractory having improved properties and / or performance. For example, the first temperature may be at least 1500° C., at least 1550° C., or at least 1600° C. In another example, the first temperature may be 1700° C. or less, 1650° C. or less, or 1625° C. or less. Additionally, the first temperature can be within a range that includes any of the maximum and minimum temperatures described herein.
[0016] In another embodiment, the first period of time can be at least 2 hours, at least 4 hours, at least 6 hours, at least 8 hours, or at least 10 hours. In further embodiments, the first period of time can be 5 days or less, 4 days or less, 3 days or less, 2 days or less, 24 hours or less, 20 hours or less, 18 hours or less, 16 hours or less, 14 hours or less, or 12 hours or less. Additionally, the first period of time can be within a range including any of the minimum and maximum times described herein. For example, the substrate can be heated at the first temperature for at least 6 hours to 5 days.
[0017] In one embodiment, the second temperature can include a sintering temperature of the zircon batch, which can facilitate the formation of a refractory having improved properties and / or performance. For example, the second temperature can be at least 1250° C., at least 1300° C., at least 1350° C., at least 1400° C., or at least 1425° C. In another example, the second temperature can be no greater than 1525° C., no greater than 1500° C., no greater than 1475° C., or no greater than 1450° C. Additionally, the second temperature can be within a range that includes any of the minimum and maximum temperatures described herein.
[0018] In further embodiments, the second period of time can be at least 10 hours, at least 14 hours, at least 18 hours, at least 20 hours, at least 24 hours, at least 30 hours, at least 36 hours, or at least 2 days. In other embodiments, the second period of time can be 6 days or less, 5 days or less, 4 days or less, 3 days or less, 60 hours or less, 50 hours or less, 48 hours or less, 44 hours or less, 40 hours or less, 36 hours or less, or 30 hours or less. Additionally, the second period of time can be within a range including any of the minimum or maximum times described herein.
[0019] According to one embodiment, heating the green body may include heating the green body at a particular heating rate that may facilitate the formation of a refractory having improved performance and properties. In one aspect, the heating rate may be at least 1° C. / hr, e.g., at least 3° C. / hr, at least 5° C. / hr, at least 8° C. / hr, at least 10° C. / hr, at least 13° C. / hr, at least 15° C. / hr, at least 18° C. / hr, at least 20° C. / hr, at least 23° C. / hr, at least 25° C. / hr, at least 28° C. / hr, or even at least 29° C. / hr. In another aspect, the heating rate may be 30° C. / hr or less, e.g., 27° C. / hr or less, 25° C. / hr or less, 22° C. / hr or less, 20° C. / hr or less, 17° C. / hr or less, 15° C. / hr or less, 12° C. / hr or less, 10° C. / hr or less, 7° C. / hr or less, 5° C. / hr or less, or even 3° C. / hr or less. It will be appreciated that the heating rate may be any value between any of the minimum and maximum values listed above. It will be further appreciated that the heating rate may be any value within a range between any of the maximum and minimum values listed above.
[0020] In one embodiment, heating the green body to form the zircon body can include a cooling rate that can facilitate the formation of a refractory having improved properties and / or performance. In one aspect, heating the green body can include decreasing the heating temperature from a first temperature to a second temperature at a specific cooling rate. For example, the cooling rate can be less than 5° C. / hr, e.g., 4.5° C. / hr or less, 3.7° C. / hr or less, 3.1° C. / hr or less, 2.7° C. / hr or less, 1.8° C. / hr or less, 1.7° C. / hr or less, 1.6° C. / hr or less, 1.5° C. / hr or less, 1.4° C. / hr or less, 1.3° C. / hr or less, 1.2° C. / hr or less, 1° C. / hr or less, 0.8° C. / hr or less, 0.7° C. / hr or less, 0.6° C. / hr or less, 0.5° C. / hr or less, 0.4° C. / hr or less, 0.3° C. / hr or less, 0.2° C. / hr or less, or 0.1° C. / hr or less. In another example, the cooling rate can be at least 0.01° C. / hr, at least 0.02° C. / hr, at least 0.03° C. / hr, at least 0.04° C. / hr, at least 0.05° C. / hr, at least 0.06° C. / hr, at least 0.07° C. / hr, at least 0.08° C. / hr, at least 0.09° C. / hr, at least 0.1° C. / hr, at least 0.2° C. / hr, at least 0.3° C. / hr, at least 0.4° C. / hr, at least 0.5° C. / hr, at least 0.6° C. / hr, at least 0.7° C. / hr, at least 0.8° C. / hr, at least 0.9° C. / hr, at least 1° C. / hr, at least 1.1° C. / hr, at least 1.2° C. / hr, at least 1.3° C. / hr, at least 1.4° C. / hr, at least 1.5° C. / hr, at least 1.6° C. / hr, at least 1.7° C. / hr, or at least 1.8° C. / hr. Additionally, the cooling rate can be any value within a range including any of the maximum and minimum values stated herein.
[0021] After reading this disclosure, one of skill in the art will also understand that heating the block may be done at a faster rate at lower temperatures than at higher temperatures, and in some cases no dipping may occur between these temperatures.
[0022] In one embodiment, the process 100 may further include cooling the sintered body at a specific cooling rate to facilitate the formation of a refractory having improved properties and / or performance. In one aspect, the sintered body may be cooled from the second temperature to ambient temperature. In one aspect, the sintered body may be cooled at a cooling rate including a rate of 35° C. / hr or less, 30° C. / hr or less, 25° C. / hr or less, 20° C. / hr or less, 10° C. / hr or less, 9° C. / hr or less, 8° C. / hr or less, 7° C. / hr or less, 6° C. / hr or less, 5° C. / hr or less, 4° C. / hr or less, 3° C. / hr or less, 2° C. / hr or less, 1° C. / hr or less, 0.9° C. / hr or less, or 0.8° C. / hr or less. In further embodiments, the sintered body may be cooled at a cooling rate of at least at least 0.03°C / hr, at least 0.04°C / hr, at least 0.05°C / hr, at least 0.06°C / hr, at least 0.07°C / hr, at least 0.08°C / hr, at least 0.09°C / hr, at least 0.1°C / hr, at least 0.2°C / hr, at least 0.3°C / hr, at least 0.4°C / hr, at least 0.5°C / hr, at least 0.6°C / hr, at least 0.7°C / hr, at least 0.8°C / hr, at least 0.9°C / hr, at least 1°C / hr, at least 2°C / hr, at least 3°C / hr, at least 4°C / hr, at least 5°C / hr, at least 6°C / hr, at least 7°C / hr, at least 8°C / hr, at least 9°C / hr, at least 10°C / hr, or at least 15°C / hr. Additionally, the sintered body may be cooled at a cooling rate that may be any value within the range including any of the minimum and maximum values described herein.
[0023] The shape of the body after sintering generally corresponds to the shape of the green body before sintering. Thus, the body may have any of the shapes as described above for the green body. Some shrinkage may occur during sintering, and the body may be smaller than the green body.
[0024] After initial processing and milling, the raw powder in the zircon batch may include zircon grains that may have a particular median (D50) grain size. For example, the zircon grains may have a median (D50) grain size of 15 μm or less, such as 14 μm or less, 12 μm or less, 10 μm or less, 9 μm or less, 8 μm or less, 7 μm or less, 6 μm or less, 5 μm or less, 4 μm or less, 3 μm or less, or even 2 μm or less. According to yet another example, the zircon grains may have a median (D50) grain size of at least 1 μm, such as at least 2 μm, at least 3 μm, at least 4 μm, at least 5 μm, at least 6 μm, at least 7 μm, at least 8 μm, at least 9 μm, at least 10 μm, at least 12 μm, or even at least 14 μm. It will be appreciated that the zircon grains may have a median (D50) grain size of any value between any of the minimum and maximum values listed above. It will be further understood that the zircon grains may have a median (D50) grain size of any value within the range between any of the above maximum and minimum values. According to yet other embodiments, the raw powder in the zircon batch may have a controlled grain size distribution such that the zircon grains have a particular D90 grain size. For example, the zircon grains may have a D90 grain size of 40 μm or less, e.g., 30 μm or less, 20 μm or less, 15 μm or less, or even 10 μm or less. In still other cases, the zircon grains may have a D90 grain size of at least 5 μm, e.g., at least 10 μm, at least 15 μm, at least 20 μm, or even at least 30 μm. It will be further understood that the zircon grains may have a D90 grain size of any value within the range between any of the above minimum and maximum values. It will be further understood that the zircon grains may have a D90 grain size of any value within the range between any of the above maximum and minimum values.
[0025] According to yet another embodiment, the raw powder in the zircon batch may have a controlled particle size distribution such that the zircon grains have a particular D10 grain size. For example, the zircon grains may have a D10 grain size of at least 0.2 μm, such as at least 0.5 μm, at least 0.8 μm, or even at least 1.0 μm. In still other cases, the raw powder may have a D10 grain size of 1.1 μm or less, such as at most 1.0 μm, at most 0.8 μm, or even at most 0.5 μm. It will be appreciated that the raw powder may have a D10 grain size of any value within the range between any of the maximum and minimum values listed above. It will be further appreciated that the raw powder may have a D10 grain size of any value within the range between any of the maximum and minimum values listed above.
[0026] According to yet another embodiment, the raw powder in the zircon batch may have a broad particle size distribution. According to yet another embodiment, the raw powder in the zircon batch may have a non-Gaussian particle size distribution. According to certain embodiments, the non-Gaussian particle size distribution of the raw powder may include a distribution using at least two different average particle sizes. One such distribution may be a bimodal particle size distribution. In certain cases, it may be preferable to select at least one particle size that is significantly larger than another particle size. As will be further understood, more modes, such as three, four, or more, may be used when forming the selected non-Gaussian particle size distribution for the raw powder in the zircon batch. According to yet another embodiment, the broad particle size distribution may not necessarily include the selection and combination of two (or more) separate particle sizes, but may include the creation of a particular broad particle size distribution with representative particle size uniformity over the entire range of the distribution.
[0027] The zircon batch may include a particular content of zircon, for example, the zircon batch may include at least 50% by weight, e.g., at least 52% by weight, at least 53% by weight, at least 54% by weight, at least 55% by weight, at least 56% by weight, at least 57% by weight, at least 57.5% by weight, at least 58% by weight, at least 58.5% by weight, at least 59% by weight, at least 59.5% by weight, at least 60% by weight, at least 60.5% by weight, at least 61% by weight, at least 61.5% by weight, at least 62 ... In some embodiments, the zircon content may be at least 62%, at least 62.5%, at least 63%, at least 62.5%, at least 64%, at least 64.5%, at least 65.5%, at least 66%, at least 66.5%, at least 67%, at least 68%, at least 69%, at least 70%, at least 75%, at least 80%, at least 85%, at least 90%, or even at least 92% by weight. According to yet another embodiment, the zircon batch comprises 99% or less by weight, e.g., 95% or less by weight, 90% or less by weight, 85% or less by weight, 80% or less by weight, 75% or less by weight, 70% or less by weight, 69% or less by weight, 68% or less by weight, 67% or less by weight, 66.5% or less by weight, 66% or less by weight, at least 66.5% by weight, 65% or less by weight, 64.5% or less by weight, 64% or less by weight, 63.5% or less by weight, based on the total weight of the zircon batch. The zircon content may be 53 wt% or less, 62.5 wt% or less, 62 wt% or less, 61.5 wt% or less, 61 wt% or less, 60.5 wt% or less, 60 wt% or less, 59.5 wt% or less, 59 wt% or less, 58 wt% or less, 58 wt% or less, 57 wt% or less, 57 wt% or less, 56 wt% or less, 55 wt% or less, 54 wt% or less, 53 wt% or less, 52 wt% or less, or even 51 wt% or less. It will be appreciated that the zircon content in wt% relative to the total weight of the zircon batch may be any value between any of the minimum and maximum values set forth above. It will be further appreciated that the zircon content in wt% relative to the total weight of the zircon batch may be within a range between any of the minimum and maximum values set forth above.The contents of elements in a batch of zircon can be determined by Inductively Coupled Plasma (ICP) analysis.
[0028] According to another specific embodiment, the zircon batch may include a specific content of the Al2O3-containing component. For example, the zircon batch may include an Al2O3-containing component of 10 wt% or less, for example, an Al2O3-containing component of 9 wt% or less, an Al2O3-containing component of 8 wt% or less, an Al2O3-containing component of 7 wt% or less, an Al2O3-containing component of 6.7 wt% or less, an Al2O3-containing component of 6.5 wt% or less, an Al2O3-containing component of 6.3 wt% or less, an Al2O3-containing component of 6 wt% or less, an Al2O3-containing component of 5.8 wt% or less, an Al2O3-containing component of 5.5 wt% or less, an Al2O3-containing component of 5.5 wt% or less, an Al2O3-containing component of 5.2 wt% or less, an Al2O3-containing component of 5 wt% or less, an Al2O3-containing component of 4.8 wt% or less, an Al2O3-containing component of 4.7 wt% or less, or an Al2O3-containing component of 4.5 wt% or less, based on the total weight of the zircon batch. According to yet another embodiment, the zircon batch has at least 0.2 wt. % of the Al2O3-containing component, e.g., at least 0.5 wt. % of the Al2O3-containing component, at least 1.0 wt. % of the Al2O3-containing component, at least 1.5 wt. % of the Al2O3-containing component, at least 1.6 wt. % of the Al2O3-containing component, at least 1.7 wt. % of the Al2O3-containing component, at least 1.8 wt. % of the Al2O3-containing component, at least 1.9 wt. % of the Al2O3-containing component, at least 2.0 wt. % of the Al2O3-containing component, at least 2.1 wt. % of the Al2O3-containing component, at least 2.2 wt. % of the Al2O3-containing component, at least 2.3 wt. % of the Al2O3-containing component, at least % Al2O3-containing component, at least 2.4 wt. % Al2O3-containing component, at least 2.5 wt. % Al2O3-containing component, at least 2.7 wt. % Al2O3-containing component, at least 2.9 wt. % Al2O3-containing component, at least 3.1 wt. % Al2O3-containing component, at least 3.3 wt. % Al2O3-containing component, at least 3.5 wt. % Al2O3-containing component, at least 3.8 wt. % Al2O3-containing component, at least 4 wt. % Al2O3-containing component, at least 4.2 wt. % Al2O3-containing component, at least 4.4 wt. % Al2O3-containing component, at least 4.5 wt. % Al2O3-containing component, at least 4.7 wt. % Al2O3-containing component, or even at least 5 wt. % Al2O3-containing component.It will be appreciated that the content of the Al2O3-containing component in weight percent relative to the total weight of the zircon batch can be any value between any of the minimum and maximum values set forth above. It will be further appreciated that the content of the Al2O3-containing component in weight percent relative to the total weight of the zircon batch can be within a range between any of the minimum and maximum values set forth above.
[0029] According to another particular embodiment, the Al2O3-containing component in the zircon batch can include alumina. According to yet another embodiment, the Al2O3-containing component in the zircon batch can include a specific alumina content. For example, the Al2O3-containing component in the zircon batch can comprise at least 1 wt.% alumina, e.g., at least 2 wt.% alumina, at least 5 wt.% alumina, at least 10 wt.% alumina, at least 15 wt.% alumina, at least 20 wt.% alumina, at least 25 wt.% alumina, at least 30 wt.% alumina, at least 35 wt.% alumina, at least 40 wt.% alumina, at least 45 wt.% alumina, at least 50 wt.% alumina, at least 55 wt.% alumina, at least 60 wt.% alumina, at least 65 wt.% alumina, at least 70 wt.% alumina, at least 75 wt.% alumina, at least 80 wt.% alumina, at least 85 wt.% alumina, at least 90 wt.% alumina, at least 95 wt.% alumina, or the Al2O3-containing component can even consist essentially of alumina, based on the total weight of the Al2O3-containing component. It will be appreciated that the alumina content in the Al2O3-containing component in the zircon batch can be any value or any value between at least any of the above values.
[0030] According to another particular embodiment, the Al2O3-containing component in the zircon batch can include corundum. According to yet another embodiment, the Al2O3-containing component in the zircon batch can include a specific content of corundum. For example, the Al2O3-containing component in the zircon batch may comprise at least 1 weight percent corundum, e.g., at least 2 weight percent corundum, at least 5 weight percent corundum, at least 10 weight percent corundum, at least 15 weight percent corundum, at least 20 weight percent corundum, at least 25 weight percent corundum, at least 30 weight percent corundum, at least 35 weight percent corundum, at least 40 weight percent corundum, at least 45 weight percent corundum, at least 50 weight percent corundum, at least 55 weight percent corundum, at least 60 weight percent corundum, at least 65 weight percent corundum, at least 70 weight percent corundum, at least 75 weight percent corundum, at least 80 weight percent corundum, at least 85 weight percent corundum, at least 90 weight percent corundum, at least 95 weight percent corundum, or the Al2O3-containing component may even consist essentially of corundum. It will be understood that the corundum content in the Al2O3-containing component in the zircon batch can be any value or any value between at least any of the above values.
[0031] According to yet another embodiment, the Al2O3-containing component in the zircon batch may include a particular content of crystallographic form of alumina (i.e., boehmite). For example, the Al2O3-containing component in the zircon batch may include at least 1 wt. % of crystallographic form of alumina, e.g., at least 2 wt. % of crystallographic form of alumina, at least 5 wt. % of crystallographic form of alumina, at least 10 wt. % of crystallographic form of alumina, at least 15 wt. % of crystallographic form of alumina, at least 20 wt. % of crystallographic form of alumina, at least 25 wt. % of crystallographic form of alumina, at least 30 wt. % of crystallographic form of alumina, at least 35 wt. % of crystallographic form of alumina, at least 40 wt. % of crystallographic form of alumina, at least 45 wt. % of crystallographic form of alumina, at least 50 wt. % of crystallographic form of alumina, at least 60 wt. % of crystallographic form of alumina, at least 70 wt. % of crystallographic form of alumina, at least 80 wt. % of crystallographic form of alumina, at least 90 wt. % of crystallographic form of alumina, at least 10 ... The Al2O3-containing component may comprise at least 50% by weight of alumina in crystallographic form, at least 55% by weight of alumina in crystallographic form, at least 60% by weight of alumina in crystallographic form, at least 65% by weight of alumina in crystallographic form, at least 70% by weight of alumina in crystallographic form, at least 75% by weight of alumina in crystallographic form, at least 80% by weight of alumina in crystallographic form, at least 85% by weight of alumina in crystallographic form, at least 90% by weight of alumina in crystallographic form, at least 95% by weight of alumina in crystallographic form, or the Al2O3-containing component may even consist essentially of alumina in crystallographic form. It will be understood that the content of alumina in crystallographic form in the Al2O3-containing component in the zircon batch may be any value or any value between at least any of the above values.
[0032] According to a particular embodiment, the Al2O3-containing component in the zircon batch may include mullite. According to yet another embodiment, the Al2O3-containing component in the zircon batch may include a particular content of mullite. For example, the Al2O3-containing component in the zircon batch can include at least 1 wt.% mullite, e.g., at least 2 wt.% mullite, at least 5 wt.% mullite, at least 10 wt.% mullite, at least 15 wt.% mullite, at least 20 wt.% mullite, at least 25 wt.% mullite, at least 30 wt.% mullite, at least 35 wt.% mullite, at least 40 wt.% mullite, at least 45 wt.% mullite, at least 50 wt.% mullite, at least 55 wt.% mullite, at least 60 wt.% mullite, at least 65 wt.% mullite, at least 70 wt.% mullite, at least 75 wt.% mullite, at least 80 wt.% mullite, at least 85 wt.% mullite, at least 90 wt.% mullite, at least 95 wt.% mullite, or the Al2O3-containing component can even consist essentially of mullite, based on the total weight of the Al2O3-containing component. It will be understood that the mullite content in the Al2O3-containing component in the zircon batch can be any value or can be any value between at least any of the above values.
[0033] According to yet another embodiment, the mullite in the zircon batch is Al6Si2O 13 According to yet another embodiment, the mullite in the zircon batch may include a specific content of Al6Si2O 13 For example, the mullite in the zircon batch may contain at least 1 wt. % Al6Si2O 13 , e.g., at least 2 wt.% Al6Si2O 13 , at least 2.5% by weight of Al6SiO2 13 , at least 2.9% by weight of Al6SiO2 13 , at least 5% by weight of Al6SiO2 13 , at least 10% by weight of Al6Si2O 13 , at least 15% by weight of Al6SiO213 , at least 20% by weight of Al6Si2O 13 , at least 25% by weight of Al6SiO2 13 , at least 30% by weight of Al6SiO2 13 , at least 35% by weight of Al6SiO2 13 , at least 40% by weight of Al6SiO2 13 , at least 45% by weight of Al6SiO2 13 , at least 50% by weight of Al6Si2O 13 , at least 55% by weight of Al6Si2O 13 , at least 60% by weight of Al6Si2O 13 , at least 65% by weight of Al6Si2O 13 , at least 70% by weight of Al6Si2O 13 , at least 75% by weight of Al6Si2O 13 , at least 80% by weight of Al6Si2O 13 , at least 85% by weight of Al6Si2O 13 , at least 90% by weight of Al6Si2O 13 , at least 95% by weight of Al6Si2O 13 Or the mullite in the zircon batch may further comprise Al6Si2O 13 In the zircon batch, the batch may consist essentially of Al6Si2O 13 It will be understood that the content of can be any value or can be any value between at least any of the above values.
[0034] According to yet another particular embodiment, the Al2O3-containing component may include an aluminosilicate species. According to yet another embodiment, the aluminosilicate species may include at least one of non-stoichiometric mullite, stoichiometric mullite, and combinations thereof. According to yet another embodiment, the Al2O3-containing component may include a combination of an aluminate species and an aluminosilicate species. According to yet another embodiment, the aluminosilicate species is present in a content greater than the aluminate species. According to another particular embodiment, the zircon batch may include a particular content of a SiO2 component. The SiO2 component may include a combination of SiO2 added to the zircon batch as part of the zircon material, SiO2 added to the zircon batch as part of the Al2O3-containing component, and SiO2 added to the zircon batch as free silica. Free silica may be defined as SiO2 that is not bound as part of the crystalline form of the zircon material or the Al2O3-containing component. For example, the zircon batch may comprise, based on the total weight of the zircon batch, an SiO2 component of 34.5 wt.% or less, an SiO2 component of 33 wt.% or less, an SiO2 component of 32.5 wt.% or less, an SiO2 component of 32 wt.% or less, an SiO2 component of 31.5 wt.% or less, an SiO2 component of 30 wt.% or less, an SiO2 component of 29.5 wt.% or less, an SiO2 component of 29 wt.% or less, an SiO2 component of 28.5 wt.% or less, an SiO2 component of 28 wt.% or less, an SiO2 component of 27.5 wt.% or less, an SiO2 component of 27 wt.% or less, or even an SiO2 component greater than 26.5 wt.%.According to yet another embodiment, the zircon batch may comprise at least 25.5 wt.% of the SiO2 component, at least 26 wt.% of the SiO2 component, at least 26.5 wt.% of the SiO2 component, at least 27 wt.% of the SiO2 component, at least 27.5 wt.% of the SiO2 component, at least 28 wt.% of the SiO2 component, at least 28.5 wt.% of the SiO2 component, at least 29 wt.% of the SiO2 component, at least 29.5 wt.% of the SiO2 component, at least 30 wt.% of the SiO2 component, at least 30.5 wt.% of the SiO2 component, at least 31 wt.% of the SiO2 component, at least 31.5 wt.% of the SiO2 component, at least 32 wt.% of the SiO2 component, at least 32.5 wt.% of the SiO2 component, at least 33 wt.% of the SiO2 component, at least 33.5 wt.% of the SiO2 component, about 34 wt.% of the SiO2 component, or even at least 34.5 wt.% of the SiO2 component, based on the total weight of the zircon batch. It will be appreciated that the content of the SiO2 component in weight percent relative to the total weight of the zircon batch can be any value between any of the minimum and maximum values set forth above. It will be further appreciated that the content of the SiO2 component in weight percent relative to the total weight of the zircon batch can be within a range between any of the minimum and maximum values set forth above.
[0035] According to yet another embodiment, the zircon batch may include a particular content of free silica, for example, the zircon batch may include 4.5% or less free silica by weight, e.g., 4.0% or less free silica, 3.9% or less free silica, 3.8% or less free silica, 3.7% or less free silica, 3.6% or less free silica, 3.5% or less free silica, 3.4% or less free silica, 3.3% or less free silica, 3.2% or less free silica, 3.1% or less free silica, 3.0% or less free silica, 2.9% or less free silica, 2.8% or less free silica, 2.7% or less free silica, based on the total weight of the zircon batch. free silica, up to 2.6% free silica, up to 2.5% free silica, up to 2.4% free silica, up to 2.3% free silica, up to 2.2% free silica, up to 2.1% free silica, up to 2.0% free silica, up to 1.9% free silica, up to 1.8% free silica, up to 1.7% free silica, up to 1.6% free silica, up to 1.5% free silica, up to 1.4% free silica, up to 1.3% free silica, up to 1.2% free silica, up to 1.1% free silica.According to another particular embodiment, the zircon batch has at least 0.1 wt. % free silica, e.g., at least 0.5 wt. % free silica, at least 0.6 wt. % free silica, at least 0.7 wt. % free silica, at least 0.8 wt. % free silica, at least 0.9 wt. % free silica, at least 1.0 wt. % free silica, at least 1.1 wt. % free silica, at least 1.1 wt. % free silica, at least 1.2 wt. % free silica, at least 1.3 wt. % free silica, at least 1.4 wt. % free silica, at least 1.5 wt. % free silica, at least 1.6 wt. % free silica, at least 1.7 wt. % free silica, at least 1.8 wt. % free silica, at least 1.9 wt. % free silica, at least 2.0 wt. % free silica, at least 2.1 wt. % free silica, at least 2.2 wt. % free silica, at least 2.3 wt. % free silica, at least 2.4 wt. % free silica, at least 2.5 wt. % free silica, at least 2.6 wt. % free silica, at least 2.7 wt. % free silica, at least 2.8 wt. % free silica, at least 2.9 wt. % free silica, at least 3.0 wt. % free silica, at least 3.1 wt. % free silica, at least 3.2 wt. % free silica, at least 3.3 wt. % free silica, at least 3.4 wt. % free silica, at least 3.5 wt. % free silica, at least 3.6 wt. % free silica, at least 3.7 wt. % free silica, at least 3 % free silica, at least 2.2% free silica, at least 2.3% free silica, at least 2.4% free silica, at least 2.5% free silica, at least 2.6% free silica, at least 2.7% free silica, at least 2.8% free silica, at least 2.9% free silica, at least 3.0% free silica, at least 3.1% free silica, at least 3.2% free silica, at least 3.3% free silica, at least 3.4% free silica, at least 3.5% free silica, at least 3.6% free silica, at least 3.7% free silica, at least 3.8% free silica, at least 3.9% free silica, at least 4.0% free silica, or even at least 4.5% free silica. It will be appreciated that the content of free silica in weight percent relative to the total weight of the zircon batch can be any value between any of the minimum and maximum values listed above. It will be further understood that the free silica content, in weight percent, based on the total weight of the zircon batch, can be within a range between any of the minimum and maximum values set forth above.
[0036] According to yet another embodiment, the zircon batch has a specific ratio C SiO2 / CM AlCCM SiO2 can represent the content of SiO2 component in weight percent relative to the total weight of the zircon batch, and CM AlC can represent the content of the Al2O3-containing component in weight percent relative to the total weight of the zircon batch. For example, the zircon batch can have a ratio C M of at least 5, e.g., at least 8, at least 10, at least 13, at least 15, at least 18, at least 20, at least 23, at least 25, at least 28, at least 30, at least 33, at least 35, at least 38, at least 40, at least 43, at least 45, or even at least 48. SiO2 / CM AlC According to another embodiment, the zircon batch may have a ratio CM of 50 or less, e.g., 47 or less, 45 or less, 42 or less, 40 or less, 37 or less, 35 or less, 32 or less, 30 or less, 27 or less, 20 or less, 17 or less, 12 or less, 10 or less, or even 7 or less. SiO2 / CM AlC It may include the following: SiO2 / CM AlC It will be appreciated that CM can be any value between any of the minimum and maximum values listed above. SiO2 / CM AlC It will be further understood that may be within a range between any of the minimum and maximum values listed above.
[0037] According to yet another embodiment, the zircon batch has a specific ratio C FS / CM AlC CM FS can represent the free silica content in wt% relative to the total weight of the zircon batch, and C AlC can represent the content of the Al2O3-containing component in weight percent relative to the total weight of the zircon batch. For example, the zircon batch may have a ratio C M of at least 0.3, e.g., at least 0.5, at least 0.7, at least 1.0, at least 1.3, at least 1.5, at least 1.7, at least 2.0, at least 2.3, at least 2.7, at least 3.0, at least 3.3, at least 3.5, or even at least 3.7. FS / CMAlC According to another embodiment, the zircon batch may have a ratio CM of 3.8 or less, e.g., 3.5 or less, 3.3 or less, 3.0 or less, 2.8 or less, 2.5 or less, 2.3 or less, 2.0 or less, 1.8 or less, 1.5 or less, 1.3 or less, 1.0 or less, 0.8 or less, or even 0.5 or less. FS / CM AlC It may include the following: FS / CM AlC It will be appreciated that CM can be any value between any of the minimum and maximum values listed above. FS / CM AlC It will be further understood that may be within a range between any of the minimum and maximum values listed above.
[0038] According to yet another embodiment, the zircon batch has a specific ratio C AlC / CM Z CM ALC can represent the content of Al2O3-containing components in weight percent relative to the total weight of the zircon batch, and C M Z can represent the zircon content in weight percent relative to the total weight of the mixture. For example, the zircon batch may have a ratio C M of 0.08 or less, e.g., 0.075 or less, 0.07 or less, 0.065 or less, 0.06 or less, 0.055 or less, 0.05 or less, 0.045 or less, 0.04 or less, 0.035 or less, 0.030 or less, 0.025 or less, 0.02 or less, 0.015 or less, or even 0.01 or less. AlC / CM Z According to yet another embodiment, the zircon batch may include a CM of at least 0.002, e.g., at least 0.005, at least 0.01, at least 0.02, at least 0.03, at least 0.035, at least 0.04, at least 0.045, at least 0.05, at least 0.055, at least 0.06, at least 0.065, at least 0.07, at least 0.075, at least 0.08, at least 0.085, or even at least 0.09. AlC / CM Z The ratio CM AlC / CM ZIt will be appreciated that CM can be any value between any of the minimum and maximum values listed above. AlC / CM Z It will be further understood that may be within a range between any of the minimum and maximum values listed above.
[0039] In another embodiment, the zircon batch may include an alkaline earth-containing component including compounds such as oxides, nitrates, sulfates, hydrated forms thereof, or any combination thereof, organic materials, or any combination thereof. In a particular embodiment, the alkaline earth-containing component may include oxides including CaO, BaO, SrO, or any combination thereof. In another particular embodiment, the alkaline earth-containing component may be purposefully added in a particular amount that may facilitate the formation of a zircon body having improved properties and / or performance.
[0040] In another embodiment, the zircon batch may include a particular content of the alkaline earth-containing component that may facilitate the formation of a refractory having improved properties and / or performance. For example, the zircon batch may include 14 wt.% or less of the alkaline earth-containing component, e.g., 13 wt.% or less of the alkaline earth-containing component, 12 wt.% or less of the alkaline earth-containing component, 11 wt.% or less of the alkaline earth-containing component, 10 wt.% or less of the alkaline earth-containing component, 9 wt.% or less of the alkaline earth-containing component, 8 wt.% or less of the alkaline earth-containing component, 7 wt.% or less of the alkaline earth-containing component, 6 wt.% or less of the alkaline earth-containing component, 5 wt.% or less of the alkaline earth-containing component, 4.5 wt.% or less of the alkaline earth-containing component, 4.2 wt.% or less of the alkaline earth-containing component, 4 wt.% or less of the alkaline earth-containing component, 3.5 wt.% or less of the alkaline earth-containing component, 3 wt.% or less of the alkaline earth-containing component, 2.5 wt.% or less of the alkaline earth-containing component, or 2 wt.% or less of the alkaline earth-containing component, based on the total weight of the zircon batch. In another example, the zircon batch has at least 0.02 wt. % alkaline earth-containing component, e.g., at least 0.05 wt. % alkaline earth-containing component, at least 0.08 wt. % alkaline earth-containing component, at least 0.1 wt. % alkaline earth-containing component, at least 0.15 wt. % alkaline earth-containing component, at least 0.2 wt. % alkaline earth-containing component, at least 0.3 wt. % alkaline earth-containing component, at least 0.4 wt. % alkaline earth-containing component, at least 0.5 wt. % alkaline earth-containing component, at least 0. The alkaline earth-containing component may comprise 6 wt.% alkaline earth-containing component, at least 0.7 wt.% alkaline earth-containing component, at least 0.8 wt.% alkaline earth-containing component, at least 0.9 wt.% alkaline earth-containing component, at least 1 wt.% alkaline earth-containing component, at least 1.2 wt.% alkaline earth-containing component, at least 1.4 wt.% alkaline earth-containing component, at least 1.5 wt.% alkaline earth-containing component, at least 1.8 wt.% alkaline earth-containing component, at least 2 wt.% alkaline earth-containing component, or even at least 2.3 wt.% alkaline earth-containing component.It will be appreciated that the content of the alkaline earth-containing component in weight percent, based on the total weight of the zircon batch, can be any value between any of the minimum and maximum values set forth above. It will be further appreciated that the content of the alkaline earth-containing component in weight percent, based on the total weight of the zircon batch, can be within a range between any of the minimum and maximum values set forth above.
[0041] According to certain embodiments, the zircon batch may include a particular content of CaO that may facilitate the formation of a refractory having improved properties and / or performance. For example, the zircon batch may include 5 wt.% or less CaO, e.g., 4.5 wt.% or less CaO, 4 wt.% or less CaO, 3.8 wt.% or less CaO, 3.6 wt.% or less CaO, 3.5 wt.% or less CaO, 3.2 wt.% or less CaO, 3 wt.% or less CaO, 2.8 wt.% or less CaO, 2.6 wt.% or less CaO, 2.5 wt.% or less CaO, 2.3 wt.% or less CaO, 2.1 wt.% or less CaO, 2 wt.% or less CaO, 1.8 wt.% or less CaO, 1.6 wt.% or less CaO, 1.4 wt.% or less CaO, 1.2 wt.% or less CaO, or 1 wt.% or less CaO, based on the total weight of the zircon batch. In another example, the zircon batch contains more than 0.07 wt.% CaO, e.g., at least 0.1 wt.% CaO, at least 0.12 wt.%, at least 0.15 wt.%, at least 0.18 wt.%, at least 0.2 wt.% CaO, at least 0.25 wt.%, at least 0.29 wt.%, at least 0.3 wt.% CaO, at least 0.31 wt.% CaO, at least 0.33 wt.%, at least 0.4 wt.% CaO, at least 0.43 wt.%, or less, based on the total weight of the zircon batch. The zircon batch may include at least 0.45 wt%, at least 0.47 wt%, at least 0.5 wt%, at least 0.6 wt%, at least 0.62 wt%, at least 0.7 wt%, at least 0.8 wt%, at least 0.9 wt%, at least 1 wt%, at least 1.2 wt%, at least 1.4 wt%, at least 1.5 wt%, at least 1.8 wt%, or at least 2 wt% CaO. Furthermore, the CaO content in weight percent relative to the total weight of the zircon batch may be any value between any of the minimum and maximum values set forth above. It is further understood that the CaO content in weight percent relative to the total weight of the zircon batch may be within a range between any of the minimum and maximum values set forth above.
[0042] According to another particular embodiment, the zircon batch may include a particular content of MgO that may facilitate the formation of a refractory having improved properties and / or performance. For example, the zircon batch may include 4 wt.% or less MgO, e.g., 3.8 wt.% or less MgO, 3.6 wt.% or less MgO, 3.5 wt.% or less MgO, 3.2 wt.% or less MgO, 3 wt.% or less MgO, 2.8 wt.% or less MgO, 2.6 wt.% or less MgO, 2.5 wt.% or less MgO, 2.3 wt.% or less MgO, 2.1 wt.% or less MgO, 3.8 wt.% or less MgO, 3.6 wt.% or less MgO, 3.5 wt.% or less MgO, 3.2 wt.% or less MgO, 3 ....8 wt.% or less MgO, 3.6 wt.% or less MgO, 3.5 wt.% or less MgO, 3.2 wt.% or less MgO, 3.8 wt.% or less MgO, 3.6 wt.% or less MgO, 3.5 wt.% or less MgO, 3.2 wt.% or less MgO, 3. It may contain up to 2% MgO by weight, up to 1.8% MgO, up to 1.6% MgO, up to 1.4% MgO, up to 1.2% MgO, up to 1.0% MgO, up to 0.8% MgO, up to 0.5% MgO, up to 0.4% MgO, up to 0.3% MgO, up to 0.2% MgO, up to 0.1% MgO, up to 0.05% MgO, or up to 0.01% MgO by weight. In another example, the zircon batch may include at least 0.005% MgO by weight based on the total weight of the zircon batch, for example, at least 0.01% MgO by weight, at least 0.02% MgO by weight, at least 0.03% MgO by weight, at least 0.04% MgO by weight, at least 0.05% MgO by weight, at least 0.06% MgO by weight, at least 0.07% MgO by weight, at least 0.08% MgO by weight, at least 0.09% MgO by weight, or at least 0.1% MgO by weight based on the total weight of the zircon body. In certain embodiments, the zircon batch may be essentially free of MgO. Furthermore, the content of MgO in weight percent based on the total weight of the zircon batch may be any value between any of the minimum and maximum values set forth above. It will be further understood that the content of MgO in weight percent based on the total weight of the zircon batch may be within a range between any of the minimum and maximum values set forth above.
[0043] According to certain embodiments, the zircon batch may include a particular content of SrO that may facilitate the formation of a refractory having improved properties and / or performance. For example, the zircon batch may include 5 wt.% or less SrO, e.g., 4.5 wt.% or less SrO, 4 wt.% or less SrO, 3.8 wt.% or less SrO, 3.6 wt.% or less SrO, 3.5 wt.% or less SrO, 3.2 wt.% or less SrO, 3 wt.% or less SrO, 2.8 wt.% or less SrO, 2.6 wt.% or less SrO, 2.5 wt.% or less SrO, 2.3 wt.% or less SrO, 2.1 wt.% or less SrO, 2 wt.% or less SrO, 1.8 wt.% or less SrO, 1.6 wt.% or less SrO, 1.4 wt.% or less SrO, 1.2 wt.% or less SrO, or 1 wt.% or less SrO, based on the total weight of the zircon batch. In another example, the zircon batch has more than 0.04 wt.% SrO, e.g., at least 0.05 wt.%, at least 0.07 wt.%, at least 0.1 wt.%, at least 0.12 wt.%, at least 0.15 wt.% SrO, at least 0.18 wt.%, at least 0.2 wt.% SrO, at least 0.24 wt.% SrO, at least 0.28 wt.% SrO, at least 0.3 wt.% SrO, at least 0.4 wt.% SrO, based on the total weight of the zircon batch. % SrO, at least 0.42 wt. % SrO, at least 0.47 wt. % SrO, at least 0.5 wt. % SrO, at least 0.6 wt. % SrO, at least 0.7 wt. % SrO, at least 0.8 wt. % SrO, at least 0.9 wt. % SrO, at least 1 wt. % SrO, at least 1.2 wt. % SrO, at least 1.4 wt. % SrO, at least 1.5 wt. % SrO, at least 1.8 wt. % SrO, or at least 2 wt. % SrO. Furthermore, the content of SrO in weight percent relative to the total weight of the zircon batch can be any value between any of the minimum and maximum values set forth above. It is further understood that the content of SrO in weight percent relative to the total weight of the zircon batch can be within a range between any of the minimum and maximum values set forth above.
[0044] According to certain embodiments, the zircon batch may include a particular content of BaO that may facilitate the formation of a refractory having improved properties and / or performance. For example, the zircon batch may include 6.5 wt.% or less BaO, e.g., 6 wt.% or less, 5 wt.% or less, 4.5 wt.% or less BaO, 4 wt.% or less BaO, 3.8 wt.% or less BaO, 3.6 wt.% or less BaO, 3.5 wt.% or less BaO, 3.2 wt.% or less BaO, 3 wt.% or less BaO, 2.8 wt.% or less BaO, 2.6 wt.% or less BaO, 2.5 wt.% or less BaO, 2.3 wt.% or less BaO, 2.1 wt.% or less BaO, 2 wt.% or less BaO, 1.8 wt.% or less BaO, 1.6 wt.% or less BaO, 1.4 wt.% or less BaO, 1.2 wt.% or less BaO, or 1 wt.% or less BaO, based on the total weight of the zircon batch. In another example, the zircon batch has more than 0.09 wt.% BaO, e.g., at least 0.15 wt.% BaO, at least 0.2 wt.% BaO, at least 0.21 wt.% BaO, at least 0.3 wt.% BaO, at least 0.35 wt.% BaO, at least 0.4 wt.% BaO, at least 0.5 wt.% BaO, at least 5.3 wt.% BaO, at least 0.6 wt.% BaO, at least 0.63 wt.% BaO, at least 0.7 wt.% BaO, or less, based on the total weight of the zircon batch. The zircon batch may include at least 0.72 wt% BaO, at least 0.78 wt% BaO, at least 0.8 wt% BaO, at least 0.9 wt% BaO, at least 1 wt% BaO, at least 1.2 wt% BaO, at least 1.4 wt% BaO, at least 1.5 wt% BaO, at least 1.53 wt% BaO, at least 1.6 wt% BaO, at least 1.7 wt% BaO, at least 1.8 wt% BaO, at least 1.9 wt% BaO, or at least 2 wt% BaO. Furthermore, the content of BaO in weight percent relative to the total weight of the zircon batch may be any value between any of the minimum and maximum values set forth above. It is further understood that the content of BaO in weight percent relative to the total weight of the zircon batch may be within a range between any of the minimum and maximum values set forth above.
[0045] According to yet another particular embodiment, the zircon batch may include a sintering aid, such as Ta2O5 or TiO2. According to yet another particular embodiment, the zircon batch may include a particular content of sintering aid. For example, the zircon batch may include 5.0 wt% or less of sintering aid, such as 4.5 wt% or less of sintering aid, 4.0 wt% or less of sintering aid, 3.5 wt% or less of sintering aid, 3.0 wt% or less of sintering aid, 2.5 wt% or less of sintering aid, 2.0 wt% or less of sintering aid, 1.5 wt% or less of sintering aid, 1.0 wt% or less of sintering aid, 0.5 wt% or less of sintering aid, 0.1 wt% or less of sintering aid, or the zircon batch may even be essentially free of sintering aid, based on the total weight of the zircon batch. According to yet another particular embodiment, the zircon batch may include at least 0.1 wt. % sintering aid, at least 0.2 wt. % sintering aid, at least 0.3 wt. % sintering aid, at least 0.4 wt. % sintering aid, at least 0.5 wt. % sintering aid, at least 0.6 wt. % sintering aid, at least 0.7 wt. % sintering aid, at least 0.8 wt. % sintering aid, or even at least 0.9 wt. % sintering aid, based on the total weight of the zircon batch. It will be understood that the content of the sintering aid in wt. % based on the total weight of the zircon batch may be any value between any of the minimum and maximum values listed above. It will be further understood that the content of the sintering aid in wt. % based on the total weight of the zircon batch may be within a range between any of the minimum and maximum values listed above.
[0046] According to yet another embodiment, the zircon batch is formed of a mixture of zircon and zirconium in a specific ratio C SA / CM SiO2 CM SA represents the content of sintering aid in wt% relative to the total weight of the zircon batch, and C SiO2 represents the content of the SiO2 component in weight percent relative to the total weight of the zircon batch. According to certain embodiments, the zircon batch has a ratio C M of 0.5 or less, for example, 0.1 or less, 0.05 or less, 0.04 or less, 0.03 or less, or even 0.02 or less. SA / CM SiO2According to another particular embodiment, the zircon batch may have a ratio CM of at least 0.001, e.g., at least 0.005, at least 0.01, at least 0.02, or even at least 0.03. SA / CM SiO2 It may include the following: SA / CM SiO2 It will be appreciated that CM can be any value between any of the minimum and maximum values listed above. SA / CM SiO2 It will be further understood that may be within a range between any of the minimum and maximum values listed above.
[0047] According to yet another embodiment, the zircon batch may include a specific content of Ta2O5. For example, the zircon batch may include at least 0.1 wt% Ta2O5, at least 0.2 wt% Ta2O5, at least 0.3 wt% Ta2O5, at least 0.4 wt% Ta2O5, at least 0.5 wt% Ta2O5, at least 0.6 wt% Ta2O5, at least 0.7 wt% Ta2O5, at least 0.8 wt% Ta2O5, or even at least 0.9 wt% Ta2O5, based on the total weight of the zircon batch. According to yet another embodiment, the zircon batch may include 3.0 wt% or less Ta2O5, for example, 2.5 wt% or less Ta2O5, 2.0 wt% or less Ta2O5, 1.5 wt% or less Ta2O5, 1.0 wt% or less Ta2O5, 0.5 wt% or less Ta2O5, 0.1 wt% or less Ta2O5, or the zircon batch may even be essentially free of Ta2O5, based on the total weight of the zircon batch. It will be understood that the content of Ta2O5 in wt% based on the total weight of the zircon batch may be any value between any of the minimum and maximum values listed above. It will be further understood that the content of Ta2O5 in wt% based on the total weight of the zircon batch may be within a range between any of the minimum and maximum values listed above.
[0048] According to yet another embodiment, the zircon batch is formed of a mixture of zircon and zirconium in a specific ratio C Ta2O5 / CM SiO2 CMTa2O5 represents the content of Ta2O5 in wt% relative to the total weight of the zircon batch, and C SiO2 represents the content of the SiO2 component in weight percent relative to the total weight of the zircon batch. According to certain embodiments, the zircon batch has a ratio C M of 0.5 or less, for example, 0.1 or less, 0.05 or less, 0.04 or less, 0.03 or less, or even 0.02 or less. Ta2O5 / CM SiO2 According to another particular embodiment, the zircon batch may have a ratio CM of at least 0.001, e.g., at least 0.005, at least 0.01, at least 0.02, or even at least 0.03. Ta2O5 / CM SiO2 It may include the following: Ta2O5 / CM SiO2 It will be appreciated that CM can be any value between any of the minimum and maximum values listed above. Ta2O5 / CM SiO2 It will be further understood that may be within a range between any of the minimum and maximum values listed above.
[0049] According to yet another embodiment, the zircon batch may include a specific content of TiO2. For example, the zircon batch may include 5.0 wt% or less TiO2, such as 4.5 wt% or less TiO2, 4.0 wt% or less TiO2, 3.5 wt% or less TiO2, 3.0 wt% or less TiO2, 2.5 wt% or less TiO2, 2.0 wt% or less TiO2, 1.5 wt% or less TiO2, 1.0 wt% or less TiO2, 0.5 wt% or less TiO2, 0.1 wt% or less TiO2, or the zircon batch may even be essentially free of TiO2, based on the total weight of the zircon batch. According to yet another particular embodiment, the zircon batch may include at least 0.1 wt% TiO2, at least 0.2 wt% TiO2, at least 0.3 wt% TiO2, at least 0.4 wt% TiO2, at least 0.5 wt% TiO2, at least 0.6 wt% TiO2, at least 0.7 wt% TiO2, at least 0.8 wt% TiO2, or even at least 0.9 wt% TiO2, based on the total weight of the zircon batch. It will be understood that the content of TiO2 in wt% based on the total weight of the zircon batch may be any value between any of the minimum and maximum values listed above. It will be further understood that the content of TiO2 in wt% based on the total weight of the zircon batch may be within a range between any of the minimum and maximum values listed above.
[0050] According to yet another embodiment, the zircon batch is formed of a mixture of zircon and zirconium in a specific ratio C TiO2 / CM SiO2 CM TiO2 represents the content of TiO2 in wt% relative to the total weight of the zircon batch, and C SiO2 represents the content of the SiO2 component in weight percent relative to the total weight of the zircon batch. According to certain embodiments, the zircon batch has a ratio C M of 0.5 or less, for example, 0.1 or less, 0.05 or less, 0.04 or less, 0.03 or less, or even 0.02 or less. TiO2 / CM SiO2According to another particular embodiment, the zircon batch may have a ratio CM of at least 0.001, e.g., at least 0.005, at least 0.01, at least 0.02, or even at least 0.03. TiO2 / CM SiO2 It may include the following: TiO2 / CM SiO2 It will be appreciated that CM can be any value between any of the minimum and maximum values listed above. TiO2 / CM SiO2 It will be further understood that may be within a range between any of the minimum and maximum values listed above.
[0051] According to yet another embodiment, the zircon batch may include a specific content of combined Ta2O5 and TiO2. For example, the zircon batch may include 5.0 wt% or less of combined Ta2O5 and TiO2, such as 4.0 wt% or less of combined Ta2O5 and TiO2, 3.0 wt% or less of combined Ta2O5 and TiO2, 2.0 wt% or less of combined Ta2O5 and TiO2, 1.0 wt% or less of combined Ta2O5 and TiO2, 0.5 wt% or less of combined Ta2O5 and TiO2, 0.1 wt% or less of combined Ta2O5 and TiO2, or the zircon batch may even be essentially free of combined Ta2O5 and TiO2, based on the total weight of the zircon batch. According to yet another embodiment, the zircon batch may include at least 0.1 weight percent of the combined Ta2O5 and TiO2, e.g., at least 0.2 weight percent of the combined Ta2O5 and TiO2, at least 0.3 weight percent of the combined Ta2O5 and TiO2, at least 0.4 weight percent of the combined Ta2O5 and TiO2, at least 0.5 weight percent of the combined Ta2O5 and TiO2, at least 0.6 weight percent of the combined Ta2O5 and TiO2, at least 0.7 weight percent of the combined Ta2O5 and TiO2, at least 0.8 weight percent of the combined Ta2O5 and TiO2, or even at least 0.9 weight percent of the combined Ta2O5 and TiO2, based on the total weight of the zircon batch. It will be appreciated that the combined Ta2O5 and TiO2 content in weight percent relative to the total weight of the zircon batch can be any value between any of the minimum and maximum values set forth above. It will be further appreciated that the combined Ta2O5 and TiO2 content in weight percent relative to the total weight of the zircon batch can be within a range between any of the minimum and maximum values set forth above.
[0052] According to yet another embodiment, the zircon batch may include a particular content of KO. For example, the zircon batch may include 1.0 wt.% or less KO, e.g., 0.8 wt.% or less KO, 0.5 wt.% or less KO, 0.4 wt.% or less KO, 0.3 wt.% or less KO, 0.2 wt.% or less KO, 0.1 wt.% or less KO, based on the total weight of the zircon batch, or the zircon batch may be essentially free of KO.
[0053] According to yet another embodiment, the zircon batch may include a particular content of Na2O. For example, the zircon batch may include 1.0 wt% or less Na2O, e.g., 0.8 wt% or less Na2O, 0.5 wt% or less Na2O, 0.4 wt% or less Na2O, 0.3 wt% or less Na2O, 0.2 wt% or less Na2O, 0.1 wt% or less Na2O, or the zircon batch may be essentially free of Na2O, based on the total weight of the zircon batch.
[0054] According to yet another embodiment, the zircon batch may include a particular content of Y2O3. For example, the zircon batch may include 1.0 wt% or less Y2O3, e.g., 0.8 wt% or less Y2O3, 0.5 wt% or less Y2O3, 0.4 wt% or less Y2O3, 0.3 wt% or less Y2O3, 0.2 wt% or less Y2O3, 0.1 wt% or less Y2O3, or the zircon batch may be essentially free of Y2O3, based on the total weight of the zircon batch.
[0055] According to yet another embodiment, the zircon batch may include a specific content of P2O5. For example, the zircon batch may include 1.0 wt% or less P2O5, e.g., 0.8 wt% or less P2O5, 0.5 wt% or less P2O5, 0.4 wt% or less P2O5, 0.3 wt% or less P2O5, 0.2 wt% or less P2O5, 0.1 wt% or less P2O5, or the zircon batch may be essentially free of P2O5, based on the total weight of the zircon batch.
[0056] According to yet another embodiment, the zircon batch may include a specific content of Fe2O3. For example, the zircon batch may include 1.0 wt% or less Fe2O3, e.g., 0.8 wt% or less Fe2O3, 0.5 wt% or less Fe2O3, 0.4 wt% or less Fe2O3, 0.3 wt% or less Fe2O3, 0.2 wt% or less Fe2O3, 0.1 wt% or less Fe2O3, or the zircon batch may be essentially free of Fe2O3, based on the total weight of the zircon batch.
[0057] According to yet another embodiment, the zircon batch may include a particular content of ZnO, for example, the zircon batch may include 1.0 wt.% or less ZnO, e.g., 0.8 wt.% or less ZnO, 0.5 wt.% or less ZnO, 0.4 wt.% or less ZnO, 0.3 wt.% or less ZnO, 0.2 wt.% or less ZnO, 0.1 wt.% or less ZnO, or the zircon batch may be essentially free of ZnO, based on the total weight of the zircon batch.
[0058] According to yet another embodiment, the zircon batch may include a specific content of combined TiO2, K2O, Na2O, Y2O3, P2O5, Fe2O3, and ZnO. For example, the zircon batch may include 1.5 wt. % or less of combined TiO2, K2O, Na2O, Y2O3, P2O5, Fe2O3, and ZnO, for example, 1.2 wt. % or less of combined TiO2, K2O, Na2O, Y2O3, P2O5, Fe2O3, and ZnO, 1.0 wt. % or less of combined TiO2, K2O, Na2O, Y2O3, P2O5, Fe2O3, and ZnO, 0.7 wt. % or less of combined TiO2, K2O, Na2O, Y2O3, P2O5, Fe2O3, and ZnO, 0.5 wt. % or less of combined TiO2, K2O, Na2O, Y2O3, P2O5, Fe2O3, and ZnO, 0.2 wt. % or less of combined TiO2, K2O, Na2O, Y2O3, P2O5, Fe2O3, and ZnO, 0.1 wt. % or less of combined TiO2, K2O, Na2O, Y2O3, P2O5, Fe2O3, and ZnO, or the zircon batch may be essentially free of combined TiO2, K2O, Na2O, Y2O3, P2O5, Fe2O3, and ZnO.
[0059] In other embodiments, the zircon batch may have a minimum content of certain metal oxides, such as, for example, rare earth oxides, alkali oxides, and any transition metal oxides not expressly disclosed herein. The rare earth oxides may include any oxide composition including rare earth metals from the lanthanide series (i.e., elements having atomic numbers between 57 and 71), such as lanthanum oxide, cerium oxide, and europium oxide. The alkali oxides may include any oxide composition including Group 1 metals (i.e., lithium, sodium, potassium, rubidium, cesium, and francium), such as lithium oxide, potassium oxide, and cesium oxide. The zircon batch having a minimum content of any of the above oxides, such as, for example, rare earth oxides, alkali oxides, and any transition metal oxides not expressly disclosed herein, may have a content of that oxide of 1 wt. % or less, such as, for example, 0.7 wt. % or less, 0.5 wt. % or less, or even 0.2 wt. % or less of the total weight of the zircon batch.
[0060] In one embodiment, forming the sintered zircon body may include forming specific crystalline phases within the zircon body. In another embodiment, forming the sintered zircon body may include forming specific contents of crystalline phases, specific content ratios of crystalline phases, or any combination thereof. Controlling the formation and / or content and / or ratio of specific crystalline phases may facilitate the formation of refractories having improved performance and / or properties.
[0061] In one embodiment, the zircon body may include a first crystalline phase that includes an alkaline earth element. In a particular aspect, the alkaline earth element may include at least one of Ca, Mg, Sr, and Ba. More specifically, the alkaline earth metal element may include Ca, Sr, Ba, or any combination thereof. In a further aspect, the first crystalline phase may be an alkaline earth-Al-Si rich crystalline phase. In another particular aspect, the first crystalline phase may include an alkaline earth oxide-containing component, including, for example, CaO, MgO, SrO, BaO, or any combination thereof. In another embodiment, the first crystalline phase may further include Al, Si, or a combination thereof. Al and / or Si may be present in an alumina-containing component, such as an aluminosilicate species. A particular example may include an alkaline earth-containing aluminosilicate. In further embodiments, the zircon body may include a first crystalline phase comprising calcium aluminosilicate, barium aluminosilicate, magnesium aluminosilicate, strontium aluminosilicate, or a combination thereof. In certain aspects, the first crystalline phase may include calcium aluminosilicate, barium aluminosilicate, strontium aluminosilicate, or a combination thereof. More specifically, in embodiments, the first crystalline phase may consist essentially of one or more of calcium aluminosilicate, barium aluminosilicate, magnesium aluminosilicate, and strontium aluminosilicate. Even more specifically, the first crystalline phase may consist essentially of one or more of calcium aluminosilicate, barium aluminosilicate, and strontium aluminosilicate. In certain instances, the first crystalline phase may consist essentially of calcium aluminosilicate.
[0062] In one embodiment, the zircon body can include a first crystalline phase that includes feldspar-type crystals. In a particular aspect, the first crystalline phase can consist essentially of feldspar-type crystals. In another particular aspect, the feldspar-type crystals can be selected from the group consisting of gehlenite (CaAlSiO), prehnite (CaAl[AlSiO], and CaAl(AlSiO). 10)(OH)2), anorthite (CaAl2Si2O8), celsian (BaAl2Si2O8), or any combination thereof. In a more particular embodiment, the first crystalline phase may include gehlenite (Ca2Al2SiO7), prehnite (Ca2Al[AlSiO7] and Ca2Al(AlSiO 10 )(OH)2), anorthite (CaAl2Si2O8), and celsian (BaAl2Si2O8).
[0063] In one embodiment, the zircon body may include a specific content of the first crystalline phase that may facilitate the formation of a refractory having improved properties and / or performance. In one aspect, the zircon body may include at least 0.01 wt.%, based on the total weight of the zircon body, at least 0.05 wt.%, at least 0.1 wt.%, at least 0.2 wt.%, at least 0.3 wt.%, at least 0.4 wt.%, at least 0.5 wt.%, at least 0.6 wt.%, at least 0.7 wt.%, at least 0.8 wt.%, at least 0.9 wt.%, at least 1 wt.%, at least 2 wt.%, or at least 3 wt.%, at least 4 wt.%, at least 5 wt.%, or at least 6 wt.% of the first crystalline phase including an alkaline earth metal based on the total weight of the zircon body. In another embodiment, the zircon body may include a first crystalline phase comprising 20% or less by weight, 18% or less by weight, 16% or less by weight, 14% or less by weight, 12% or less by weight, 10% or less by weight, 8% or less by weight, 6% or less by weight, 5% or less by weight, 4% or less by weight, 3% or less by weight, 2% or less by weight, or 1% or less by weight of an alkaline earth metal, based on the total weight of the zircon body. Furthermore, the zircon body may include the first crystalline phase in a content that may be any value within a range including any of the minimum and maximum percentages described herein. It will be further understood that the content of the first crystalline phase may be within a range including any of the minimum and maximum percentages described herein. The content of the crystalline phase may be determined by X-ray diffraction analysis.
[0064] In one embodiment, the zircon body may include a second crystalline phase comprising tantalum, iron, titanium, or any combination thereof. In one aspect, the second crystalline phase may be a tantalum-iron-titania rich crystalline phase. In another aspect, the second crystalline phase may include tapiolite type crystals. In another embodiment, the zircon body may include a specific content of the second crystalline phase to facilitate the formation of a refractory having improved properties and / or performance. In one embodiment, the zircon body can comprise at least 0.01% by weight, based on the total weight of the zircon body, at least 0.05% by weight, at least 0.1% by weight, at least 0.2% by weight, at least 0.3% by weight, at least 0.4% by weight, at least 0.5% by weight, at least 0.6% by weight, at least 0.7% by weight, at least 0.8% by weight, at least 0.9% by weight, at least 1% by weight, at least 1.5% by weight, at least 2% by weight, at least 2.5% by weight, at least 3% by weight, at least 3.5% by weight, at least 4% by weight, at least 4.5% by weight, or at least 5% by weight of a second crystalline phase. In another embodiment, the zircon body may include 20% or less by weight of the second crystalline phase, based on the total weight of the zircon body, 18% or less by weight, 16% or less by weight, 14% or less by weight, 12% or less by weight, 10% or less by weight, 8% or less by weight, 6% or less by weight, 5% or less by weight, 4% or less by weight, 3% or less by weight, or 2% or less by weight, based on the total weight of the zircon body. Furthermore, the zircon body may include the second crystalline phase in a content that may be any value within a range that includes any of the minimum and maximum percentages described herein. It will be further understood that the content of the second crystalline phase may be within a range that includes any of the minimum and maximum percentages described herein.
[0065] In one embodiment, the zircon body may include an amorphous phase. The amorphous phase may be referred to as a glass phase in this disclosure. In one aspect, the amorphous phase may include Si, Al, Ta, an alkaline earth metal element, or any combination thereof. In another aspect, the amorphous phase may include a specific content for the element present in the amorphous phase. For example, the zircon body may include an amorphous phase including Si in the range of 40 wt% to 60 wt%, or in the range of 48 wt% to 58 wt%, based on the total weight of the amorphous phase. The amorphous phase may also include Al in a content in the range of 10 wt% to 30 wt%, or in the range of 15 wt% to 25 wt%, based on the total weight of the amorphous phase. In certain cases, the amorphous phase may include an alkaline earth metal element in a content in the range of 0.5 wt% to 15 wt%, or in the range of 2 wt% to 9 wt%, based on the total weight of the amorphous phase. The alkaline earth elements may include Ca, Ba, Mg, Sr, or any combination thereof. The amorphous phase may further include Ta in a content in the range of 0.3 wt.% to 12 wt.%, or in the range of 1 wt.% to 7 wt.%, based on the total weight of the amorphous phase. In certain examples, the amorphous phase may include alumina, silica, titania, alkaline earth oxides, or any combination thereof. In further embodiments, the amorphous phase may be substantially uniformly distributed in the zircon body. In further aspects, the amorphous phase may include impurities derived from the raw materials, including, for example, P, Na, K, Fe, the like, or any combination thereof.
[0066] In further embodiments, the zircon body may include a particular content of amorphous phase that may facilitate the formation of a refractory having improved properties and / or performance. For example, the zircon body may include at least 0.5 wt.%, e.g., at least 0.8 wt.%, at least 1 wt.%, at least 1.5 wt.%, at least 1.8 wt.%, at least 2 wt.%, at least 2.5 wt.%, at least 3 wt.%, at least 4 wt.%, or at least 5 wt.% of amorphous phase based on the total weight of the zircon body. In another example, the zircon body may include 20 wt.% or less of amorphous phase based on the total weight of the zircon body, e.g., 18 wt.% or less, 16 wt.% or less, 14 wt.% or less, 12 wt.% or less, 10 wt.% or less, 8 wt.% or less, 6 wt.% or less, 5 wt.% or less, 4 wt.% or less, 3 wt.% or less, or 2 wt.% or less of amorphous phase based on the total weight of the zircon body. Additionally, the zircon body may include an amorphous phase in a content that may be any value within a range including any of the minimum and maximum percentages described herein. It will be further understood that the content of the amorphous phase may be within a range including any of the minimum and maximum percentages described herein. The content of the amorphous phase may be determined by the formula C. G =C AEB / C AEG It can be determined using C G represents the content of amorphous phase relative to the total weight of the zircon body. AEG represents the total content of alkaline earth oxides in the amorphous phase identified by microprobe analysis, and C AEB represents the total alkaline earth oxide content in the zircon body as determined by bulk ICP analysis performed on the crushed zircon body.
[0067] In one embodiment, the first crystalline phase, the second crystalline phase, or both, can be contained within an amorphous phase.
[0068] In one embodiment, the zircon body may include a third crystalline phase including Al and Si. In further embodiments, the third crystalline phase may include aluminum silicate species. For example, the zircon body may include a third crystalline phase including mullite (3Al2O3·2SiO2, 2Al2O3·SiO2, or both), sillimanite (Al2O(SiO4)), andalusite (Al2SiO5), or any combination thereof. In a particular example, mullite may be the major component of the third crystalline phase. In another particular example, the third crystalline phase may include mullite, sillimanite, and andalusite. In yet another particular example, the third crystalline phase consists essentially of mullite. In another embodiment, the zircon body may include a particular content of the third crystalline phase that may facilitate the formation of a refractory having improved properties and / or performance. For example, the zircon body can include at least 0.01 weight percent of a third crystalline phase, based on the total weight of the zircon body, e.g., at least 0.05 weight percent, at least 0.1 weight percent, at least 0.2 weight percent, at least 0.3 weight percent, at least 0.4 weight percent, at least 0.5 weight percent, at least 0.6 weight percent, at least 0.7 weight percent, at least 0.8 weight percent, at least 0.9 weight percent, at least 1 weight percent, at least 1.5 weight percent, at least 2 weight percent, at least 2.5 weight percent, at least 3 weight percent, at least 3.5 weight percent, at least 3.7 weight percent, at least 4 weight percent, at least 4.5 weight percent, or at least 5 weight percent of a third crystalline phase, based on the total weight of the zircon body. In another example, the zircon body may include a third crystalline phase of 20% or less by weight, for example, 18% or less by weight, 16% or less by weight, 14% or less by weight, 12% or less by weight, 10% or less by weight, 8% or less by weight, 7.5% or less by weight, 7.2% or less by weight, 6% or less by weight, 5% or less by weight, or 4% or less by weight, based on the total weight of the zircon body. Furthermore, the zircon body may include a third crystalline phase in a content that may be any value within a range including any of the minimum and maximum percentages described herein. It is further understood that the content of the third crystalline phase may be within a range including any of the minimum and maximum percentages described herein. The third crystalline phase may be referred to as a mullite crystalline phase in this disclosure.
[0069] In one embodiment, the zircon body may include a fourth crystalline phase comprising zircon. The fourth crystalline phase may be referred to as a zircon crystalline phase in this disclosure. In certain cases, the fourth crystalline phase may consist essentially of zircon. In another embodiment, the zircon body may include a certain content of the fourth crystalline phase that may facilitate the formation of a refractory having improved properties and / or performance. For example, the zircon body may include at least 50% by weight, e.g., at least 60% by weight, at least 70% by weight, at least 75% by weight, at least 80% by weight, at least 85% by weight, at least 87.5% by weight, at least 90% by weight, or at least 93% by weight, based on the total weight of the zircon body. In other cases, the zircon body may include 99.5% or less by weight of the fourth crystalline phase, based on the total weight of the zircon body, 99% or less by weight, 98% or less by weight, 97% or less by weight, 96% or less by weight, 95% or less by weight, or 94% or less by weight, based on the total weight of the zircon body. Additionally, the zircon body may include the fourth crystalline phase in a content that may be any value within a range including any of the minimum and maximum percentages described herein. It will be further understood that the content of the fourth crystalline phase may be within a range including any of the minimum and maximum percentages described above.
[0070] In further embodiments, the zircon body may include a fifth crystalline phase comprising zirconia. In certain embodiments, the fifth crystalline phase may consist essentially of zirconia. In other embodiments, the zircon body may include a certain content of the fourth crystalline phase that may facilitate the formation of a refractory having improved properties and / or performance. For example, the zircon body may include at least 0.01 wt. % of the fifth crystalline phase relative to the total weight of the zircon body, at least 0.03 wt. %, at least 0.05 wt. %, at least 0.1 wt. %, at least 0.2 wt. %, at least 0.3 wt. %, at least 0.4 wt. %, at least 0.5 wt. %, at least 0.6 wt. %, at least 0.7 wt. %, at least 0.8 wt. %, at least 0.9 wt. %, at least 1 wt. %, at least 1.3 wt. %, at least 1.5 wt. %, or at least 1.7 wt. % of the fifth crystalline phase relative to the total weight of the zircon body. In another example, the zircon body may include 15% or less by weight of the fifth crystalline phase, for example, 12% or less, 10% or less, 9% or less, 8.7% or less, 8.5% or less, 8.3% or less, 8% or less, 7% or less, 6% or less, 5% or less, 4% or less, 3% or less, or 2% or less by weight of the fifth crystalline phase, based on the total weight of the zircon body. Furthermore, the zircon body may include the fifth crystalline phase in a content that may be any value within a range including any of the minimum and maximum percentages described herein. It will be further understood that the content of the fifth crystalline phase may be within a range including any of the minimum and maximum percentages described above. In one embodiment, most or essentially all of the zirconia may be present in the crystalline phase, i.e., the fifth crystalline phase. The fifth crystalline phase may be referred to as a zirconia crystalline phase in the present disclosure.
[0071] In another embodiment, the zircon body formed according to the embodiments described herein may include a particular content of zirconia, for example, the zircon body may include a content of at least 0.01 wt.%, at least 0.02 wt.%, at least 0.04 wt.%, at least 0.06 wt.%, at least 0.08 wt.%, at least 0.1 wt.%, at least 0.2 wt.%, at least 0.3 wt.%, at least 0.4 wt.%, at least 0.5 wt.%, at least 0.6 wt.%, at least 0.7 wt.%, at least 0.8 wt.%, at least 0.9 wt.%, or at least 1 wt.% zirconia, based on the total weight of the zircon body. In another example, the zircon body may include 15% or less by weight of zirconia, for example, 12% or less, 10% or less, 9% or less, 8% or less, 7% or less, 6% or less, 5% or less, 4% or less, 3% or less, or 2% or less by weight of zirconia, based on the total weight of the zircon body. Furthermore, the zircon body may include zirconia in a content that may be any value within a range including any of the minimum and maximum percentages described herein. It will be further understood that the zirconia content may be within a range including any of the minimum and maximum percentages described above.
[0072] 4 and 5, which include images of the microstructure of a zircon body of a refractory formed according to embodiments described herein. When analyzed using electron backscatter diffraction, the zircon body can be shown to include a zircon crystalline phase 401, a Ta-Fe-Ti rich crystalline phase 403, a glassy phase 405, a Ca-Al-Si rich crystalline phase 407 contained within the glassy phase 405, a zirconia crystalline phase 409, and a mullite crystalline phase 411. When further analyzed using electron backscatter diffraction, the Ca-Al-Si rich phase 407 is found to be gehlenite (Ca2Al2SiO7) or its hydrated form, prehnite (Ca2Al2Si3O4). 12 H2) is included.
[0073] In one embodiment, the zircon body may include specific ratios of crystalline phase contents that may facilitate the formation of refractory materials having improved properties and / or performance.
[0074] In one embodiment, the zircon body has a specific ratio of C C2 / C C1 C C2 is the content of the second crystalline phase in weight percent relative to the total weight of the zircon body, and C C1 is the content of the first crystalline phase in weight percent relative to the total weight of the zircon body. For example, C C2 / C C1 The ratio of C may be at least 0.01, at least 0.1, at least 0.5, at least 1, at least 2, at least 3, at least 4, or at least 5. C2 / C C1 The ratio of C may be 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 40 or less, 30 or less, 20 or less, 10 or less, 9 or less, 8 or less, 7 or less, 6 or less, or 5 or less. C3 / C C1 The ratio of C may be within a range including any of the minimum and maximum values described herein. C3 / C C1 It will be further understood that the ratio can be any value within a range including any of the minimum and maximum values stated herein.
[0075] In one embodiment, the zircon body has a specific ratio of C C3 / C C1 C C3 is the content of the third crystalline phase in weight percent relative to the total weight of the zircon body, and C C1 is the content of the first crystalline phase in weight percent relative to the total weight of the zircon body. For example, C C3 / C C1is at least 0.01, at least 0.05, at least 0.1, at least 0.5, at least 1, at least 1.5, at least 2, at least 2.5, at least 3, at least 3.5, at least 4, at least 4.5, at least 5, at least 5, at least 5.5, at least 6, at least 6.5, at least 7, at least 7.5, at least 8, at least 8.5, at least 9, at least 9.5, or at least 10. C3 / C C1 The ratio of C may be 200 or less, 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 48 or less, 45 or less, 42 or less, 40 or less, 38 or less, 35 or less, 32 or less, 30 or less, 28 or less, 25 or less, 22 or less, 20 or less, 18 or less, 15 or less, 12 or less, or 10 or less. C3 / C C1 The ratio of C may be within a range including any of the minimum and maximum values described herein. C3 / C C1 It will be further understood that the ratio can be any value within a range including any of the minimum and maximum values stated herein.
[0076] In one embodiment, the zircon body has a specific ratio of C A / C C1 C A is the content of amorphous phase in weight percent relative to the total weight of the zircon body, and C C1 is the content of the first crystalline phase in weight percent relative to the total weight of the zircon body. A / C C1can be at least 1, at least 1.5, at least 2, at least 2.5, at least 3, at least 3.5, at least 4, at least 4.5, at least 5, at least 5, at least 5.5, at least 6, at least 6.5, at least 7, at least 7.5, at least 8, at least 8.5, at least 9, at least 9.5, at least 10, at least 11, at least 12, at least 13, at least 14, at least 15, at least 16, at least 17, at least 18, at least 19, at least 20, at least 22, at least 24, at least 26, at least 28, at least 30, at least 32, at least 35, at least 38, at least 40, at least 50, at least 60, or at least 70. A / C C1 The ratio of C may be 500 or less, 400 or less, 300 or less, 200 or less, 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 48 or less, 45 or less, 42 or less, 40 or less, 38 or less, 35 or less, 32 or less, or 30 or less. A / C C1 The ratio of C may be within a range including any of the minimum and maximum values described herein. A / C C1 It will be further understood that the ratio can be any value within a range including any of the minimum and maximum values stated herein.
[0077] In one embodiment, the zircon body has a specific ratio of C C4 / C C1 C C4 is the content of the fourth crystalline phase in weight percent relative to the total weight of the zircon body, and C C1 is the content of the first crystalline phase in weight percent relative to the total weight of the zircon body. C4 / C C1can be at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 40, at least 45, at least 50, at least 55, at least 60, at least 65, at least 70, at least 75, at least 80, at least 85, or at least 90. C4 / C C1 The ratio of C4 / C may be 9300 or less, 7000 or less, 5000 or less, 3000 or less, 1000 or less, 800 or less, 600 or less, 500 or less, 400 or less, 300 or less, 200 or less, 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 40 or less, 30 or less, 20 or less, or 10 or less. C1 The ratio of C4 / C can be within a range including any of the minimum and maximum values described herein. C1 It will be further understood that the ratio can be any value within a range including any of the minimum and maximum values stated herein.
[0078] In one embodiment, the zircon body has a specific ratio of C C5 / C C1 C C5 is the content of the fifth crystal phase in weight percent relative to the total weight of the zircon body, and C C1 is the content of the first crystalline phase in weight percent relative to the total weight of the zircon body. C5 / C C1 The ratio of C may be at least 0.01, at least 0.1, at least 0.5, at least 1, at least 2, at least 3, at least 4, or at least 5. C5 / C C1 The ratio of C5 / C may be 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 40 or less, 30 or less, 20 or less, 10 or less, 9 or less, 8 or less, 7 or less, 6 or less, 5 or less, 4 or less, or 3 or less. C1 The ratio of C5 / C can be within a range including any of the minimum and maximum values described herein. C1It will be further understood that the ratio can be any value within a range including any of the minimum and maximum values stated herein.
[0079] In another embodiment, the zircon body formed according to the embodiments described herein can include a particular content of zircon, for example, the zircon body can include at least 50 wt%, e.g., at least 52 wt%, at least 53 wt%, at least 54 wt%, at least 55 wt%, at least 56 wt%, at least 57 wt%, at least 57.5 wt%, at least 58 wt%, at least 58.5 wt%, at least 59 wt%, at least 59.5 wt%, at least 60 wt%, at least 60.5 wt%, at least 61 wt%, at least 61.5 wt%, at least 62 wt%, based on the total weight of the zircon body. , at least 62.5%, at least 63%, at least 62.5%, at least 64%, at least 64.5%, at least 5%, at least 65.5%, at least 66%, at least 66.5%, at least 67%, at least 68%, at least 69%, at least 70%, at least 75%, at least 80%, at least 85%, at least 90%, or even at least 93% by weight of zircon. In another example, the zircon body comprises 99% or less by weight, e.g., 95% or less by weight, 90% or less by weight, 85% or less by weight, 80% or less by weight, 75% or less by weight, 70% or less by weight, 69% or less by weight, 68% or less by weight, 67% or less by weight, 66.5% or less by weight, 66% or less by weight, 66.5% or less by weight, 65% or less by weight, 64.5% or less by weight, 64% or less by weight, 63.5% or less by weight, 53% or less by weight, or 65% or less by weight, based on the total weight of the zircon body. %, 62.5% or less, 62% or less, 61.5% or less, 61% or less, 60.5% or less, 60% or less, 59.5% or less, 59% or less, 58% or less, 58% or less, at least 57%, 57% or less, 56% or less, 55% or less, 54% or less, 53% or less, 52% or less, or even 51% or less by weight. It will be appreciated that the zircon content in weight percent relative to the total weight of the zircon body can be any value between any of the minimum and maximum values recited above.It will be further understood that the zircon content, in weight percent, of the total weight of the zircon body can be within a range between any of the minimum and maximum values recited above. In further embodiments, the zircon body can comprise zircon such that a majority or essentially all of the zircon is present in the fourth crystalline phase.
[0080] According to another particular embodiment, the zircon body may include a particular content of the Al2O3-containing component. For example, the zircon body may include an Al2O3-containing component of 10 wt% or less, such as an Al2O3-containing component of 9 wt% or less, an Al2O3-containing component of 8 wt% or less, an Al2O3-containing component of 7 wt% or less, an Al2O3-containing component of 6.8 wt% or less, an Al2O3-containing component of 6.5 wt% or less, an Al2O3-containing component of 6.2 wt% or less, an Al2O3-containing component of 6 wt% or less, an Al2O3-containing component of 5.8 wt% or less, an Al2O3-containing component of 5.6 wt% or less, an Al2O3-containing component of 5.3 wt% or less, an Al2O3-containing component of 5 wt% or less, an Al2O3-containing component of 4.8 wt% or less, or an Al2O3-containing component of 4.6 wt% or less, based on the total weight of the zircon body. In further examples, the zircon body may include at least 0.2 wt. % Al2O3, e.g., at least 0.5 wt. % Al2O3-containing component, at least 1.0 wt. % Al2O3-containing component, at least 1.5 wt. % Al2O3-containing component, at least 1.7 wt. % Al2O3-containing component, at least 2.0 wt. % Al2O3-containing component, at least 2.5 wt. % Al2O3-containing component, at least 3 wt. % Al2O3-containing component, at least 3.5 wt. % Al2O3-containing component, at least 3.8 wt. % Al2O3-containing component, at least 4 wt. % Al2O3-containing component, at least 4.2 wt. % Al2O3-containing component, at least 4.4 wt. % Al2O3-containing component, or even at least 4.5 wt. % Al2O3-containing component, based on the total weight of the zircon body. It will be appreciated that the content of the Al2O3-containing component in weight percent relative to the total weight of the zircon body can be any value between any of the minimum and maximum values set forth above. It will be further appreciated that the content of the Al2O3-containing component in weight percent relative to the total weight of the zircon body can be within a range between any of the minimum and maximum values set forth above.
[0081] According to another particular embodiment, the zircon body may include a particular content of Al2O3. For example, the zircon body may include 10 wt% or less Al2O3, such as 9 wt% or less Al2O3, 8 wt% or less Al2O3, 7 wt% or less Al2O3, 6.5 wt% or less Al2O3, 6 wt% or less Al2O3, 5.8 wt% or less Al2O3, 5.6 wt% or less Al2O3, 5.4 wt% or less Al2O3, 5.3 wt% or less Al2O3, 5.1 wt% or less Al2O3, 5 wt% or less Al2O3, 4.9 wt% or less Al2O3, 4.8 wt% or less Al2O3, 4.7 wt% or less Al2O3, 4.6 wt% or less Al2O3, or even 4.5 wt% or less Al2O3, based on the total weight of the zircon body. According to yet another embodiment, the zircon body may include at least 0.2% by weight Al2O3, for example, at least 0.5% by weight Al2O3, at least 1.0% by weight Al2O3, at least 1.5% by weight Al2O3, at least 2% by weight Al2O3, at least 2.5% by weight Al2O3, at least 3% by weight Al2O3, at least 3.4% by weight Al2O3, at least 3.7% by weight Al2O3, at least 4% by weight Al2O3, at least 4.1% by weight Al2O3, at least 4.2% by weight Al2O3, or even at least 4.3% by weight Al2O3, based on the total weight of the zircon body. It will be understood that the content of Al2O3 in weight% based on the total weight of the zircon body may be any value between any of the minimum and maximum values listed above. It will be further understood that the content of Al2O3 in weight% based on the total weight of the zircon body may be within a range between any of the minimum and maximum values listed above.
[0082] According to certain embodiments, the AI2O3-containing component in the zircon body may include alumina. According to yet other embodiments, the AI2O3-containing component in the zircon body may include a specific content of alumina. For example, the Al2O3-containing component in the zircon body may comprise at least 1 wt.% alumina, e.g., at least 2 wt.% alumina, at least 5 wt.% alumina, at least 10 wt.% alumina, at least 15 wt.% alumina, at least 20 wt.% alumina, at least 25 wt.% alumina, at least 30 wt.% alumina, at least 35 wt.% alumina, at least 40 wt.% alumina, at least 45 wt.% alumina, at least 50 wt.% alumina, at least 55 wt.% alumina, at least 60 wt.% alumina, at least 65 wt.% alumina, at least 70 wt.% alumina, at least 75 wt.% alumina, at least 80 wt.% alumina, at least 85 wt.% alumina, at least 90 wt.% alumina, at least 95 wt.% alumina, or the Al2O3-containing component may even consist essentially of alumina, based on the total weight of the Al2O3-containing component. It will be appreciated that the alumina content in the Al2O3-containing component in the zircon body can be any value or any value between at least any of the above values.
[0083] According to certain embodiments, the Al2O3-containing component in the zircon body may include mullite. According to yet other embodiments, the Al2O3-containing component in the zircon body may include a specific content of mullite. For example, the Al2O3-containing component in the zircon body can include at least 1 wt.% mullite, e.g., at least 2 wt.% mullite, at least 5 wt.% mullite, at least 10 wt.% mullite, at least 15 wt.% mullite, at least 20 wt.% mullite, at least 25 wt.% mullite, at least 30 wt.% mullite, at least 35 wt.% mullite, at least 40 wt.% mullite, at least 45 wt.% mullite, at least 50 wt.% mullite, at least 55 wt.% mullite, at least 60 wt.% mullite, at least 65 wt.% mullite, at least 70 wt.% mullite, at least 75 wt.% mullite, at least 80 wt.% mullite, at least 85 wt.% mullite, at least 90 wt.% mullite, at least 95 wt.% mullite, or the Al2O3-containing component can even consist essentially of mullite, based on the total weight of the Al2O3-containing component. It will be appreciated that the mullite content in the Al2O3-containing component in the zircon body can be any value, or any value between at least any of the above values.
[0084] According to yet another embodiment, the mullite in the zircon body is Al6Si2O 13 According to yet another embodiment, the mullite in the zircon body may include a specific content of Al6Si2O 13 For example, the mullite in the zircon body may contain at least 1 wt. % Al6Si2O 13 , e.g., at least 2 wt.% Al6Si2O 13 , at least 5% by weight of Al6SiO2 13 , at least 10% by weight of Al6Si2O 13 , at least 15% by weight of Al6SiO2 13 , at least 20% by weight of Al6Si2O 13 , at least 25% by weight of Al6SiO2 13, at least 30% by weight of Al6SiO2 13 , at least 35% by weight of Al6SiO2 13 , at least 40% by weight of Al6SiO2 13 , at least 45% by weight of Al6SiO2 13 , at least 50% by weight of Al6Si2O 13 , at least 55% by weight of Al6Si2O 13 , at least 60% by weight of Al6Si2O 13 , at least 65% by weight of Al6Si2O 13 , at least 70% by weight of Al6Si2O 13 , at least 75% by weight of Al6Si2O 13 , at least 80% by weight of Al6Si2O 13 , at least 85% by weight of Al6Si2O 13 , at least 90% by weight of Al6Si2O 13 , at least 95% by weight of Al6Si2O 13 Or the mullite in the zircon body may further include Al6Si2O 13 In the zircon body, the mullite may consist essentially of Al6Si2O 13 It will be appreciated that the content of can be any value or any value between at least any of the above values.
[0085] According to yet another particular embodiment, the Al2O3-containing component may include an aluminosilicate species. According to yet another embodiment, the aluminosilicate species may include at least one of non-stoichiometric mullite, stoichiometric mullite, and combinations thereof. According to yet another embodiment, the Al2O3-containing component may include a combination of an aluminate species and an aluminosilicate species. According to yet another embodiment, the aluminosilicate species is present in a content greater than the aluminate species.
[0086] According to another particular embodiment, the zircon body may include a particular content of mullite. In one aspect, the zircon body may include at least 0.5 wt.% mullite, based on the total weight of the zircon body, for example, at least 1 wt.%, at least 1.2 wt.%, at least 1.5 wt.%, at least 1.8 wt.%, at least 2 wt.%, at least 2.2 wt.%, at least 2.5 wt.%, at least 2.7 wt.%, at least 3 wt.%, at least 3.2 wt.%, at least 3.5 wt.%, at least 3.7 wt.%, at least 4.1 wt.% mullite, based on the total weight of the zircon body. In another embodiment, the zircon body may include 10% or less, 9% or less, 8.6% or less, 8.2% or less, 8% or less, 7.6% or less, 7.4% or less, 7.2% or less, 7% or less, 6% or less, 5% or less, 4% or less, 3.8% or less, 3.5% or less, 3.2% or less, or 3% or less by weight of mullite, based on the total weight of the zircon body. It will be understood that the content of mullite in weight percent based on the total weight of the zircon body may be any value between any of the minimum and maximum values listed above. It will be further understood that the content of mullite in weight percent based on the total weight of the zircon body may be within a range between any of the minimum and maximum values listed above. For example, the zircon body may include a content of mullite in a range of at least 0.5% and not more than 10% by weight, or in a range of at least 3% and not more than 8% by weight, based on the total weight of the zircon body.
[0087] In one embodiment, the zircon body has a particular ratio of C, which can facilitate the formation of a refractory body having improved properties and / or performance. ZN / C M C ZN is the content of zircon in weight percent relative to the total weight of the zircon body, and C M is the mullite content in weight percent relative to the total weight of the zircon body. ZN / C Mcan be at least 7, at least 8, at least 9, at least 10, at least 11, at least 12, at least 13, at least 14, at least 15, at least 16, at least 17, at least 18, at least 19, at least 20, at least 21, at least 22, at least 23, at least 24, at least 25, at least 26, at least 27, at least 28, at least 29, at least 30, at least 31, at least 32, or at least 33. ZN / C M The ratio may be 200 or less, 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 48 or less, 45 or less, 42 or less, 40 or less, 38 or less, 35 or less, 32 or less, or 30 or less. ZN / C M It will be appreciated that the ratio of C can be any value between any of the minimum and maximum values listed above. ZN / C M It will be further understood that the ratio of can be within a range between any of the minimum and maximum values recited above.
[0088] According to another particular embodiment, the zircon body may include a particular content of SiO2 component. The SiO2 component may include a combination of SiO2 added to the zircon body as part of the zircon material, SiO2 added to the zircon body as part of the Al2O3-containing component, and SiO2 added to the zircon body as free silica. Free silica may be defined as SiO2 that is not bound as part of the crystalline form of the zircon material or the Al2O3-containing component. For example, the zircon body may comprise, based on the total weight of the zircon body, an SiO2 content of 34.5 wt.% or less, an SiO2 content of 33 wt.% or less, an SiO2 content of 32.5 wt.% or less, an SiO2 content of 32 wt.% or less, an SiO2 content of 31.5 wt.% or less, an SiO2 content of 30 wt.% or less, an SiO2 content of 29.5 wt.% or less, an SiO2 content of 29 wt.% or less, an SiO2 content of 28.5 wt.% or less, an SiO2 content of 28 wt.% or less, an SiO2 content of 27.5 wt.% or less, an SiO2 content of 27 wt.% or less, or even greater than 26.5 wt.%. According to yet another embodiment, the zircon body may comprise at least 25.5 wt.% SiO2, at least 26 wt.% SiO2 component, at least 26.5 wt.% SiO2 component, at least 27 wt.% SiO2 component, at least 27.5 wt.% SiO2 component, at least 28 wt.% SiO2 component, at least 28.5 wt.% SiO2 component, at least 29 wt.% SiO2 component, at least 29.5 wt.% SiO2 component, at least 30 wt.% SiO2 component, at least 30.5 wt.% SiO2 component, at least 31 wt.% SiO2 component, at least 31.5 wt.% SiO2 component, at least 32 wt.% SiO2 component, at least 32.5 wt.% SiO2 component, at least 33 wt.% SiO2 component, at least 33.5 wt.% SiO2 component, about 34 wt.% SiO2 component, or even at least 34.5 wt.% SiO2 component, based on the total weight of the zircon body. It will be appreciated that the content of the SiO2 component in weight percent relative to the total weight of the zircon body can be any value between any of the minimum and maximum values set forth above. It will be further appreciated that the content of the SiO2 component in weight percent relative to the total weight of the zircon body can be within a range between any of the minimum and maximum values set forth above.
[0089] According to yet another embodiment, the zircon body has a specific ratio C SiO2 / C AlC C SiO2 can represent the content of SiO2 in weight percent relative to the total weight of the zircon body, and C AlC can represent the content of the Al2O3-containing component in weight percent relative to the total weight of the zircon body. For example, the zircon body can have a ratio C of at least 5, e.g., at least 8, at least 10, at least 13, at least 15, at least 18, at least 20, at least 23, at least 25, at least 28, at least 30, at least 33, at least 35, at least 38, at least 40, at least 43, at least 45, or even at least 48. SiO2 / C AlC According to another embodiment, the zircon body may have a ratio C of 50 or less, e.g., 47 or less, 45 or less, 42 or less, 40 or less, 37 or less, 35 or less, 32 or less, 30 or less, 27 or less, 20 or less, 17 or less, 12 or less, 10 or less, or even 7 or less. SiO2 / C AlC The ratio C SiO2 / C AlC It will be further understood that C can be any value between any of the minimum and maximum values listed above. SiO2 / C AlC It will be further understood that may be within a range between any of the minimum and maximum values listed above.
[0090] According to yet another embodiment, the zircon body has a specific ratio C AlC / C ZN C ALC can represent the content of Al2O3-containing components in weight percent relative to the total weight of the zircon body, and C ZNcan represent the content of zircon in weight percent relative to the total weight of the body. For example, the zircon body has a ratio C of 0.08 or less, e.g., 0.075 or less, 0.07 or less, 0.065 or less, 0.06 or less, 0.055 or less, 0.05 or less, 0.045 or less, 0.04 or less, 0.035 or less, 0.030 or less, 0.025 or less, 0.02 or less, 0.015 or less, or even 0.01 or less. AlC / C ZN According to yet another embodiment, the zircon body may include a C of at least 0.002, e.g., at least 0.005, at least 0.01, at least 0.02, at least 0.03, at least 0.035, at least 0.04, at least 0.045, at least 0.05, at least 0.055, at least 0.06, at least 0.065, at least 0.07, at least 0.075, at least 0.08, at least 0.085, or even at least 0.09. AlC / C ZN The ratio C AlC / C ZN It will be appreciated that C can be any value between any of the minimum and maximum values listed above. AlC / C ZN It will be further understood that may be within a range between any of the minimum and maximum values listed above.
[0091] According to yet another particular embodiment, the zircon body may include a sintering aid, such as Ta2O5 or TiO2. According to yet another particular embodiment, the zircon body may include a particular content of sintering aid. For example, the zircon body may include 5.0 wt.% or less of sintering aid, such as 4.5 wt.% or less of sintering aid, 4.0 wt.% or less of sintering aid, 3.5 wt.% or less of sintering aid, 3.0 wt.% or less of sintering aid, 2.5 wt.% or less of sintering aid, 2.0 wt.% or less of sintering aid, 1.5 wt.% or less of sintering aid, 1.0 wt.% or less of sintering aid, 0.5 wt.% or less of sintering aid, 0.1 wt.% or less of sintering aid, or the zircon body may even be essentially free of sintering aid, based on the total weight of the zircon body. According to yet another particular embodiment, the zircon body may include at least 0.1 wt. % sintering aid, at least 0.2 wt. % sintering aid, at least 0.3 wt. % sintering aid, at least 0.4 wt. % sintering aid, at least 0.5 wt. % sintering aid, at least 0.6 wt. % sintering aid, at least 0.7 wt. % sintering aid, at least 0.8 wt. % sintering aid, or even at least 0.9 wt. % sintering aid, based on the total weight of the zircon body. It will be understood that the content of the sintering aid in wt. % based on the total weight of the zircon body may be any value between any of the minimum and maximum values listed above. It will be further understood that the content of the sintering aid in wt. % based on the total weight of the zircon body may be within a range between any of the minimum and maximum values listed above.
[0092] According to yet another embodiment, the zircon body has a specific ratio C SA / C SiO2 C SA represents the content of the sintering aid in weight percent relative to the total weight of the zircon body, and C SiO2 represents the content of the SiO2 component in weight percent relative to the total weight of the zircon body. According to certain embodiments, the zircon body has a ratio CB of 0.5 or less, for example, 0.1 or less, 0.05 or less, 0.04 or less, 0.03 or less, or even 0.02 or less. SA / CB SiO2According to another particular embodiment, the zircon body may have a ratio C of at least 0.001, e.g., at least 0.005, at least 0.01, at least 0.02, or even at least 0.03. SA / C SiO2 The ratio C SA / C SiO2 It will be appreciated that C can be any value between any of the minimum and maximum values listed above. SA / C SiO2 It will be further understood that may be within a range between any of the minimum and maximum values listed above.
[0093] According to yet another embodiment, the zircon body may include a specific content of Ta2O5. For example, the zircon body may include at least 0.1 wt% Ta2O5, such as at least 0.2 wt% Ta2O5, at least 0.3 wt% Ta2O5, at least 0.4 wt% Ta2O5, at least 0.5 wt% Ta2O5, at least 0.6 wt% Ta2O5, at least 0.7 wt% Ta2O5, at least 0.8 wt% Ta2O5, or even at least 0.9 wt% Ta2O5, based on the total weight of the zircon body. According to yet another embodiment, the zircon body may include 3.0 wt.% or less Ta2O5, for example, 2.5 wt.% or less Ta2O5, 2.0 wt.% or less Ta2O5, 1.5 wt.% or less Ta2O5, 1.0 wt.% or less Ta2O5, 0.5 wt.% or less Ta2O5, 0.1 wt.% or less Ta2O5, or the zircon body may even be essentially free of Ta2O5, based on the total weight of the zircon body. It will be understood that the content of Ta2O5 in wt.% based on the total weight of the zircon body may be any value between any of the minimum and maximum values listed above. It will be further understood that the content of Ta2O5 in wt.% based on the total weight of the zircon body may be within a range between any of the minimum and maximum values listed above.
[0094] According to yet another embodiment, the zircon body has a specific ratio C Ta2O5 / C SiO2 C Ta2O5represents the Ta2O5 content in weight percent relative to the total weight of the zircon body, and C SiO2 represents the content of the SiO2 component in weight percent relative to the total weight of the zircon body. According to certain embodiments, the zircon body has a ratio C of 0.5 or less, for example, 0.1 or less, 0.05 or less, 0.04 or less, 0.03 or less, or even 0.02 or less. Ta2O5 / C SiO2 According to another particular embodiment, the zircon body may have a ratio C of at least 0.001, e.g., at least 0.005, at least 0.01, at least 0.02, or even at least 0.03. Ta2O5 / C SiO2 The ratio C Ta2O5 / C SiO2 It will be appreciated that C can be any value between any of the minimum and maximum values listed above. Ta2O5 / C SiO2 It will be further understood that may be within a range between any of the minimum and maximum values listed above.
[0095] According to yet another embodiment, the zircon body may include a specific content of TiO2. For example, the zircon body may include 5.0 wt% or less TiO2, e.g., 4.5 wt% or less TiO2, 4.0 wt% or less TiO2, 3.5 wt% or less TiO2, 3.0 wt% or less TiO2, 2.5 wt% or less TiO2, 2.0 wt% or less TiO2, 1.5 wt% or less TiO2, 1.0 wt% or less TiO2, 0.5 wt% or less TiO2, 0.1 wt% or less TiO2, or the zircon body may even be essentially free of TiO2, based on the total weight of the zircon body. According to yet another particular embodiment, the zircon body may include at least 0.1 wt.% TiO2, at least 0.2 wt.% TiO2, at least 0.3 wt.% TiO2, at least 0.4 wt.% TiO2, at least 0.5 wt.% TiO2, at least 0.6 wt.% TiO2, at least 0.7 wt.% TiO2, at least 0.8 wt.% TiO2, or even at least 0.9 wt.% TiO2, based on the total weight of the zircon body. It will be understood that the content of TiO2 based on the total weight of the zircon body may be any value between any of the minimum and maximum values listed above. It will be further understood that the content of TiO2 in wt.% based on the total weight of the zircon body may be within a range between any of the minimum and maximum values listed above.
[0096] According to yet another embodiment, the zircon body has a specific ratio C TiO2 / C SiO2 C TiO2 represents the TiO2 content in weight percent relative to the total weight of the zircon body, and C SiO2 represents the content of the SiO2 component in weight percent relative to the total weight of the zircon body. According to certain embodiments, the zircon body has a ratio C of 0.5 or less, for example, 0.1 or less, 0.05 or less, 0.04 or less, 0.03 or less, or even 0.02 or less. TiO2 / C SiO2 According to another particular embodiment, the zircon body may have a ratio C of at least 0.001, e.g., at least 0.005, at least 0.01, at least 0.02, or even at least 0.03. TiO2 / CSiO2 The ratio C TiO2 / C SiO2 It will be appreciated that C can be any value between any of the minimum and maximum values listed above. TiO2 / C SiO2 It will be further understood that may be within a range between any of the minimum and maximum values listed above.
[0097] According to yet another embodiment, the zircon body may include a specific content of combined Ta2O5 and TiO2. For example, the zircon body may include 5.0 wt.% or less of combined Ta2O5 and TiO2, e.g., 4.0 wt.% or less of combined Ta2O5 and TiO2, 3.0 wt.% or less of combined Ta2O5 and TiO2, 2.0 wt.% or less of combined Ta2O5 and TiO2, 1.0 wt.% or less of combined Ta2O5 and TiO2, 0.5 wt.% or less of combined Ta2O5 and TiO2, 0.1 wt.% or less of combined Ta2O5 and TiO2, or the zircon body may even be essentially free of combined Ta2O5 and TiO2, based on the total weight of the zircon body. According to yet another embodiment, the zircon body may include at least 0.1 weight percent of the combined Ta2O5 and TiO2, e.g., at least 0.2 weight percent of the combined Ta2O5 and TiO2, at least 0.3 weight percent of the combined Ta2O5 and TiO2, at least 0.4 weight percent of the combined Ta2O5 and TiO2, at least 0.5 weight percent of the combined Ta2O5 and TiO2, at least 0.6 weight percent of the combined Ta2O5 and TiO2, at least 0.7 weight percent of the combined Ta2O5 and TiO2, at least 0.8 weight percent of the combined Ta2O5 and TiO2, or even at least 0.9 weight percent of the combined Ta2O5 and TiO2, based on the total weight of the zircon body. It will be appreciated that the combined Ta2O5 and TiO2 content in weight percent relative to the total weight of the zircon body can be any value between any of the minimum and maximum values set forth above. It will be further appreciated that the combined Ta2O5 and TiO2 content in weight percent relative to the total weight of the zircon body can be within a range between any of the minimum and maximum values set forth above.
[0098] According to certain embodiments, the zircon body may include a particular content of alkaline earth oxides that may facilitate the formation of a refractory having improved properties and / or performance. In one aspect, the zircon body may include one or more alkaline earth oxides, and the total alkaline earth oxide content may be at least 0.02 wt.%, e.g., at least 0.1 wt.%, at least 0.15 wt.%, at least 0.2 wt.%, at least 0.5 wt.%, at least 0.8 wt.%, at least 1 wt.%, at least 1.2 wt.%, at least 1.5 wt.%, at least 1.8 wt.%, or at least 2 wt.%, based on the total weight of the zircon body. In another aspect, the total alkaline earth oxide content may be 8 wt.% or less, e.g., 7 wt.% or less, 6 wt.% or less, 5 wt.% or less, or 4 wt.% or less, based on the total weight of the zircon body. Furthermore, the total alkaline earth oxide content may be any value within a range including any of the minimum and maximum percentages described herein. It will be further understood that the total alkaline earth oxide content can be within a range including any of the minimum and maximum percentages described herein, for example, the total content can be within a range of at least 0.02 wt.% and not more than 8 wt.%, or within a range of at least 0.15 wt.% and not more than 8 wt.%, based on the total weight of the zircon body.
[0099] According to certain embodiments, the zircon body has a particular ratio of C that can facilitate the formation of a refractory body having improved properties and / or performance. Al2O3 / C AKO C Al2O3 is the alumina content in weight percent relative to the total weight of the zircon body, and C AKO is the alkaline earth oxide content in weight percent relative to the total weight of the zircon body. In certain embodiments, the alkaline earth oxide may include CaO, BaO, SrO, MgO, or any combination thereof. In one example, C Al2O3 / C AKOcan be at least 1, at least 2, at least 3, at least 4, at least 5, at least 6, at least 7, at least 8, at least 9, at least 10, at least 11, at least 12, at least 13, or at least 14. Al2O3 / C AKO The ratio may be 200 or less, 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 40 or less, 30 or less, 20 or less, 15 or less, 14 or less, 13 or less, 12 or less, 11 or less, 10 or less, or 9 or less. Al2O3 / C AKO It will be appreciated that the ratio of C can be any value between any of the minimum and maximum values listed above. Al2O3 / C AKO It will be further understood that the ratio of can be within a range between any of the minimum and maximum values recited above.
[0100] In certain embodiments, the zircon body may include a particular content of CaO that may facilitate the formation of a refractory having improved properties and / or performance, such as at least 0.02 wt.%, at least 0.08 wt.%, at least 0.1 wt.%, at least 0.15 wt.%, at least 0.2 wt.%, at least 0.3 wt.%, at least 0.5 wt.%, at least 0.7 wt.%, at least 1 wt.%, at least 1.2 wt.%, at least 1.4 wt.%, at least 1.5 wt.%, at least 1.8 wt.%, or at least 2 wt.% CaO, based on the total weight of the zircon body. In another example, the zircon body may include 5 wt.% or less CaO, e.g., 4 wt.% or less, 3.8 wt.% or less, 3.5 wt.% or less, 3 wt.% or less CaO, 3.8 wt.% or less, 3.5 wt.% or less, 3.2 wt.% or less, 3 wt.% or less CaO, 2.8 wt.% or less, 2.5 wt.% or less, 2.2 wt.% or less, 2 wt.% or less CaO, 1.8 wt.% or less, 1.5 wt.% or less, 1.2 wt.% or less, or 1 wt.% or less CaO, based on the total weight of the zircon body. In a particular example, the zircon body may include a CaO content that may be any percentage within a range that includes any of the minimum and maximum percentages described herein. It is further understood that the zircon body may include a CaO content within a range that includes any of the minimum and maximum percentages described herein.
[0101] According to certain embodiments, the zircon body has a particular ratio of C that can facilitate the formation of a refractory body having improved properties and / or performance. Al2O3 / C CaO C Al2O3 is the alumina content in weight percent relative to the total weight of the zircon body, and C CaO is the CaO content in weight percent relative to the total weight of the zircon body. Al2O3 / C CaOcan be at least 1, at least 2, at least 3, at least 4, at least 5, at least 6, at least 7, at least 8, at least 9, at least 10, at least 11, at least 12, at least 13, or at least 14. Al2O3 / C AKO The ratio may be 200 or less, 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 40 or less, 30 or less, 20 or less, 15 or less, 14 or less, 13 or less, 12 or less, 11 or less, 10 or less, or 9 or less. Al2O3 / C CaO It will be appreciated that the ratio of C can be any value between any of the minimum and maximum values listed above. Al2O3 / C CaO It will be further understood that the ratio of can be within a range between any of the minimum and maximum values recited above.
[0102] According to yet another embodiment, the zircon body may include a specific content of MgO that may facilitate the formation of a refractory having improved properties and / or performance. For example, the zircon body may include at least 0.01 wt.% MgO, e.g., at least 0.02 wt.% MgO, at least 0.03 wt.% MgO, at least 0.04 wt.% MgO, at least 0.05 wt.% MgO, at least 0.06 wt.% MgO, at least 0.07 wt.% MgO, at least 0.08 wt.% MgO, at least 0.09 wt.% MgO, at least 0.1 wt.%, at least 0.12 wt.%, at least 0.13 wt.%, at least 0.15 wt.%, or at least 0.18 wt.% MgO, based on the total weight of the zircon body. In another instance, the zircon body may include 0.2 wt.% or less MgO, for example, 0.18 wt.% or less, 0.15 wt.% or less, 0.12 wt.% or less, 0.1 wt.% or less, 0.08 wt.% or less, 0.05 wt.% or less, or 0.03 wt.% or less MgO, based on the total weight of the zircon body. Furthermore, the zircon body may include a content of MgO that may be any percentage within a range including any of the minimum and maximum percentages described herein. It is further understood that the zircon body may include a content of MgO within a range including any of the minimum and maximum percentages described herein. In certain embodiments, the zircon body may be essentially free of MgO. For example, MgO may be an impurity from one or more of the raw materials.
[0103] According to certain embodiments, the zircon body has a particular ratio of C that can facilitate the formation of a refractory body having improved properties and / or performance. Al2O3 / C MgO C Al2O3 is the alumina content in weight percent relative to the total weight of the zircon body, and C MgO is the content of MgO in weight percent relative to the total weight of the zircon body. Al2O3 / C MgOcan be at least 5, at least 6, at least 7, at least 8, at least 9, at least 10, at least 11, at least 12, at least 13, at least 14, at least 16, at least 18, at least 20, at least 24, at least 25, at least 28, at least 30, at least 33, at least 35, at least 38, or at least 40. Al2O3 / C MgO The ratio may be 5000 or less, 4000 or less, 3000 or less, 2000 or less, 1000 or less, 800 or less, 700 or less, 500 or less, 300 or less, 200 or less, 150 or less, 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 40 or less, 30 or less, or 20 or less. Al2O3 / C MgO It will be appreciated that the ratio of C can be any value between any of the minimum and maximum values listed above. Al2O3 / C MgO It will be further understood that the ratio of can be within a range between any of the minimum and maximum values recited above.
[0104] According to yet another embodiment, the zircon body may include a specific content of BaO that may facilitate the formation of a refractory having improved properties and / or performance. For example, the zircon body may include at least 0.05 wt.% BaO, based on the total weight of the zircon body, at least 0.1 wt.%, at least 0.2 wt.%, at least 0.3 wt.%, at least 0.5 wt.%, at least 0.8 wt.%, at least 1 wt.%, at least 1.2 wt.%, at least 1.4 wt.%, at least 1.5 wt.%, at least 1.8 wt.%, or at least 2 wt.% BaO, based on the total weight of the zircon body. In another example, the zircon body may include 5 wt% or less BaO, for example, 4 wt% or less, 3.8 wt% or less, 3.5 wt% or less, 3.2 wt% or less, 3 wt% or less, 2.8 wt% or less, 2.5 wt% or less, 2.2 wt% or less, 2 wt% or less, 1.8 wt% or less, 1.5 wt% or less, or 1.2 wt% or less, or 1 wt% or less BaO, based on the total weight of the zircon body. Furthermore, the zircon body may include a BaO content that may be any percentage within a range including any of the minimum and maximum percentages described herein. It will be further understood that the zircon body may include a BaO content within a range including any of the minimum and maximum percentages described herein.
[0105] According to certain embodiments, the zircon body has a particular ratio of C that can facilitate the formation of a refractory body having improved properties and / or performance. Al2O3 / C BaO C Al2O3 is the alumina content in weight percent relative to the total weight of the zircon body, and C BaO is the BaO content in weight percent relative to the total weight of the zircon body. Al2O3 / C BaO can be at least 1, at least 2, at least 3, at least 4, at least 5, at least 6, at least 7, at least 8, at least 9, at least 10, at least 11, at least 12, at least 13, or at least 14. Al2O3 / CBaO The ratio may be 200 or less, 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 40 or less, 30 or less, 20 or less, 15 or less, 14 or less, 13 or less, 12 or less, 11 or less, 10 or less, or 9 or less. Al2O3 / C BaO It will be appreciated that the ratio of C can be any value between any of the minimum and maximum values listed above. Al2O3 / C BaO It will be further understood that the ratio of can be within a range between any of the minimum and maximum values recited above.
[0106] According to yet another embodiment, the zircon body may include a particular content of SrO that may facilitate the formation of a refractory having improved properties and / or performance. For example, the zircon body may include at least 0.05 wt.% SrO, at least 0.1 wt.%, at least 0.15 wt.%, at least 0.2 wt.%, at least 0.3 wt.%, at least 0.5 wt.%, at least 0.8 wt.%, at least 1 wt.%, at least 1.2 wt.%, at least 1.4 wt.%, at least 1.6 wt.%, at least 1.8 wt.%, or at least 2 wt.% SrO, based on the total weight of the zircon body. In another example, the zircon body may include 5 wt.% or less SrO, for example, 4 wt.%, 3.8 wt.%, 3.5 wt.%, 3.2 wt.%, 3 wt.%, 2.8 wt.%, 2.5 wt.%, 2.2 wt.%, 2 wt.%, 1.8 wt.%, 1.5 wt.%, 1.2 wt.%, or 1 wt.% or less SrO, based on the total weight of the zircon body. Furthermore, the zircon body may include a content of SrO that may be any percentage within a range including any of the minimum and maximum percentages described herein. It will be further understood that the zircon body may include a content of SrO within a range including any of the minimum and maximum percentages described herein.
[0107] According to certain embodiments, the zircon body has a particular ratio of C that can facilitate the formation of a refractory body having improved properties and / or performance. Al2O3 / C SrO C Al2O3 is the alumina content in weight percent relative to the total weight of the zircon body, and C SrO is the SrO content in weight percent relative to the total weight of the zircon body. Al2O3 / C SrO can be at least 1, at least 2, at least 3, at least 4, at least 5, at least 6, at least 7, at least 8, at least 9, at least 10, at least 11, at least 12, at least 13, or at least 14. Al2O3 / C SrO The ratio may be 200 or less, 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 40 or less, 30 or less, 20 or less, 15 or less, 14 or less, 13 or less, 12 or less, 11 or less, 10 or less, or 9 or less. Al2O3 / C SrO It will be appreciated that the ratio of C can be any value between any of the minimum and maximum values listed above. Al2O3 / C SrO It will be further understood that the ratio of can be within a range between any of the minimum and maximum values recited above.
[0108] According to yet another embodiment, the zircon body may include a particular content of K2O. For example, the zircon body may include 1.0 wt.% or less K2O, e.g., 0.8 wt.% or less K2O, 0.5 wt.% or less K2O, 0.4 wt.% or less K2O, 0.3 wt.% or less K2O, 0.2 wt.% or less K2O, 0.1 wt.% or less K2O, based on the total weight of the zircon body, or the zircon body may be essentially free of K2O.
[0109] According to yet another embodiment, the zircon body may include a particular content of Na2O. For example, the zircon body may include 1.0 wt.% or less Na2O, e.g., 0.8 wt.% or less Na2O, 0.5 wt.% or less Na2O, 0.4 wt.% or less Na2O, 0.3 wt.% or less Na2O, 0.2 wt.% or less Na2O, 0.1 wt.% or less Na2O, based on the total weight of the zircon body, or the zircon body may be essentially free of Na2O.
[0110] According to yet another embodiment, the zircon body may include a particular content of Y2O3. For example, the zircon body may include 1.0 wt% or less Y2O3, e.g., 0.8 wt% or less Y2O3, 0.5 wt% or less Y2O3, 0.4 wt% or less Y2O3, 0.3 wt% or less Y2O3, 0.2 wt% or less Y2O3, 0.1 wt% or less Y2O3, or the zircon body may be essentially free of Y2O3, based on the total weight of the zircon body.
[0111] According to yet another embodiment, the zircon body may include a particular content of P2O5. For example, the zircon body may include 1.0 wt% or less P2O5, e.g., 0.8 wt% or less P2O5, 0.5 wt% or less P2O5, 0.4 wt% or less P2O5, 0.3 wt% or less P2O5, 0.2 wt% or less P2O5, 0.1 wt% or less P2O5, or the zircon body may be essentially free of P2O5, based on the total weight of the zircon body.
[0112] According to yet another embodiment, the zircon body may include a specific content of Fe2O3. For example, the zircon body may include 1.0 wt.% or less Fe2O3, e.g., 0.8 wt.% or less Fe2O3, 0.5 wt.% or less Fe2O3, 0.4 wt.% or less Fe2O3, 0.3 wt.% or less Fe2O3, 0.2 wt.% or less Fe2O3, 0.1 wt.% or less Fe2O3, or the zircon body may be essentially free of Fe2O3, based on the total weight of the zircon body.
[0113] According to yet another embodiment, the zircon body may include a particular content of ZnO, for example, the zircon body may include 1.0 wt.% or less ZnO, e.g., 0.8 wt.% or less ZnO, 0.5 wt.% or less ZnO, 0.4 wt.% or less ZnO, 0.3 wt.% or less ZnO, 0.2 wt.% or less ZnO, 0.1 wt.% or less ZnO, or the zircon body may be essentially free of ZnO, based on the total weight of the zircon body.
[0114] According to yet another embodiment, the zircon body may include specific contents of combined Yb2O3, K2O, Na2O, Y2O3, P2O5, Fe2O3, and ZnO. For example, the zircon body may include 1.5 wt. % or less of combined Yb2O3, K2O, Na2O, Y2O3, P2O5, Fe2O3, and ZnO, e.g., 1.2 wt. % or less of combined Yb2O3, K2O, Na2O, Y2O3, P2O5, Fe2O3, and ZnO, 1.0 wt. % or less of combined Yb2O3, K2O, Na2O, Y2O3, P2O5, Fe2O3, and ZnO, 0.7 wt. % or less of combined Yb2O3, K2O, Na2O, Y2O3, P2O5, Fe2O3, and ZnO, based on the total weight of the zircon body. and ZnO, 0.5 wt. % or less of combined Yb2O3, K2O, Na2O, Y2O3, P2O5, Fe2O3, and ZnO, 0.2 wt. % or less of combined Yb2O3, K2O, Na2O, Y2O3, P2O5, Fe2O3, and ZnO, 0.1 wt. % or less of combined Yb2O3, K2O, Na2O, Y2O3, P2O5, Fe2O3, and ZnO, or the zircon body may be essentially free of combined Yb2O3, K2O, Na2O, Y2O3, P2O5, Fe2O3, and ZnO.
[0115] In other embodiments, the zircon body may have a minimum content of metal oxides, such as, for example, rare earth oxides, alkali oxides, and any transition metal oxide not expressly disclosed herein. The rare earth oxides may include any oxide composition including a rare earth metal from the lanthanide series (i.e., elements having atomic numbers between 57 and 71), such as lanthanum oxide, cerium oxide, and europium oxide. The alkali oxides may include any oxide composition including a Group 1 metal (i.e., lithium, sodium, potassium, rubidium, cesium, and francium), such as lithium oxide, potassium oxide, and cesium oxide. The zircon body having a minimum content of any of the above oxides, such as, for example, rare earth oxides, alkali oxides, and any transition metal oxide not expressly disclosed herein, may have a content of that oxide of 1 wt. % or less, such as, for example, 0.7 wt. % or less, 0.5 wt. % or less, or even 0.2 wt. % or less of the total weight of the zircon body.
[0116] According to certain embodiments, the refractory material formed according to the methods described herein may include an amorphous phase that includes free silica. Free silica may be defined as SiO2 that is not bound as part of the crystalline form of the zircon material or Al2O3-containing component. In certain aspects, most or essentially all of the free silica may be present in the amorphous phase of the zircon body. In further embodiments, the fourth crystalline phase may include zircon grains and the free silica may be present between the zircon grains.
[0117] According to yet other embodiments, the zircon body may include a particular content of free silica, for example, the zircon body may include 4.5% or less free silica, e.g., 4.0% or less free silica, 3.9% or less free silica, 3.8% or less free silica, 3.7% or less free silica, 3.6% or less free silica, 3.5% or less free silica, 3.4% or less free silica, 3.3% or less free silica, 3.2% or less free silica, 3.1% or less free silica, 3.0% or less free silica, 2.9% or less free silica, 2.8% or less free silica, 2.7% or less free silica, 2.6% or less free silica, based on the total weight of the zircon body. % free silica, up to 2.5% free silica, up to 2.4% free silica, up to 2.3% free silica, up to 2.2% free silica, up to 2.1% free silica, up to 2.0% free silica, up to 1.9% free silica, up to 1.8% free silica, up to 1.7% free silica, up to 1.6% free silica, up to 1.5% free silica, up to 1.4% free silica, up to 1.3% free silica, up to 1.2% free silica, up to 1.1% free silica, up to 1.0% free silica, or even up to 0.5% free silica.According to yet other embodiments, the zircon body has at least 0.1 wt. % free silica, e.g., at least 0.5 wt. % free silica, at least 0.6 wt. % free silica, at least 0.7 wt. % free silica, at least 0.8 wt. % free silica, at least 0.9 wt. % free silica, at least 1.0 wt. % free silica, at least 1.1 wt. % free silica, at least 1.1 wt. % free silica, at least 1.2 wt. % free silica, at least 1.3 wt. % free silica, at least 1.4 wt. % free silica, at least 1.5 wt. % free silica, at least 1.6 wt. % free silica, at least 1.7 wt. % free silica, at least 1.8 wt. % free silica, at least 1.9 wt. % free silica, at least 2.0 wt. % free silica, at least 2.1 wt. % free silica, based on the total weight of the zircon body. The zircon body may comprise at least 2.2% free silica, at least 2.3% free silica, at least 2.4% free silica, at least 2.5% free silica, at least 2.6% free silica, at least 2.7% free silica, at least 2.8% free silica, at least 2.9% free silica, at least 3.0% free silica, at least 3.1% free silica, at least 3.2% free silica, at least 3.3% free silica, at least 3.4% free silica, at least 3.5% free silica, at least 3.6% free silica, at least 3.7% free silica, at least 3.8% free silica, at least 3.9% free silica, at least 4.0% free silica, or even at least 4.5% free silica. It will be appreciated that the content of free silica in the zircon body in weight percent relative to the total weight of the zircon body may be any value between any of the minimum and maximum values listed above. It will be further understood that the content of free silica in the zircon body, in weight percent based on the total weight of the zircon body, can be within a range between any of the minimum and maximum values set forth above.
[0118] According to another particular embodiment, the zircon grains in the zircon body may include a particular content of free silica, for example, the zircon grains may include 4.5% or less free silica by weight, e.g., 4.0% or less free silica, 3.9% or less free silica, 3.8% or less free silica, 3.7% or less free silica, 3.6% or less free silica, 3.5% or less free silica, 3.4% or less free silica, 3.3% or less free silica, 3.2% or less free silica, 3.1% or less free silica, 3.0% or less free silica, 2.9% or less free silica, 2.8% or less free silica, 2.7% or less free silica, 2.6% or less free silica, based on the total weight of the zircon body. % free silica, up to 2.5% free silica, up to 2.4% free silica, up to 2.3% free silica, up to 2.2% free silica, up to 2.1% free silica, up to 2.0% free silica, up to 1.9% free silica, up to 1.8% free silica, up to 1.7% free silica, up to 1.6% free silica, up to 1.5% free silica, up to 1.4% free silica, up to 1.3% free silica, up to 1.2% free silica, up to 1.1% free silica, up to 1.0% free silica, or even up to 0.5% free silica.According to yet other embodiments, the zircon grains have at least 0.1 wt. % free silica, e.g., at least 0.5 wt. % free silica, at least 0.6 wt. % free silica, at least 0.7 wt. % free silica, at least 0.8 wt. % free silica, at least 0.9 wt. % free silica, at least 1.0 wt. % free silica, at least 1.1 wt. % free silica, at least 1.1 wt. % free silica, at least 1.2 wt. % free silica, at least 1.3 wt. % free silica, at least 1.4 wt. % free silica, at least 1.5 wt. % free silica, at least 1.6 wt. % free silica, at least 1.7 wt. % free silica, at least 1.8 wt. % free silica, at least 1.9 wt. % free silica, at least 2.0 wt. % free silica, at least 2.1 wt. % free silica, at least 2.2 wt. % free silica, at least 2.3 wt. % free silica, at least 2.4 wt. % free silica, at least 2.5 wt. % free silica, at least 2.6 wt. % free silica, at least 2.7 wt. % free silica, at least 2.8 wt. % free silica, at least 2.9 wt. % free silica, at least 3.0 wt. % free silica, at least 3.1 wt. % free silica, at least 3.2 wt. % free silica, at least 3.3 wt. % free silica, at least 3.4 wt. % free silica, at least 3.5 wt. % free silica, at least 3.6 wt. % free silica, at least 3.7 wt. % free silica, at least free silica, at least 2.2% by weight free silica, at least 2.3% by weight free silica, at least 2.4% by weight free silica, at least 2.5% by weight free silica, at least 2.6% by weight free silica, at least 2.7% by weight free silica, at least 2.8% by weight free silica, at least 2.9% by weight free silica, at least 3.0% by weight free silica, at least 3.1% by weight free silica, at least 3.2% by weight free silica, at least 3.3% by weight free silica, at least 3.4% by weight free silica, at least 3.5% by weight free silica, at least 3.6% by weight free silica, at least 3.7% by weight free silica, at least 3.8% by weight free silica, at least 3.9% by weight free silica, at least 4.0% by weight free silica, or even at least 4.5% by weight free silica. It will be appreciated that the content of free silica in the zircon grains, in weight percent relative to the total weight of the zircon body, can be any value between any of the minimum and maximum values set forth above. It will be further appreciated that the content of free silica in the zircon grains, in weight percent relative to the total weight of the zircon body, can be within a range between any of the minimum and maximum values set forth above.
[0119] In one embodiment, the amorphous phase may include a specific content of silica (SiO2) that may facilitate the formation of refractory articles with improved properties and / or performance. According to yet another particular embodiment, the amorphous phase of the zircon body may include a specific content of SiO2 that may be measured using scanning electron microscopy with wavelength dispersive x-ray spectroscopy or scanning electron microscopy with energy dispersive x-ray spectroscopy. For example, the amorphous phase may comprise a silica content of at least 20 wt.%, based on the total weight of the amorphous phase, for example, at least 23 wt.%, at least 25 wt.%, at least 28 wt.%, at least 30 wt.%, at least 33 wt.%, at least 35 wt.%, at least 37 wt.%, at least 40 wt.%, at least 45 wt.%, at least 47 wt.%, at least 49 wt.%, at least 50 wt.%, at least 51 wt.%, at least 53 wt.%, at least 55 wt.%, at least 58 wt.%, at least 60 wt.%, at least 61 wt.%, at least 63 wt.%, at least 65 wt.%, at least 67 wt.%, or even at least 70 wt.%, based on the total weight of the amorphous phase. According to yet another embodiment, the amorphous phase may comprise a SiO2 content of 80% or less by weight, for example, 78% or less by weight, 75% or less by weight, 73% or less by weight, 71% or less by weight, 70% or less by weight, 69% or less by weight, 67% or less by weight, 65% or less by weight, 60% or less by weight, 55% or less by weight, 50% or less by weight, 45% or less by weight, 40% or less by weight, 37% or less by weight, 35% or less by weight, 33% or less by weight, 30% or less by weight, or even 27% or less by weight, based on the total weight of the amorphous phase. It will be understood that the SiO2 content in the amorphous phase may be any value between any of the above maximum and minimum values. It will be further understood that the SiO2 content in the amorphous phase may be any value within the range between any of the above maximum and minimum values. For example, the amorphous phase may have a silica content within a range including at least 47% to 85% by weight, based on the total weight of the amorphous phase, or within a range including at least 54% to 67% by weight, based on the total weight of the amorphous phase.
[0120] In one embodiment, the zircon body formed according to the embodiments described herein may include an amorphous phase including alumina (Al2O3). The alumina may be free alumina that is not bound as part of the crystalline form of the zircon material or silica-containing component. In further embodiments, most or essentially all of the free alumina may be present in the amorphous phase. In one embodiment, the amorphous phase may include a specific content of alumina (Al2O3) that may facilitate the formation of a refractory having improved properties and / or performance. According to yet another particular embodiment, the amorphous phase of the zircon body may include a specific content of Al2O3 that may be measured using scanning electron microscopy with wavelength dispersive x-ray spectroscopy or scanning electron microscopy with energy dispersive x-ray spectroscopy. For example, the amorphous phase may comprise an alumina content of at least 5 wt. % Al2O3, based on the total weight of the amorphous phase, for example, at least 8 wt. %, at least 10 wt. %, at least 12 wt. %, at least 13 wt. %, at least 14 wt. %, at least 15 wt. %, at least 16 wt. %, at least 17 wt. %, at least 18 wt. %, at least 20 wt. %, at least 21 wt. %, at least 22 wt. %, at least 23 wt. %, or even at least 25 wt. %, based on the total weight of the amorphous phase. According to yet another embodiment, the amorphous phase may comprise an alumina content of 39% or less by weight Al2O3, for example, 37% or less by weight, 35% or less by weight, 32% or less by weight, 30% or less by weight, 28% or less by weight, 27% or less by weight, 25% or less by weight, 23% or less by weight, 21% or less by weight, 19% or less by weight, 17% or less by weight, 16% or less by weight, 15% or less by weight, or 13% or less by weight, based on the total weight of the amorphous phase. It will be understood that the content of Al2O3 in the amorphous phase may be any value between any of the maximum and minimum values listed above. It will be further understood that the content of Al2O3 in the amorphous phase may be any value within the range between any of the maximum and minimum values listed above. For example, the amorphous phase may have an alumina content within a range including at least 10% by weight and up to 35% by weight, based on the total weight of the amorphous phase, or within a range including at least 16% by weight and up to 23% by weight, based on the total weight of the amorphous phase.
[0121] According to yet another particular embodiment, the amorphous phase of the zircon body may include a particular content of alkaline earth oxides, which may be measured using scanning electron microscopy with energy dispersive X-ray spectroscopy or scanning electron microscopy with wavelength dispersive X-ray spectroscopy. The alkaline earth oxides may be free alkaline earth oxides that are not bound as part of the zircon material or alumina-containing components. The alkaline earth oxides may include CaO, BaO, MgO, SrO, or any combination thereof. In a particular aspect, most or essentially all of the free alkaline earth oxides may be present in the amorphous phase.
[0122] In one embodiment, the amorphous phase may include a particular total content of alkaline earth oxides that may facilitate the formation of a refractory having improved properties and / or performance. In one example, the amorphous phase may include a total content of alkaline earth oxides of at least 2 wt.% based on the total weight of the amorphous phase. In a particular example, the amorphous phase may include more than 2.9 wt.% alkaline earth oxides based on the total weight of the amorphous phase, such as more than 3.0 wt.%, at least 3.1 wt.%, at least 3.2 wt.%, at least 3.5 wt.%, at least 3.8 wt.%, at least 4 wt.%, at least 4.3 wt.%, at least 4.5 wt.%, at least 4.8 wt.%, at least 5 wt.%, at least 5.3 wt.%, at least 5.5 wt.%, at least 5.7 wt.%, at least 6.0 wt.%, at least 6.3 wt.%, at least 6.5 wt.%, at least 6.8 wt.%, at least 7 wt.%, at least 7.6 wt.%, at least 7.9 wt.%, at least 8 wt.%, at least 9 wt.%, at least 10 ... In some embodiments, the alkaline earth oxides may comprise a total alkaline earth oxide content of at least 8.1 wt.%, at least 8.3 wt.%, at least 8.5 wt.%, at least 8.8 wt.%, at least 9 wt.%, at least 9.3 wt.%, at least 9.5 wt.%, at least 9.8 wt.%, at least 10 wt.%, at least 10.4 wt.%, at least 10.8 wt.%, at least 11.0 wt.%, at least 11.3 wt.%, at least 11.5 wt.%, at least 11.8 wt.%, at least 12.0 wt.%, at least 12.3 wt.%, at least 12.5 wt.%, at least 12.8 wt.%, at least 13.0 wt.%, or even at least 13.2 wt.%. According to yet another embodiment, the amorphous phase may comprise an alkaline earth oxide content of 50% or less by weight, based on the total weight of the amorphous phase, for example, 45% or less by weight, 40% or less by weight, 35% or less by weight, 30% or less by weight, 25% or less by weight, 20% or less by weight, 15% or less by weight, or 14% or less by weight, based on the total weight of the amorphous phase.In certain cases, the amorphous phase may include a total content of alkaline earth oxide of 13.7% or less by weight, for example, 13.5% or less by weight, 13.2% or less by weight, 13% or less by weight, 12% or less by weight, 11% or less by weight, 10% or less by weight, 9% or less by weight, 8% or less by weight, 7% or less by weight, 6% or less by weight, 5% or less by weight, 4.5% or less by weight, 4.2% or less by weight, 4% or less by weight, or 3.5% or less by weight, based on the total weight of the amorphous phase. It is understood that the content of alkaline earth oxide in the amorphous phase may be any value between any of the maximum and minimum values described above. It is further understood that the content of alkaline earth oxide in the amorphous phase may be any value within a range between any of the maximum and minimum values described above.
[0123] In one embodiment, the amorphous phase may include a specific content of calcium oxide (CaO) that may facilitate the formation of a refractory having improved properties and / or performance. According to yet another particular embodiment, the amorphous phase of the zircon body may include a specific content of CaO that may be measured using scanning electron microscopy with energy dispersive X-ray spectroscopy or scanning electron microscopy with wavelength dispersive X-ray spectroscopy. For example, the amorphous phase may comprise a calcium oxide content of more than 1.9 wt.%, based on the total weight of the amorphous phase, e.g., a calcium oxide content of at least 2.0 wt.%, at least 2.2 wt.%, at least 2.5 wt.%, at least 2.8 wt.%, at least 3 wt.%, at least 3.2 wt.%, at least 3.5 wt.%, at least 3.8 wt.%, at least 4.2 wt.%, at least 4.8 wt.%, at least 5 wt.%, at least 5.2 wt.%, at least 5.5 wt.%, at least 5.7 wt.%, at least 5.9 wt.%, at least 6.2 wt.%, at least 6.5 wt.%, at least 6.7 wt.%, at least 6.8 wt.%, at least 7 wt.%, at least 7.1 wt.%, at least 7.4 wt.%, at least 7.4 wt.%, at least 7.8 wt.%, at least 8.1 wt.%, at least 8.4 wt.%, at least 8.7 wt.%, at least 9 wt.%, or at least 9.2 wt.%, based on the total weight of the amorphous phase. In certain cases, the amorphous phase may contain even higher contents of CaO, for example at least 10% by weight, for example at least 13% by weight, at least 15% by weight, at least 18% by weight, at least 20% by weight, at least 22% by weight, or even at least 25% by weight, based on the total weight of the amorphous phase. According to yet another embodiment, the amorphous phase may contain a content of CaO of 50% by weight or less, for example 90% by weight or less, 85% by weight or less, 40% by weight or less, 35% by weight or less, 30% by weight or less, 25% by weight or less, or even 20% by weight or less, based on the total weight of the amorphous phase.In certain cases, the amorphous phase can include a calcium oxide content of 14 wt% or less, based on the total weight of the amorphous phase, e.g., 13 wt% or less, 12 wt% or less, 11 wt% or less, 10 wt% or less, 9 wt% or less, 8.9 wt% or less, 8.8 wt% or less, 8.7 wt% or less, 8.3 wt% or less, 8.1 wt% or less, 7.7 wt% or less, 7.4 wt% or less, 7.2 wt% or less, 7.0 wt% or less, 6.8 wt% or less, 6.5 wt% or less, 6.2 wt% or less, 5.9 wt% or less, 5.7 wt% or less, 5.5 wt% or less, 5.1 wt% or less, 4.9 wt% or less, 4.6 wt% or less, 4.3 wt% or less, 4.0 wt% or less, or 3.8 wt% or less, based on the total weight of the amorphous phase. It will be appreciated that the content of CaO in the amorphous phase may be any value between any of the maximum and minimum values set forth above. It will be further appreciated that the content of CaO in the amorphous phase may be any value within a range between any of the maximum and minimum values set forth above.
[0124] In one embodiment, the amorphous phase may include a specific content of barium oxide (BaO) that may facilitate the formation of a refractory having improved properties and / or performance. According to yet another specific embodiment, the amorphous phase of the zircon body may include a specific content of BaO, which may be measured using scanning electron microscopy with energy dispersive X-ray spectroscopy or scanning electron microscopy with wavelength dispersive X-ray spectroscopy. For example, the amorphous phase may include more than 0.1 wt.% BaO, relative to the total weight of the amorphous phase, such as at least 0.5 wt.%, at least 0.7 wt.%, at least 0.9 wt.%, at least 1.1 wt.%, at least 1.3 wt.%, at least 1.5 wt.%, at least 1.8 wt.%, at least 2 wt.%, at least 2.2 wt.%, at least 2.8 wt.%, at least 3 wt.%, at least 3.3 wt.%, at least 3.7 wt.%, at least 3.9 wt.%, at least 4.0 ... The amorphous phase may comprise a barium oxide content of 0%, at least 4.2%, at least 4.6%, at least 5%, at least 5.1%, at least 5.8%, at least 6.3%, at least 6.5%, at least 7%, at least 8.0%, at least 9%, at least 10%, at least 10.4%, at least 10.9%, at least 11%, at least 11.4%, at least 11.6%, or at least 11.8% by weight. In certain cases, the amorphous phase may comprise a higher content of BaO, for example, at least 13%, at least 15%, at least 18%, at least 20%, at least 22%, or even at least 25% by weight of BaO, based on the total weight of the amorphous phase. According to yet another embodiment, the amorphous phase may comprise a BaO content of 50% by weight or less, such as 90% by weight or less, 85% by weight or less, 40% by weight or less, 35% by weight or less, 30% by weight or less, 25% by weight or less, or even 20% by weight or less, relative to the total weight of the amorphous phase.In certain examples, the amorphous phase comprises 14 wt% or less, based on the total weight of the amorphous phase, e.g., 13 wt% or less, 12 wt% or less, 11.8 wt% or less, 11.4 wt% or less, 10.9 wt% or less, 9.8 wt% or less, 9.3 wt% or less, 8.9 wt% or less, 8.3 wt% or less, 8.1 wt% or less, 7.7 wt% or less, 7.4 wt% or less, 7.2 wt% or less, 7.0 wt% or less, 6.8 wt% or less, based on the total weight of the amorphous phase. % or less, 6.5 wt. % or less, 6.2 wt. % or less, 5.9 wt. % or less, 5.7 wt. % or less, 5.5 wt. % or less, 5.1 wt. % or less, 4.9 wt. % or less, 4.6 wt. % or less, 4.3 wt. % or less, 4.1 wt. % or less, 3.9 wt. % or less, 3.6 wt. % or less, 3.2 wt. % or less, 2.9 wt. % or less, 2.5 wt. % or less, 2.3 wt. % or less, 2.0 wt. % or less, 1.5 wt. % or less, 1.1 wt. % or less of barium oxide. It will be understood that the content of BaO in the amorphous phase can be any value between any of the maximum and minimum values recited above. It will be further understood that the content of BaO in the amorphous phase can be any value within a range between any of the maximum and minimum values recited above.
[0125] In one embodiment, the amorphous phase may include a specific content of magnesium oxide (MgO) that may facilitate the formation of a refractory with improved properties and / or performance. According to yet another specific embodiment, the amorphous phase of the zircon body may include a specific content of MgO, which may be measured using scanning electron microscopy with energy dispersive X-ray spectroscopy or scanning electron microscopy with wavelength dispersive X-ray spectroscopy. For example, the amorphous phase may include a content of MgO of at least 0.01% by weight, relative to the total weight of the amorphous phase, such as at least 0.05% by weight, at least 0.1% by weight, at least 0.2% by weight, at least 0.5% by weight, at least 0.7% by weight, or at least 0.9% by weight, relative to the total weight of the amorphous phase. According to yet another embodiment, the amorphous phase may comprise a content of MgO of less than 4.5% by weight, for example, 4% or less, 3.5% or less, 3% or less, 2.5% or less, 2% or less, 1.5% or less, 1% or less, 0.8% or less, 0.6% or less, 0.4% or less, 0.3% or less, 0.25% or less, 0.2% or less, 0.1% or less, or even 0.05% or less by weight, based on the total weight of the amorphous phase. In certain examples, the amorphous phase may be essentially free of MgO. It will be appreciated that the content of MgO in the amorphous phase may be any value between any of the maximum and minimum values listed above. It will be further appreciated that the content of MgO in the amorphous phase may be any value within a range between any of the maximum and minimum values listed above.
[0126] In one embodiment, the amorphous phase may include a specific content of strontium oxide (SrO) that may facilitate the formation of a refractory having improved properties and / or performance. According to yet another particular embodiment, the amorphous phase of the zircon body may include a specific content of SrO that may be measured using scanning electron microscopy with energy dispersive x-ray spectroscopy or scanning electron microscopy with wavelength dispersive x-ray spectroscopy. For example, the amorphous phase may comprise more than 0.1 wt.% SrO, relative to the total weight of the amorphous phase, e.g., a strontium oxide content of at least 0.5 wt.%, at least 0.7 wt.%, at least 0.9 wt.%, at least 1.1 wt.%, at least 1.3 wt.%, at least 1.5 wt.%, at least 1.8 wt.%, at least 2 wt.%, at least 2.2 wt.%, at least 2.8 wt.%, at least 3 wt.%, at least 3.3 wt.%, at least 3.7 wt.%, at least 4.2 wt.%, at least 4.6 wt.%, at least 5 wt.%, at least 5.1 wt.%, at least 5.8 wt.%, at least 6.3 wt.%, at least 6.5 wt.%, at least 7 wt.%, at least 8.0 wt.%, at least 9 wt.%, at least 9.3 wt.%, at least 9.6 wt.%, at least 10 wt.%, or at least 10.4 wt.%, relative to the total weight of the amorphous phase. In certain cases, the amorphous phase may contain even higher contents of SrO, for example, at least 13 wt.%, at least 15 wt.%, at least 18 wt.%, at least 20 wt.%, at least 22 wt.%, or even at least 25 wt.% SrO, based on the total weight of the amorphous phase. According to yet another embodiment, the amorphous phase may contain a content of SrO of 50 wt.% or less, for example, 90 wt.%, 85 wt.%, 40 wt.%, 35 wt.%, 30 wt.%, 25 wt.%, or even 20 wt.% or less, based on the total weight of the amorphous phase.In certain examples, the amorphous phase has 14 wt.% or less strontium oxide, based on the total weight of the amorphous phase, e.g., 13 wt.% or less, 12 wt.% or less, 11 wt.% or less, 10.4 wt.% or less, 10.0 wt.% or less, 9 wt.% or less, 8.9 wt.% or less, 8.8 wt.% or less strontium oxide, based on the total weight of the amorphous phase, 8.7 wt.% or less, 8.3 wt.% or less, 8.1 wt.% or less, 7.7 wt.% or less, 7.4 wt.% or less, 7.2 wt.% or less, 7 ... 0.0%, 6.8%, 6.5%, 6.2%, 5.9%, 5.7%, 5.5%, 5.1%, 4.9%, 4.6%, 4.3%, 4.0%, 3.5%, 3.1%, 2.9%, 2.5%, 2.3%, 2.0%, 1.5%, or 1.1% by weight of strontium oxide. It will be appreciated that the content of SrO in the amorphous phase may be any value between any of the maximum and minimum values listed above. It will be further appreciated that the content of SrO in the amorphous phase may be any value within a range between any of the maximum and minimum values listed above.
[0127] In another embodiment, the amorphous phase may include a particular content of tantalum oxide (Ta2O5) that may facilitate improved formation of the zircon body and improved properties and / or performance of the zircon body. For example, the amorphous phase may include tantalum oxide of 12 wt% or less, based on the total weight of the amorphous phase, e.g., tantalum oxide of 11.7 wt% or less, 11.5 wt% or less, 11.3 wt% or less, 11.1 wt% or less, 10.9 wt% or less, 10.6 wt% or less, 10.3 wt% or less, 10.0 wt% or less, 9.6 wt% or less, based on the total weight of the amorphous phase. tantalum oxide, 9.3 wt.% or less tantalum oxide, 9.1 wt.% or less tantalum oxide, 8.8 wt.% or less tantalum oxide, 8.5 wt.% or less tantalum oxide, 8.2 wt.% or less tantalum oxide, 7.9 wt.% or less tantalum oxide, 7.5 wt.% or less tantalum oxide, 7.1 wt.% or less tantalum oxide, 6.8 wt.% or less tantalum oxide, 6.5 wt.% or less tantalum oxide, or 6.3 wt.% or less tantalum oxide. In another example, the amorphous phase comprises at least 6.0 wt. % tantalum oxide, based on the total weight of the amorphous phase; e.g., at least 6.3 wt. % alkaline earth oxide, at least 6.5 wt. % tantalum oxide, at least 6.8 wt. % alkaline earth oxide, at least 7.0 wt. % tantalum oxide, at least 7.3 wt. % tantalum oxide, at least 7.5 wt. % alkaline earth oxide, at least 7.7 wt. % alkaline earth oxide, at least 7.9 wt. % alkaline earth oxide, at least 8.3 wt. % tantalum oxide, based on the total weight of the amorphous phase. It may comprise a content of at least 8.5 wt.% tantalum oxide, at least 8.7 wt.% tantalum oxide, at least 9.0 wt.% tantalum oxide, at least 9.3 wt.% tantalum oxide, at least 9.5 wt.% tantalum oxide, at least 9.8 wt.% tantalum oxide, at least 10.0 wt.% tantalum oxide, at least 10.3 wt.% tantalum oxide, at least 10.5 wt.% tantalum oxide, at least 10.7 wt.% tantalum oxide, at least 11.0 wt.% tantalum oxide, or even at least 11.1 wt.% tantalum oxide.It will be appreciated that the total tantalum oxide content, in weight percent, relative to the total weight of the amorphous phase, can be any value between any of the minimum and maximum values listed above. It will be further appreciated that the tantalum oxide content, in weight percent, relative to the total weight of the amorphous phase, can be within a range between any of the minimum and maximum values listed above. For example, the amorphous phase can include tantalum oxide in a content of 6.0 wt. % to 12.0 wt. %, or 6.3 wt. % to 11.1 wt. %, relative to the total weight of the amorphous phase.
[0128] According to yet other embodiments, the zircon grains in the zircon body may have a particular average grain size. For example, the zircon grains may have an average grain size of at least 3 μm, such as at least 4 μm, at least 5 μm, at least 6 μm, at least 7 μm, at least 8 μm, at least 9 μm, at least 10 μm, at least 12 μm, or even at least 14 μm. According to yet other embodiments, the zircon grains may have an average grain size of 44 μm or less, 30 μm or less, 20 μm or less, 15 μm or less, or even 10 μm or less. It will be appreciated that the zircon grains in the zircon body may have an average grain size of any value between any of the maximum and minimum values recited above. It will be further appreciated that the zircon grains in the zircon body may have an average grain size within a range between any of the maximum and minimum values recited above.
[0129] According to yet another embodiment, the zircon body may include a specific content of apparent porosity. The apparent porosity may be measured using ASTM C20. For example, the zircon body may include an apparent porosity of at least 0.1 vol.%, e.g., at least 0.5 vol.%, at least 1.0 vol.%, at least 1.5 vol.%, at least 2.0 vol.%, at least 2.5 vol.%, at least 3.0 vol.%, at least 3.5 vol.%, at least 4.0 vol.%, at least 4.5 vol.%, at least 5.0 vol.%, at least 6 vol.%, at least 7 vol.%, at least 8 vol.%, at least 9 vol.%, at least 10 vol.%, at least 11 vol.%, at least 12 vol.%, at least 13 vol.%, or even at least 14 vol.%, based on the total volume of the zircon body. According to yet other embodiments, the zircon body may include an apparent porosity of 15 vol.% or less, e.g., 14 vol.% or less, 13 vol.% or less, 12 vol.% or less, 11 vol.% or less, 10 vol.% or less, 9 vol.% or less, 8 vol.% or less, 7 vol.% or less, 6 vol.% or less, 5 vol.% or less, 4.5 vol.% or less, 4.0 vol.% or less, 3.5 vol.% or less, 3.0 vol.% or less, 2.5 vol.% or less, 2.0 vol.% or less, 1.5 vol.% or less, 1.0 vol.% or less, and 0.5 vol.% or less, based on the total volume of the zircon body. It will be understood that the zircon body may have an apparent porosity of any value between any of the maximum and minimum values listed above. It will be further understood that the zircon body may have an apparent porosity of any value within a range between any of the maximum and minimum values listed above.
[0130] Another particular embodiment of a refractory article formed as described herein can include a zircon body, which can include zircon grains, and can have an outer portion and an inner portion. The intersection of the outer portion and the inner portion can be measured at a depth of 5000 μm from the outer surface of the body. The outer portion of the body can have an apparent porosity (P op ), and the interior portion of the body may have an apparent porosity (P ip ).
[0131] Apparent porosity can be measured using ASTM C20. In certain embodiments, P op and P ip can be substantially similar. For example, P op and P ip may have a difference of 25 vol.% or less, e.g., 20 vol.% or less, 15 vol.% or less, 10 vol.% or less, 5 vol.% or less, 4 vol.% or less, 3 vol.% or less, or 2 vol.% or less. op and P ip may have a difference of at least 1 vol.%, e.g., at least 2 vol.%, at least 3 vol.%, at least 4 vol.%, at least 5 vol.%, or at least 9 vol.%. op and P ip It will be appreciated that the apparent porosity difference between can be any value between any of the maximum and minimum values listed above. op and P ip It will be further understood that the apparent porosity difference between may be any value within a range between any of the maximum and minimum values recited above.
[0132] According to yet another embodiment, the zircon body has an apparent porosity (P op ) of the inner part of the body (P ip ) which can be mathematically expressed as P op / P ip It can be expressed as P op may represent the apparent porosity of the outer portion of the zircon body measured in volume percent. ip may represent the apparent porosity of the interior portion of the body measured in volume percent. In certain embodiments, the body has an apparent porosity ratio P of 1.9 or less, e.g., 1.8 or less, 1.7 or less, 1.6 or less, 1.5 or less, 1.4 or less, 1.3 or less, 1.2 or less, or even 1.1 or less. op / P ip In other embodiments, the body may have an apparent porosity ratio P of about 1. op / P ipIn yet other embodiments, the body may include an apparent porosity ratio P of at least 0.8, such as at least 0.85, at least 0.9, or even at least 0.95. op / P ip The porosity ratio P op / P ip It will be appreciated that the porosity ratio P can be any value between any of the above maximum and minimum values. op / P ip It will be further understood that can be any value within a range between any of the maximum and minimum values listed above.
[0133] According to yet other embodiments, the zircon bodies formed according to the methods described herein may have a particular density. The density (D) may be determined using apparent specific gravity according to ASTM C20. In one embodiment, the zircon bodies have a density, or density of at least 3.7 g / cm. 3 , e.g., 3.8 g / cm 3 , 3.9g / cm 3 , 4.0g / cm 3 , 4.1g / cm 3 , at least 4.2 g / cm 3 , at least 4.3 g / cm 3 , or even at least 4.4 g / cm 3 In yet other instances, the zircon body may have a density of 4.5 g / cm 3 For example, 4.4 g / cm 3 Below, 4.3g / cm 3 Below, 4.2g / cm 3 Below, 4.1g / cm 3 Below, 4.0g / cm 3 Below, 3.9g / cm 3 Below, 3.8g / cm 3 Less than or equal to 3.7 g / cm 3 It may have the following densities: It will be understood that the density may be any value between any of the maximum and minimum values listed above It will be further understood that the density may be any value within a range between any of the minimum and maximum values listed above.
[0134] According to yet other embodiments, the zircon bodies formed according to the methods described herein may have a particular creep deformation rate for a particular temperature, which may be measured using an isothermal four-point creep test.
[0135] In a four-point isothermal creep test, a four-point bending test configuration is used, where two outer supports are positioned under the specimen and two inner load members apply a force to the top of the specimen. The distance L between the outer supports may be 80 mm and the distance l between the inner load members may be 40 mm. The specimen bar may have a height "a" of 8 mm, a width "b" of 9 mm, and a length of 100 mm. During the test, the specimen bar may be positioned on the support members and the load members may apply a stress of 2 MPa to the specimen bar. The test may be performed in a heating chamber. The temperature of the heating chamber during the test may be maintained at a set test temperature, for example, a temperature of 1350°C, 1325°C, 1300°C, or 1275°C, for a total test time of 12 to 48 hours. The instantaneous deformation of the specimen in millimeters (mm) may be measured during the test using an LVDT in contact with the bottom surface of the specimen. The reference displacement is subtracted from the instantaneous displacement to provide the specific specimen displacement during the test. The specimen displacement can then be used to calculate the creep deformation rate per hour (i.e., creep deformation rate). def is the specific sample displacement rate "R disp " is derived from the following formula: R def =R disp .12.a / (3.L 2 -(Ll)) 2
[0136] According to certain embodiments, the zircon body formed according to the methods described herein may have a particular creep deformation rate as measured using a four-point bend test at a temperature of 1350° C. under an applied stress of 2 MPa. For example, the zircon body may have a creep deformation rate of 3.0E-5h as measured using a four-point bend test at a temperature of 1350° C. under an applied stress of 2 MPa. -1 Less than, for example, 2.5E-5h -1Below, 2.2E-5h -1 Below, 1.8E-5h -1 Below, 1.5E-5h -1 Below, 1.2E-5h -1 Below, 1E-5h -1 Below, 9.5E-6h -1. Below, 9E-6h -1. Below, 8E-6h -1. Below, or 7E-6h -1 In another example, the zircon body may have a creep deformation rate of at least 0.5E-6h when measured using a four-point bend test at a temperature of 1350°C under an applied stress of 2 MPa. -1. , at least 1E-6h -1. , or at least 1.5E-6h -1. In a further example, the zircon body may have a creep deformation rate within a range including any of the minimum and maximum values described herein, as measured using a four-point bending test at a temperature of 1350° C. under an applied stress of 2 MPa.
[0137] According to another embodiment, the zircon body formed according to the methods described herein may have a particular creep deformation rate as measured using a four-point bend test under an applied stress of 2 MPa and a temperature of 1325° C. For example, in another example, the zircon body may have a creep deformation rate of about 8.8E-6 h as measured using a four-point bend test under an applied stress of 2 MPa and a temperature of 1325° C. -1 Less than, for example, 8.5E-6h -1 Below, 8E-6h -1 Below, 7.5E-6h -1 Below, 7E-6h -1. Below, or 6.5E-6h -1 Below, 6E-6h -1 Below, 5.5E-6h -1 Below, 5E-6h -1 Below, 4.5E-6h -1 Below, 4.3E-6h -1 Below, 4E-6h -1 Below, 3.5E-6h -1 Below, or 3E-6h -1In another example, the zircon body may have a creep deformation rate of at least 0.05E-6h when measured using a four-point bend test at a temperature of 1325°C under an applied stress of 2 MPa. -1. , at least 0.5E-6h -1. , or at least 0.75E-6h -1. In a further example, the zircon body may have a creep deformation rate within a range including any of the minimum and maximum values described herein, as measured using a four-point bending test at a temperature of 1325° C. under an applied stress of 2 MPa.
[0138] According to yet another embodiment, the zircon body formed according to the methods described herein may have a particular creep deformation rate as measured using a four-point bend test under an applied stress of 2 MPa and a temperature of 1300° C. For example, the zircon body may have a creep deformation rate of 1.5E-5h as measured using a four-point bend test under an applied stress of 2 MPa and a temperature of 1300° C. -1 Less than, for example, 4.5E-6h -1 Below, 4E-6h -1 Below, 3.5E-6h -1 Below, 3E-6h -1 Below, 2.5E-6h -1 Below, 2.2E-6h -1 Below, 2E-6h -1 Below, 1.8E-6h -1 Below, 1.5E-6h -1 Below, 1.2E-6h -1 In another example, the zircon body may have a creep deformation rate of at least 0.05E-6h when measured using a four-point bend test at a temperature of 1300° C. under an applied stress of 2 MPa. -1. , at least 0.1E-6h -1. , at least 0.3E-6h -1. , or at least 0.5E-6h -1.In a further example, the zircon body may have a creep deformation rate within a range including any of the minimum and maximum values described herein, as measured using a four-point bending test at a temperature of 1300° C. under an applied stress of 2 MPa.
[0139] According to yet another embodiment, the zircon body formed according to the methods described herein may have a particular creep deformation rate as measured using a four-point bend test at a temperature of 1275° C. under an applied stress of 2 MPa. For example, the zircon body may have a creep deformation rate of 4.0E-6h as measured using a four-point bend test at a temperature of 1275° C. under an applied stress of 2 MPa. -1 Less than, for example, 3.5E-6h -1 In a particular example, the zircon body may have a creep deformation rate of 2.7E-6h when measured using a four-point bend test at a temperature of 1275°C under an applied stress. -1 Less than 2.6E-6h -1 Below, 2.5E-6h -1 Below, 2.4E-6h -1 Below, 2.53E-6h -1 Below, 2.2E-6h -1 Below, 2.1E-6h -1 Below, 1.9E-6h -1 Below, 1.7E-6h -1 Below, 1.5E-6h -1 Below, 1.3E-6h -1 Below, or 1.1E-6h -1 In another example, the zircon body may have a creep deformation rate of at least 0.005E-6h when measured using a four-point bend test at a temperature of 1275°C under an applied stress of 2 MPa. -1. , at least 0.008E-6h -1. , at least 0.01E-6h -1. , at least 0.03E-6h -1. , at least 0.05E-6h -1. , at least 0.08E-6h -1. , or at least 0.1E-6h -1.In a further example, the zircon body may have a creep deformation rate within a range including any of the minimum and maximum values described herein, as measured using a four-point bending test at a temperature of 1275° C. under an applied stress of 2 MPa.
[0140] According to yet another embodiment, the zircon bodies formed according to the methods described herein may have a particular blister value as measured using short-term or long-term blister tests performed using glasses referred to as LTPS glasses. LTPS glasses are commercially available alkali-free boroaluminosilicate glass substrates used in the manufacture of AMLCD displays. LTPS glasses 1 and 2 have a density of 2.4-2.7 g / cc and a strain point of 650-800° C.
[0141] For short-term plaque blister testing, square or cylindrical specimens were prepared. Square specimens may have a length and width of 1 inch and a thickness of 1 / 4 inch. Cylindrical specimens may have a diameter of 1 inch and a thickness of 1 / 4 inch. The faces of the specimens may be ground with a surface finish of 30 microns, cleaned in an ultrasonic bath, and dried. A glass sheet (i.e., LTPS glasses 1 and 2) may be placed on the surface of the specimen, and the specimen may be heated at 5°C / min to the test temperature of 1300°C. The specimen may be held at the test temperature for 8 hours and then rapidly cooled to room temperature at at least 10°C / min to avoid devitrification of the glass. The specimen may then be cut in half and the cross section may be polished to 1 micron. The cross section may then be observed using a stereo microscope or binocular microscope, and the number of bubbles visible at a depth of 500 microns in the glass may be counted in a cross section of 3000 microns along the interface. The number of bubbles can then be divided by 1.5 to give the number of bubbles per square mm at the interface between the sample and the glass.
[0142] For the long-term crucible bulge test, a crucible is cored from a sample block. The crucible may have a height of 40 mm and a diameter of 50 mm, with a hole in the center of the crucible having a height of 30 mm and a diameter of 30 mm. After preparation, the crucible can be cleaned using DI water in an ultrasonic bath to eliminate any possible residues from machining and then dried. After drying, the crucible can be filled with 20 g of glass (i.e., LTPS1 and 2 glasses) shards and then heated to the test temperature and soaked for an extended period of time (72 hours, 120 hours, or 360 hours). After soaking is completed, the crucible is cooled to room temperature. The crucible is then cut vertically to expose the glass and observe the bulge strength. In the long term crucible bulge test, materials are tested in LTPS1 and 2 glasses at 1300°C for 360 hours. A stereo microscope or binocular microscope can then be used to view the cross section and count the number of bubbles visible at a depth of 500 microns into the glass in a 3000 micron cross section along the interface. The number of bubbles can then be divided by 1.5 to give the number of bubbles per square mm at the interface between the sample and the glass.
[0143] According to certain embodiments, the zircon bodies formed according to the methods described herein may have particular blister values as measured using the short-term plaque blister test for LTPS1 and 2 glasses.
[0144] According to yet another embodiment, the zircon body formed according to the methods described herein may have a particular blister value as measured using the Long Term Crucible Blister Test for LTPS 1 and 2 glasses after 360 hours of exposure to a temperature of 1300° C. For example, the blister value as measured using the Long Term Crucible Blister Test for LTPS 1 and 2 glasses after 360 hours may be greater than 1 mm 2 There may be no more than one bubble per bubble.
[0145] Notably, blister values in refractory materials including zircon formed according to embodiments described herein were determined to be lower as compared to conventional zircon-based materials formed according to conventional methods.
[0146] Many different aspects and embodiments are possible. Some of these aspects and embodiments are described below. After reading this specification, a person skilled in the art will understand that these aspects and embodiments are merely examples and do not limit the scope of the present invention. An embodiment can be according to any one or more of the embodiments listed below.
[0147] Embodiment Embodiment 1. A refractory comprising a zircon body, the zircon body comprising a first crystalline phase comprising an alkaline earth metal element.
[0148] Embodiment 2: Approximately 1.8E-5 hours at a temperature of 1350°C and a stress of 2 MPa -1 A refractory comprising a zircon body having a creep deformation rate of:
[0149] Embodiment 3. Approximately 2.7E-6 hours at a temperature of 1275°C and a stress of 2 MPa -1 1. A refractory comprising a zircon body having a creep deformation rate of less than 100 nm.
[0150] Embodiment 4. Approximately 8.8E-6 hours at a temperature of 1325°C and a stress of 2 MPa -1 1. A refractory comprising a zircon body having a creep deformation rate of less than 100 nm.
[0151] Embodiment 5. Approximately 4.5E-6 hours at a temperature of 1300°C and a stress of 2 MPa -1 1. A refractory comprising a zircon body having a creep deformation rate of less than 100 nm.
[0152] Embodiment 6. The refractory material according to any one of embodiments 1 to 5, wherein the zircon body comprises a first crystalline phase comprising an alkali metal element comprising at least one of Ca, Mg, Sr, and Ba.
[0153] Embodiment 7. The refractory material of embodiment 6, wherein the first crystalline phase further comprises Al, Si, or a combination thereof.
[0154] Embodiment 8. The refractory material of any one of embodiments 1-5, wherein the zircon body comprises a first crystalline phase comprising calcium aluminosilicate, barium aluminosilicate, magnesium aluminosilicate, strontium aluminosilicate, or a combination thereof.
[0155] Embodiment 9. The refractory material of any one of embodiments 1-5, wherein the zircon body comprises a first crystalline phase comprising feldspar-type crystals.
[0156] Embodiment 10. The zircon body is made of gehlenite (CaAlSiO), prehnite (CaAl[AlSiO] and CaAl(AlSiO 10 6. The refractory material according to any one of the preceding claims, comprising: SiO2 (CaAl2Si2O8), anorthite (CaAl2Si2O8), celsian (BaAl2Si2O8), or any combination thereof.
[0157] Embodiment 11. The refractory of any one of embodiments 1-5, wherein the zircon body comprises a first crystalline phase comprising at least 0.01 wt.%, based on the total weight of the zircon body, at least 0.05 wt.%, at least 0.1 wt.%, at least 0.2 wt.%, at least 0.3 wt.%, at least 0.4 wt.%, at least 0.5 wt.%, at least 0.6 wt.%, at least 0.7 wt.%, at least 0.8 wt.%, at least 0.9 wt.%, at least 1 wt.%, at least 2 wt.%, or at least 3 wt.%, at least 4 wt.%, at least 5 wt.%, or at least 6 wt.% alkaline earth metal based on the total weight of the zircon body.
[0158] Embodiment 12. The refractory material of any one of embodiments 1-5, wherein the zircon body comprises a first crystalline phase comprising 20% or less by weight, based on the total weight of the zircon body, 18% or less by weight, 16% or less by weight, 14% or less by weight, 12% or less by weight, 10% or less by weight, 8% or less by weight, 6% or less by weight, 5% or less by weight, 4% or less by weight, 3% or less by weight, 2% or less by weight, or 1% or less by weight of an alkaline earth metal based on the total weight of the zircon body.
[0159] Embodiment 13. The refractory material of any one of embodiments 1 to 5, wherein the zircon body comprises a second crystalline phase comprising tantalum, iron, titanium, or any combination thereof, and the second crystalline phase is a tantalum-iron-titania rich crystalline phase.
[0160] Embodiment 14. The refractory material of embodiment 13, wherein the zircon body comprises at least 0.01 wt.%, based on the total weight of the zircon body, at least 0.05 wt.%, at least 0.1 wt.%, at least 0.2 wt.%, at least 0.3 wt.%, at least 0.4 wt.%, at least 0.5 wt.%, at least 0.6 wt.%, at least 0.7 wt.%, at least 0.8 wt.%, at least 0.9 wt.%, at least 1 wt.%, at least 1.5 wt.%, at least 2 wt.%, at least 2.5 wt.%, at least 3 wt.%, at least 3.5 wt.%, at least 4 wt.%, at least 4.5 wt.%, or at least 5 wt.% of the second crystalline phase based on the total weight of the zircon body.
[0161] Embodiment 15. The refractory material of embodiment 13 or 14, wherein the zircon body comprises 20% or less by weight, based on the total weight of the zircon body, 18% or less by weight, 16% or less by weight, 14% or less by weight, 12% or less by weight, 10% or less by weight, 8% or less by weight, 6% or less by weight, 5% or less by weight, 4% or less by weight, 3% or less by weight, or 2% or less by weight of the second crystalline phase based on the total weight of the zircon body.
[0162] Embodiment 16. The refractory material according to any one of embodiments 1 to 5, wherein the zircon body comprises an amorphous phase comprising Si, Al, Ta, an alkaline earth metal element, or any combination thereof.
[0163] Embodiment 17. The refractory material of embodiment 16, wherein the zircon body comprises at least 0.5 wt.%, at least 0.8 wt.%, at least 1 wt.%, at least 1.5 wt.%, at least 1.8 wt.%, at least 2 wt.%, at least 2.5 wt.%, at least 3 wt.%, at least 4 wt.%, or at least 5 wt.% amorphous phase based on the total weight of the zircon body.
[0164] Embodiment 18. The refractory material of embodiment 16 or 17, wherein the zircon body comprises 20% or less by weight, based on the total weight of the zircon body, 18% or less by weight, 16% or less by weight, 14% or less by weight, 12% or less by weight, 10% or less by weight, 8% or less by weight, 6% or less by weight, 5% or less by weight, 4% or less by weight, 3% or less by weight, or 2% or less by weight of amorphous phase based on the total weight of the zircon body.
[0165] Embodiment 19. The refractory material according to embodiment 16, wherein the amorphous phase comprises, based on the total weight of the amorphous phase, 40% to 60% by weight of Si, or 48% to 58% by weight of Si, 10% to 30% by weight of Al, or 15% to 25% by weight of Al, based on the total weight of the amorphous phase, 0.5% to 15% by weight of an alkaline earth metal element, or 2% to 9% by weight of an alkaline earth metal element, based on the total weight of the amorphous phase, and 0.3% to 12% by weight of Ta, or 1% to 7% by weight of Ta, based on the total weight of the amorphous phase.
[0166] Embodiment 20. The refractory material of embodiment 16, wherein the first crystalline phase, the second crystalline phase, or both, are within an amorphous phase.
[0167] Embodiment 21. The refractory material of any one of embodiments 1-5, wherein the zircon body comprises a third crystalline phase comprising mullite, and the third crystalline phase consists essentially of mullite.
[0168] Embodiment 22. The refractory material of embodiment 21, wherein the zircon body comprises at least 0.01% by weight, based on the total weight of the zircon body, at least 0.05% by weight, at least 0.1% by weight, at least 0.2% by weight, at least 0.3% by weight, at least 0.4% by weight, at least 0.5% by weight, at least 0.6% by weight, at least 0.7% by weight, at least 0.8% by weight, at least 0.9% by weight, at least 1% by weight, at least 1.5% by weight, at least 2% by weight, at least 2.5% by weight, at least 3% by weight, at least 3.5% by weight, at least 4% by weight, at least 4.5% by weight, or at least 5% by weight of a third crystalline phase.
[0169] Embodiment 23. The refractory material of embodiment 21 or 22, wherein the zircon body comprises 20% or less by weight, based on the total weight of the zircon body, 18% or less by weight, 16% or less by weight, 14% or less by weight, 12% or less by weight, 10% or less by weight, 8% or less by weight, 6% or less by weight, 5% or less by weight, or 4% or less by weight, based on the total weight of the zircon body.
[0170] Embodiment 24. The refractory material of any one of embodiments 1-5, wherein the zircon body includes a fourth crystalline phase comprising zircon, the fourth crystalline phase consisting essentially of zircon.
[0171] Embodiment 25. The refractory material of embodiment 24, wherein the zircon body comprises at least 50% by weight, based on the total weight of the zircon body, at least 60% by weight, at least 70% by weight, at least 75% by weight, at least 80% by weight, at least 85% by weight, at least 90% by weight, or at least 93% by weight, based on the total weight of the zircon body.
[0172] Embodiment 26. The refractory material of embodiment 24 or 25, wherein the zircon body comprises 99.5% or less by weight of a fourth crystalline phase, based on the total weight of the zircon body, 99% or less by weight, 98% or less by weight, 97% or less by weight, 96% or less by weight, 95% or less by weight, or 94% or less by weight, based on the total weight of the zircon body.
[0173] Embodiment 27. The refractory material of any one of embodiments 1-5, wherein the zircon body comprises a fifth crystalline phase comprising zirconia, the fifth crystalline phase consisting essentially of zirconia.
[0174] Embodiment 28. The refractory material of embodiment 27, wherein the zircon body comprises at least 0.01 wt.%, based on the total weight of the zircon body, at least 0.03 wt.%, at least 0.05 wt.%, at least 0.1 wt.%, at least 0.2 wt.%, at least 0.3 wt.%, at least 0.4 wt.%, at least 0.5 wt.%, at least 0.6 wt.%, at least 0.7 wt.%, at least 0.8 wt.%, at least 0.9 wt.%, or at least 1 wt.% of a fifth crystalline phase based on the total weight of the zircon body.
[0175] Embodiment 29. The refractory material of embodiment 27 or 28, wherein the zircon body comprises 15% or less by weight, based on the total weight of the zircon body, 12% or less by weight, 10% or less by weight, 9% or less by weight, 8% or less by weight, 7% or less by weight, 6% or less by weight, 5% or less by weight, 4% or less by weight, 3% or less by weight, or 2% or less by weight of a fifth crystalline phase based on the total weight of the zircon body.
[0176] Embodiment 30. The refractory material of any one of embodiments 1 to 5, wherein the zircon body comprises alkaline earth oxides, and the total alkaline earth oxide content is at least 0.02 wt. % and not more than 8 wt. %, based on the total weight of the zircon body.
[0177] Embodiment 31. The refractory material of any one of embodiments 1-5, wherein the zircon body comprises at least 0.1 wt. % of an alumina (Al2O3)-containing component, based on the total weight of the zircon body, at least 0.3 wt. %, at least 0.5 wt. %, at least 0.8 wt. %, or at least 1 wt. % of an alumina-containing component, based on the total weight of the zircon body.
[0178] Embodiment 32. The refractory material of any one of embodiments 1-5, wherein the zircon body comprises about 12 wt.% or less of an alumina (Al2O3)-containing component, based on the total weight of the zircon body, 10 wt.% or less of an Al2O3-containing component, 9 wt.% or less, 8 wt.% or less, 7 wt.% or less, or 6 wt.% or less of an alumina-containing component, based on the total weight of the zircon body.
[0179] Embodiment 33. The refractory material of any one of embodiments 1-5, wherein the zircon body comprises at least 0.5 wt.%, at least 1 wt.%, at least 1.2 wt.%, at least 1.5 wt.%, at least 1.8 wt.%, at least 2 wt.%, at least 2.2 wt.%, at least 2.5 wt.%, at least 2.7 wt.%, or at least 3 wt.% mullite, based on the total weight of the zircon body.
[0180] Embodiment 34. The refractory material of any one of embodiments 1-5, wherein the zircon body comprises 10 wt.% or less, 9 wt.% or less, 8 wt.% or less, 7 wt.% or less, 6 wt.% or less, 5 wt.% or less, 4 wt.% or less, 3.8 wt.% or less, 3.5 wt.% or less, 3.2 wt.% or less, or 3 wt.% or less of mullite, based on the total weight of the zircon body.
[0181] Embodiment 35. The refractory material of any one of embodiments 1 to 5, wherein the zircon body comprises at least 70 wt.%, at least 75 wt.%, at least 80 wt.%, at least 85 wt.%, at least 90 wt.%, or at least 93 wt.% zircon, based on the total weight of the zircon body.
[0182] Embodiment 36. The refractory material of any one of embodiments 1 to 5, wherein the zircon body comprises 99.5% by weight or less, 99% by weight or less, 98% by weight or less, 97% by weight or less, or 95% by weight or less of zircon, based on the total weight of the zircon body.
[0183] Embodiment 37. The refractory material of any one of embodiments 1 to 5, wherein the zircon body comprises at least 0.05 wt.%, at least 0.1 wt.%, at least 0.2 wt.%, at least 0.3 wt.%, or at least 0.5 wt.% Ta2O5, based on the total weight of the zircon body.
[0184] Embodiment 38. The refractory material of any one of embodiments 1-5, wherein the zircon body comprises 5 wt.% or less, 4 wt.% or less, 3 wt.% or less, 2 wt.% or less, or 1 wt.% or less of Ta2O5, based on the total weight of the zircon body.
[0185] Embodiment 39. The refractory material of any one of embodiments 1 to 5, wherein the zircon body comprises at least 0.05 wt.%, at least 0.1 wt.%, at least 0.2 wt.%, or at least 0.3 wt.% MgO, based on the total weight of the zircon body.
[0186] Embodiment 40. The refractory material of any one of embodiments 1-5, wherein the zircon body comprises 2 wt. % or less, 1.8 wt. % or less, 1.5 wt. % or less, 1.2 wt. % or less, 1 wt. % or less, 0.5 wt. % or less, or 0.3 wt. % or less MgO.
[0187] Embodiment 41. The refractory material of any one of embodiments 1-5, wherein the zircon body comprises at least 0.02 wt.%, at least 0.05 wt.%, at least 0.08 wt.%, at least 0.1 wt.%, at least 0.2 wt.%, or at least 0.3 wt.% CaO, based on the total weight of the zircon body.
[0188] Embodiment 42. The refractory material of any one of embodiments 1-5, wherein the zircon body comprises 2 wt. % or less, 1.8 wt. % or less, 1.5 wt. % or less, 1.2 wt. % or less, 1 wt. % or less, or 0.7 wt. % or less CaO.
[0189] Embodiment 43. The refractory material of any one of embodiments 1 to 5, wherein the zircon body comprises at least 0.05 wt.%, at least 0.1 wt.%, at least 0.2 wt.%, at least 0.3 wt.%, or at least 0.5 wt.% SrO, based on the total weight of the zircon body.
[0190] Embodiment 44. The refractory material of any one of embodiments 1-5, wherein the zircon body comprises 5 wt.% or less, 4 wt.% or less, 3 wt.% or less, 2 wt.% or less, 1 wt.% or less, or 0.5 wt.% or less SrO, based on the total weight of the zircon body.
[0191] Embodiment 45. The refractory material of any one of embodiments 1-5, wherein the zircon body comprises at least 0.05 wt.%, at least 0.1 wt.%, at least 0.2 wt.%, at least 0.3 wt.%, at least 0.5 wt.%, at least 0.8 wt.%, at least 1 wt.%, or at least 1.2 wt.% BaO, based on the total weight of the zircon body.
[0192] Embodiment 46. The refractory material of any one of embodiments 1-5, wherein the zircon body comprises 5 wt.% or less, 4 wt.% or less, 3 wt.% or less, 2 wt.% or less, or 1.2 wt.% or less BaO, based on the total weight of the zircon body.
[0193] Embodiment 47. A zircon body is subjected to 1.8E-5h at a temperature of 1350°C and a stress of 2MPa. -1 The following is a test performed for 1.5E-5h at a temperature of 1350℃ and a stress of 2MPa. -1 Below, 1.2E-5h -1 Below, 1E-5h -1 Below, 9E-6h -1. Below, or 8E-6h -1 6. The refractory material according to any one of the first to fifth embodiments, comprising the following creep deformation rate:
[0194] Embodiment 48. A zircon body is subjected to a temperature of 1325°C and a stress of 2 MPa for about 8.8E-6 h. -1 Less than 8.5E-6h at 1350℃ and 2MPa stress -1Below, 8E-6h -1 Below, 7.5E-6h -1 Below, 7E-6h -1 Below, or 6.5E-6h -1 Below, 6E-6h -1 Below, 5.5E-6h -1 Below, 5E-6h -1 Below, or 4.5E-6h -1 6. The refractory material according to any one of the first to fifth embodiments, comprising the following creep deformation rate:
[0195] Embodiment 49. A zircon body is subjected to 4.5E-6h at a temperature of 1300°C and a stress of 2MPa. -1 Less than 4E-6h at 1300℃ and 2MPa stress -1 Below, 3.5E-6h -1 Below, or 3E-6h -1 6. The refractory material according to any one of the first to fifth embodiments, comprising the following creep deformation rate:
[0196] Embodiment 50. A zircon body is subjected to 2.7E-6h at a temperature of 1275°C and a stress of 2 MPa. -1 Less than 2.6E-6h at 1275℃ and 2MPa stress -1 Below, 2.5E-6h -1 Below, 2.4E-6h -1 Below, 2.53E-6h -1 Below, or 2.2E-6h -1 6. The refractory material according to any one of the first to fifth embodiments, comprising the following creep deformation rate:
[0197] Embodiment 51. The zircon body has a thickness of about 4.5 g / cm 3 The density includes the following: 3 ~4.5g / cm 3 or 3.8 g / cm 3 ~4.2g / cm 3 The refractory material according to any one of embodiments 1 to 5, wherein the range is
[0198] Embodiment 52. The refractory material of any one of embodiments 1 to 5, wherein the zircon body comprises an apparent porosity of about 15 volume percent or less, relative to the total volume of the zircon body, the apparent porosity being in the range of 1 volume percent to 15 volume percent, or in the range of 3 volume percent to 12 volume percent.
[0199] Embodiment 53. The zircon body is C ZN / C M Including the ratio of C ZN is the content of zircon in weight percent relative to the total weight of the zircon body, and C M is the content of mullite in weight % relative to the total weight of the zircon body, and the ratio is at least 7, at least 8, at least 9, at least 10, at least 11, at least 12, at least 13, at least 14, at least 15, at least 16, at least 17, at least 18, at least 19, at least 20, at least 21, at least 22, at least 23, at least 24, at least 25, at least 26, at least 27, at least 28, at least 29, at least 30, at least 31, at least 32, or at least 33.
[0200] 54. The zircon body is C ZN / C M Including the ratio of C ZN is the content of zircon in weight percent relative to the total weight of the zircon body, and C M is the content of mullite in weight % relative to the total weight of the zircon body, and the ratio is 200 or less, 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 48 or less, 45 or less, 42 or less, 40 or less, 38 or less, 35 or less, 32 or less, or 30 or less.
[0201] Embodiment 55. The zircon body is C C3 / C C1 Including the ratio of C C3 is the content of the third crystalline phase in weight percent relative to the total weight of the zircon body, and C C124. The refractory of embodiment 23, wherein: is the content of the first crystalline phase in weight % relative to the total weight of the zircon body, and the ratio is at least 0.01, at least 0.05, at least 0.1, at least 0.5, at least 1, at least 1.5, at least 2, at least 2.5, at least 3, at least 3.5, at least 4, at least 4.5, at least 5, at least 5.5, at least 6, at least 6.5, at least 7, at least 7.5, at least 8, at least 8.5, at least 9, at least 9.5, or at least 10.
[0202] 56. The zircon body is C C3 / C C1 Including the ratio of C C3 is the content of the third crystalline phase in weight percent relative to the total weight of the zircon body, and C C1 is the content of the first crystalline phase in weight percent relative to the total weight of the zircon body, and the ratio is 200 or less, 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 48 or less, 45 or less, 42 or less, 40 or less, 38 or less, 35 or less, 32 or less, 30 or less, 28 or less, 25 or less, 22 or less, 20 or less, 18 or less, 15 or less, 12 or less, or 10 or less.
[0203] 57. The zircon body is C A / C C1 Including the ratio of C A is the content of the amorphous phase in weight percent relative to the total weight of the zircon body, and C C1is the content of the first crystalline phase in weight % relative to the total weight of the zircon body, and the ratio is at least 1, at least 1.5, at least 2, at least 2.5, at least 3, at least 3.5, at least 4, at least 4.5, at least 5, at least 5.5, at least 6, at least 6.5, at least 7, at least 7.5, at least 8, at least 8.5, at least 9, at least 9.5, at least 10, at least 11, at least 12, at least 13, at least 14, at least 15, at least 16, at least 17, at least 18, at least 19, at least 20, at least 22, at least 24, at least 26, at least 28, at least 30, at least 32, at least 35, at least 38, at least 40, at least 50, at least 60, or at least 70.
[0204] 58. The zircon body is C A / C C1 Including the ratio of C A is the content of the amorphous phase in weight percent relative to the total weight of the zircon body, and C C1 58. The refractory of embodiment 16 or 57, wherein: is the content of the first crystalline phase in weight percent relative to the total weight of the zircon body, and the ratio is 500 or less, 400 or less, 300 or less, 200 or less, 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 48 or less, 45 or less, 42 or less, 40 or less, 38 or less, 35 or less, 32 or less, or 30 or less.
[0205] 59. The zircon body is C C4 / C C1 Including the ratio of C C4 is the content of the fourth crystalline phase in weight percent relative to the total weight of the zircon body, and C C125. The refractory material of embodiment 24, wherein: is the content of the first crystalline phase in weight % relative to the total weight of the zircon body, and the ratio is at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 40, at least 45, at least 50, at least 55, at least 60, at least 65, at least 70, at least 75, at least 80, at least 85, or at least 90.
[0206] 60. The zircon body is C C4 / C C1 Including the ratio of C C5 is the content of the fourth crystalline phase in weight percent relative to the total weight of the zircon body, and C C1 60. The refractory of embodiment 24 or 59, wherein x is the content of the first crystalline phase in weight percent relative to the total weight of the zircon body, and the ratio is 9300 or less, 7000 or less, 5000 or less, 3000 or less, 1000 or less, 800 or less, 600 or less, 500 or less, 400 or less, 300 or less, 200 or less, 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 40 or less, 30 or less, 20 or less, or 10 or less.
[0207] Embodiment 61. The zircon body is C C5 / C C1 Including the ratio of C C5 is the content of the fifth crystal phase in weight percent relative to the total weight of the zircon body, and C C1 28. The refractory material of embodiment 27, wherein: x is the content of the first crystalline phase in weight percent relative to the total weight of the zircon body, and the ratio is at least 0.01, at least 0.1, at least 0.5, at least 1, at least 2, at least 3, at least 4, or at least 5.
[0208] 62. The zircon body is C C5 / C C1 Including the ratio of C C5 is the content of the fifth crystal phase in weight percent relative to the total weight of the zircon body, and C C161. The refractory material of embodiment 27 or 60, wherein x is the content of the first crystalline phase in weight percent relative to the total weight of the zircon body, and the ratio is 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 40 or less, 30 or less, 20 or less, 10 or less, 9 or less, 8 or less, 7 or less, 6 or less, 5 or less, 4 or less, or 3 or less.
[0209] 63. The zircon body is C C2 / C C1 Including the ratio of C C2 is the content of the second crystalline phase in weight percent relative to the total weight of the zircon body, and C C1 is the content of the first crystalline phase in weight percent relative to the total weight of the zircon body, and the ratio is at least 0.01, at least 0.1, at least 0.5, at least 1, at least 2, at least 3, at least 4, or at least 5.
[0210] 64. The zircon body is C C2 / C C1 Including the ratio of C C2 is the content of the second crystalline phase in weight percent relative to the total weight of the zircon body, and C C1 64. The refractory material of embodiment 13 or 63, wherein x is the content of the first crystalline phase in weight percent relative to the total weight of the zircon body, and the ratio is 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 40 or less, 30 or less, 20 or less, 10 or less, 9 or less, 8 or less, 7 or less, 6 or less, or 5 or less.
[0211] Embodiment 65. A method of forming a refractory body, comprising heating a green body to form a refractory body comprising zircon bodies, wherein the heating comprises a cooling rate of less than 2° C. / hr.
[0212] Embodiment 66. A method of forming a refractory body, the method comprising: forming a green body; heating the green body at a first temperature for a first period of time; and heating the green body at a second temperature lower than the first temperature for a second period of time to form a refractory body comprising zircon bodies.
[0213] Embodiment 67. The method of embodiment 65 or 66, further comprising cooling the substrate from the first temperature to the second temperature at a cooling rate of less than 2°C / hr, 0.8°C / hr or less, 0.7°C / hr or less, 0.6°C / hr or less, 0.5°C / hr or less, 0.4°C / hr or less, 0.3°C / hr or less, 0.2°C / hr or less, or 0.1°C / hr or less, and heating the substrate at the second temperature.
[0214] Embodiment 68. The method of embodiment 67, wherein the cooling rate is at least 0.01° C. / hr, at least 0.02° C. / hr, at least 0.03° C. / hr, at least 0.04° C. / hr, at least 0.05° C. / hr, at least 0.06° C. / hr, at least 0.07° C. / hr, at least 0.08° C. / hr, at least 0.09° C. / hr, or at least 0.1° C. / hr.
[0215] Embodiment 69. The method of embodiment 66 or 67, wherein the first temperature comprises a maximum heating temperature of at least 1500°C, at least 1550°C, or at least 1600°C.
[0216] Embodiment 70. The method of embodiment 66 or 67, wherein the first temperature comprises a maximum heating temperature of 1700°C or less, 1650°C or less, or 1625°C or less.
[0217] Embodiment 71. The method of embodiment 65 or 66, further comprising heating at the first temperature for a first period of time of at least 2 hours, at least 4 hours, at least 6 hours, at least 8 hours, or at least 10 hours.
[0218] Embodiment 72. The method of embodiment 65 or 66, further comprising heating at the first temperature for a first period of time of not more than 5 days, not more than 4 days, not more than 3 days, not more than 2 days, not more than 24 hours, not more than 20 hours, not more than 18 hours, not more than 16 hours, not more than 14 hours, or not more than 12 hours.
[0219] Embodiment 73. The method of embodiment 65 or 66, further comprising heating at the second temperature for a second period of at least 10 hours, at least 14 hours, at least 18 hours, at least 20 hours, at least 24 hours, at least 30 hours, at least 36 hours, or at least 2 days.
[0220] Embodiment 74. The method of embodiment 65 or 66, further comprising heating at the second temperature for a second period of time of not more than 6 days, not more than 5 days, not more than 4 days, not more than 3 days, not more than 60 hours, not more than 50 hours, not more than 48 hours, not more than 44 hours, not more than 40 hours, not more than 36 hours, or not more than 30 hours.
[0221] Embodiment 75. The method of embodiment 66 or 67, wherein the second temperature comprises a sintering temperature, and the sintering temperature is at least 1250°C, at least 1300°C, at least 1350°C, at least 1400°C, or at least 1425°C.
[0222] Embodiment 76. The method of embodiment 66 or 67, wherein the second temperature comprises a sintering temperature, and the sintering temperature is 1525°C or less, 1500°C or less, 1475°C or less, or 1450°C or less.
[0223] Embodiment 77. The method of embodiment 66 or 67, further comprising cooling from the second temperature to ambient temperature at a cooling rate of 5° C. / hr or less, 4° C. / hr or less, 3° C. / hr or less, 2° C. / hr or less, 1° C. / hr or less, 0.9° C. / hr or less, or 0.8° C. / hr or less.
[0224] Embodiment 78. The method of embodiment 66 or 67, further comprising cooling from the second temperature to ambient temperature at a cooling rate of at least 0.03° C. / hr, at least 0.04° C. / hr, at least 0.05° C. / hr, at least 0.06° C. / hr, at least 0.07° C. / hr, at least 0.08° C. / hr, at least 0.09° C. / hr, at least 0.1° C. / hr, at least 0.2° C. / hr, at least 0.3° C. / hr, at least 0.4° C. / hr, at least 0.5° C. / hr, at least 0.6° C. / hr, at least 0.7° C. / hr, at least 0.8° C. / hr, at least 0.9° C. / hr, or at least 1° C. / hr. EXAMPLES
[0225] Example 1 Sample S1 in the form of a block was fabricated. Raw materials containing 0.3 wt% CaO, 2 wt% Al2O3, 3 wt% mullite, 1 wt% Ta2O5 in balance with ZrSiO4 (93.7 wt%) were mixed in a slurry with the addition of binders and dispersants. The well-mixed homogeneous slurry was spray dried. Spray dried granules were formed and isostatically pressed under pressures of 100 MPa to 180 MPa. The block was sintered as follows:
[0226] The blocks were heated to a maximum temperature in the range of 1605°C-1620°C for 10 hours, cooled to 1350-1500°C at a cooling rate of 0.01-0.5°C / min, and held at 1350-1500°C for 24 hours. The blocks were cooled to room temperature at a cooling rate of 0.01-1°C / min.
[0227] The microstructure of the body of the block was analyzed using a scanning electron microscope and images are included in Figures 4 and 5. The amorphous phase 405 is dominated by a Ta-Ti-Fe rich crystalline phase (tapiolite type) 403 and a gehlenite (Ca2Al2SiO7) or prehnite (Ca2Al2Si3O 12 H2) are present in the crystals 407 that are rich in Ca-Al-Si.
[0228] Elemental mapping was used to analyze the microstructure. Table 1 contains the elemental concentrations of certain elements in the glass phase 405 and the mullite phase 411. The concentrations are relative to the total weight of the respective phase.
[0229] [Table 1]
[0230] Example 2 Sample C S 2 and C S Sample C was formed in the form of a block. S The raw materials for forming Sample C included 98 wt.% zircon sand, tantalum oxide (a sintering aid, 1 wt.%), and 1 wt.% silica. The zircon sand contained impurities including up to 0.5 wt.% alumina, 0.08 wt.% CaO, and less than 0.06 wt.% MgO by ICP analysis. S The raw materials for forming 3 included zircon sand (94 wt%, with the balance being additives), tantalum oxide (sintering aid, 1 wt%), mullite (3 wt%), and free alumina (2 wt%). The zircon sand contained 0.02-0.06 wt% CaO as an impurity.
[0231] The mixture of raw materials was mixed, molded, and sintered as described in the embodiments herein. Samples S1, C S 2, and C S Sample S1 was tested for creep deformation rate over the temperatures tested. FIG. 6 includes a plot of the creep deformation rate of the samples versus temperature. As described in Table 2 below and illustrated in FIG. 6, sample S1 exhibited creep deformation rate over the temperatures tested. S3 and C S It showed a significantly improved creep deformation rate compared with that of 2.
[0232] [Table 2]
[0233] Example 3 Samples S3 and S4 were formed in the form of blocks in the same manner as described for sample S1 using similar raw materials, except for the addition of 0.15 wt. % CaO for sample S3 and 0.6 wt. % CaO for sample S4. The CaO content for S3 and S4 is relative to the total weight of the respective raw materials.
[0234] FIG. 7 includes microstructural images of blocks S1, S3, and S4. As illustrated, more crystalline phases were present in samples S1 and S3 compared to sample S4. The samples were tested for creep deformation rate as described in embodiments herein. A plot of the creep deformation rate and tested temperatures of the samples is included in FIG. 8. S1 and S3 exhibited similar creep deformation rates over the temperatures tested, and showed improved creep deformation rates over sample S4.
[0235] Example 4 Using similar raw materials, except that 1 mol% BaO was added based on the total weight of the raw materials instead of CaO, sample S6 was formed in the form of a block in the same manner as described for sample S1. Samples CS3, S1, and S6 were tested for creep deformation rate as described in the embodiments herein. A plot of the creep deformation rate of the samples versus the temperatures tested is included in FIG. 9. S1 and S6 showed improved creep deformation rate over the temperatures tested than sample CS3.
[0236] Samples CS2, CS3, S1, and S6 were tested for blistering effects as described in the embodiments herein, and a significantly reduced number of bubbles can be observed at the interface between the glass material and the zircon material of samples S1 and S6 compared to samples CS2 and CS3, as illustrated in FIG.
[0237] Example 5 Additional samples were formed in the form of blocks in the same manner as described for sample S1 using similar raw materials, but with different dopants added at different contents. Samples S7, S8, S9, and S10 were formed with 0.125 mol%, 0.25 mol%, 0.5 mol%, and 1.0 mol% BaO, respectively, based on the total weight of the raw materials. Samples S11, S12, and S13 were formed with 0.125 mol%, 0.5 mol%, and 1.0 mol% SrO, respectively, based on the total weight of the raw materials. Samples S14, S15, S16, and S17 were formed with 0.125 mol%, 0.5 mol%, 1.0 mol%, and 2.0 mol% CaO, respectively, based on the total weight of the raw materials.
[0238] Samples S7-S17 and comparative sample CS3 were tested for creep deformation rate as described in the embodiments herein. The relative creep deformation rate versus dopant concentration for samples S7-S17 is illustrated in FIG. 11. The normalized creep deformation rate is calculated using the formula RCR S =CR S / CR C Determine the creep deformation rate of the representative sample by normalizing it to the creep deformation rate of the comparative sample using the formula: RCR S represents the normalized creep deformation rate of a representative sample (e.g., any one of S7 to S17), and CR S represents the creep deformation rate of the representative specimen, and CR C represents the creep deformation rate of the comparative sample (e.g., CS3). The relative value of the creep deformation rate of CS3 is 1, which is illustrated by the horizontal dotted line in FIG.
[0239] As illustrated, samples S9, S10, S12, S13, and S15-S17 show improved creep resistance compared to CS3. The BaO doped samples appear to have further improved creep resistance compared to the CaO or SrO doped samples at the same concentrations. For example, on average, the normalized creep deformation rate of sample S9 is lower compared to samples S12 and S15, and the normalized creep deformation rate of sample S10 is lower than S13 and S16.
[0240] Example 6 Samples S20-S22 were formed in the form of blocks in the same manner as described for sample S1 using similar raw materials except that instead of CaO, the dopants described in Table 3 were added at the indicated concentrations. The samples were tested for creep deformation rate as described in the embodiments herein and the results are included in Table 3.
[0241] [Table 3]
[0242] Sample S9 containing 0.42 wt% BaO showed improved creep deformation rate at the tested conditions compared to S8 containing 0.21 wt% BaO. It is noteworthy that S9 had improved creep resistance than S20-S22 doped with BaO and CaO, BaO and CaO, and BaO and SrO at total concentrations of 0.42 wt%, respectively.
[0243] Example 7 Samples S23-S38 were formed in the form of blocks in the same manner as described for sample S1 using similar raw materials except that instead of CaO, the dopants described in Table 4 were added at the concentrations specified. Sample CS4 was similarly formed except that no alkaline earth oxide dopant was used. The amorphous phase of the samples was analyzed using microprobe analysis, and the contents (in weight percent) of the components in the amorphous phase as determined by using wavelength dispersive X-ray spectroscopy are included below in Tables 4-5.
[0244] The samples were tested for creep resistance according to embodiments herein and the test results are included in Tables 4-6. Samples S24-S35 showed improved creep rates at some or all of the temperatures tested. Samples S23 and S39 did not show any improvement in creep rate.
[0245] [Table 4]
[0246] [Table 5]
[0247] [Table 6]
[0248] Tables 7 and 8 contain the compositions of the samples that were analyzed by performing ICP (also referred to as bulk ICP) on at least 0.25 g powder samples obtained from the crushed zircon body of each sample.
[0249] [Table 7]
[0250] [Table 8]
[0251] This application represents a departure from the prior art. Notably, embodiments herein show unexpected improved performance over zircon components formed according to conventional methods. Without wishing to be bound by a particular theory, it is suggested that certain combinations of materials in the zircon raw material mixture and in the formed zircon body material, including, for example, the content of alumina-containing compositions, the content of alkaline earth oxides, the presence of certain crystalline phases, the content of certain crystalline phases, the content of SiO2, the content of sintering aids, and the ratios of these components to each other, facilitate the formation of refractories or components having a unique combination of characteristics, including, but not limited to, low creep deformation rates at high temperatures, low blister values, crystalline phases including alkaline earth aluminosilicates, and the content of alkaline earth aluminosilicates in the final formed zircon body. In particular, it is notable that the unexpected synergistic effect of alumina or alumina-containing components with alkaline earth oxides facilitates the improvement of low creep deformation rates and low blister values of the zircon body.
[0252] It should be noted that in the general description or examples, not all of the activities described above are required, some of the specific activities may not be required, and one or more additional activities may be performed in addition to the activities described. Furthermore, the order in which the activities are listed is not necessarily the order in which they are performed. Any value of the characteristics or features of the embodiments herein may represent a mean or median value derived from a statistically relevant sample size. It will be understood that the composition is based on a total of 100%, and the total content of the ingredients does not exceed 100%, unless otherwise specified.
[0253] In the foregoing specification, the concepts have been described with reference to specific embodiments. However, those skilled in the art will recognize that various modifications and changes can be made without departing from the scope of the invention as set forth in the following claims. The specification and figures are therefore to be regarded in an illustrative rather than a restrictive sense, and all such modifications are intended to be included within the scope of the invention.
[0254] As used herein, the terms "comprises," "comprising," "includes," "including," "has," "having," or any other variations thereof, are intended to cover non-exclusive inclusions. For example, a process, method, article, or apparatus that includes a list of features is not necessarily limited to only those features and may include other features not expressly listed or inherent to such process, method, article, or apparatus. Further, unless expressly stated to the contrary, "or" refers to an inclusive or, not an exclusive or. For example, a condition A or B is satisfied by any one of the following: A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and both A and B are true (or exist).
[0255] Additionally, the use of "a" or "an" is used to describe elements and components described herein. This is done merely for convenience and to give a general sense of the scope of the invention. This description should be read to include one or at least one, and the singular also includes the plural unless it is clear that otherwise is meant.
[0256] Benefits, other advantages, and solutions to problems have been described above with respect to particular embodiments. However, the benefits, advantages, solutions to problems, and any features that may provide or make more prominent any benefit, advantage, or solution should not be construed as critical, necessary, or essential features of any or all of the claims.
[0257] After reading this specification, those skilled in the art will appreciate that certain features that are, for clarity, described herein in the context of separate embodiments, may also be provided in combination in a single embodiment. Conversely, various features that are, for brevity, described in the context of a single embodiment, may also be provided separately or in any subcombination. Further, references to values stated in ranges include any and all values within that range.
Claims
1. A refractory material, A body comprising at least 50 wt. % zircon, based on a total weight of the body, 1.8E-5h at 1350°C and 2MPa stress -1 below, 2.7E-6h at 1275°C and 2MPa stress -1 less than, 8.8E-6h at 1325°C and 2MPa stress -1 less than, 4.5E-6h at 1300°C and 2MPa stress -1 Less than, or a creep deformation rate of any combination thereof; The body comprises an amorphous phase, the amorphous phase comprising: an alkaline earth oxide including at least one of CaO, SrO, and BaO; At least 8% by weight and no more than 39% by weight of alumina, based on the total weight of the amorphous phase; the amorphous phase comprises a total content of the alkaline earth oxides greater than 3.5% by weight and less than or equal to 50% by weight, based on the total weight of the amorphous phase; A refractory material, wherein said amorphous phase comprises from 0.3% to 12% by weight of Ta2O5, based on the total weight of said amorphous phase.
2. 2. The refractory material of claim 1, wherein the amorphous phase comprises at least 3.2 wt.% and no more than 50 wt.% CaO, based on the total weight of the amorphous phase.
3. 2. The refractory material of claim 1, wherein the amorphous phase comprises at least 8 wt.% and no more than 50 wt.% BaO, based on the total weight of the amorphous phase.
4. 2. The refractory material of claim 1, wherein the amorphous phase comprises at least 9.6 wt. % and no more than 50 wt. % SrO, based on the total weight of the amorphous phase.
5. the amorphous phase having, based on the total weight of the amorphous phase, 40% to 80% by weight of silica; 5. The refractory material according to claim 1, comprising 10% to 30% by weight of alumina.
6. 5. The refractory material according to claim 1, wherein the body comprises a crystalline phase comprising zircon, the crystalline phase being at least 80% by weight, based on the total weight of the body.
7. 5. The refractory material of claim 1, wherein the body comprises a crystalline phase comprising mullite, sillimanite, andalusite, or any combination thereof, and the crystalline phase is at least 0.01 wt.% and not more than 20 wt.%, based on the total weight of the body.
8. 5. The refractory material of claim 1, wherein the body comprises at least 1 wt. % and no more than 12 wt. % alumina, at least 0.5 wt. % and no more than 10 wt. % mullite, or a combination thereof, based on the total weight of the body.
9. 5. The refractory material of claim 1, wherein the body comprises a crystalline phase comprising tantalum, iron, titanium, or any combination thereof.
10. A refractory material comprising a body, the body comprising: At least 75% and 99.5% by weight of zircon based on the total weight of the body; an amorphous phase of at least 0.5 wt.% and no more than 20 wt.% based on the total weight of the body, the amorphous phase having a total alkaline earth oxide content of greater than 3.2 wt.% and no more than 50 wt.% and at least 8 wt.% and no more than 39 wt.% alumina based on the total weight of the amorphous phase; A refractory material, wherein said amorphous phase comprises from 0.3% to 12% by weight of Ta2O5, based on the total weight of said amorphous phase.
11. 11. The refractory material of claim 10, wherein the body comprises at least 2 wt.% and no more than 15 wt.% of the amorphous phase, based on the total weight of the body.
12. the amorphous phase having, based on the total weight of the amorphous phase, 50% to 70% by weight of silica; 14% to 28% by weight of alumina; 4% to 12% by weight of Ta 2 O 5 The refractory material of claim 10 comprising:
13. 13. The refractory material of any one of claims 10 to 12, wherein the amorphous phase comprises CaO, BaO, SrO, or any combination thereof.
14. the amorphous phase having, based on the total weight of the amorphous phase, at least 4% by weight and not more than 50% by weight of CaO, At least 9.6 wt. % and not more than 50 wt. % SrO, at least 8% by weight and not more than 50% by weight BaO, or 13. The refractory material according to any one of claims 10 to 12, including any combination thereof.
Citation Information
Patent Citations
Basic castable refractory
JP1994144939A
Creep resistant refractory material used in glass manufacturing system
JP2005200295A
Low-creep zircon material using nano-additives and method for producing the same
JP2011500502A
Sintered zircon material for forming blocks
JP2016508951A
Method for making glass sheet including vehicle pretreatment of refractory
JP2017502910A
